A scale-undistorted test prediction method for ultra-high core earth-rockfill dam using multi-scale dynamic centrifuge model tests - Chaojun Han; Zhenggang Zhan; Sheng Zhu; Xingwen Gu; Wenjing Niu (Soil Dynamics and Earthquake Engineering, 2026)

Geostationary observations of air pollutants from biomass burning: A synergy of GIIRS and GEMS over Southeast Asia - Shan Han; Shangyi Liu; Mengya Sheng; Jhoon Kim; Ximin Cui; Minqiang Zhou; Wei Wang; Isamu Morino; Voltaire A. Velazco; Zhao-Cheng Zeng (Remote Sensing of Environment, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Melatonin attenuates gentamicin-induced cochlear hair cell injury by modulating the cGAS–STING signaling pathway - Han-gui Lu; Shuang-le Wang; Guo-feng Wen; Chuang-wei Li; Xin-sheng Lin (Tissue and Cell, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Long-term cultivation of indica–japonica hybrid rice increases grain yield, belowground carbon inputs, and soil organic carbon pools in paddy fields - Jinjia Gan; Sheng Tang; Lingli Mao; Fan Liu; Kefeng Han; Lianghuan Wu; Qingxu Ma (Field Crops Research, 2026)

Cadmium-associated cognitive impairment in adults: Proteomics-guided blood-based risk stratification with external validation and rat multimodal corroboration - Hao Gao; Hui Liu; Sheng Wan; Zhaokui Dan; Jianjun Xiong; Zelong Xing; Yinghui Yin; Feng Han; Yong Yang; Maoqin Tian; Qiwen Chen; Zhijian Hu; et al. (Environmental Pollution, 2026)

Straw-derived carbon powder (SDCP) and PDMS co-functionalized melamine sponge for high-efficiency oil-water separation - Ruiyi Han; Haiyang Huang; Jingjing He; Taipeng Jiang; Yingying Wang; Lingling Zeng; Sheng Chen; Jianyong Tang; Jin Li; Zhuwei Gao (Desalination, 2026)

Disguise strategy-adjusted controlled cleavage of DNA hydrogel for precision theranostics in colorectal cancer - Bo Han; Haitao Cui; Wenhui Chen; Zixiao Ma; Dandan Liang; Dongyang Wang; Jinghui Zhang; Juan Song; Sheng Tang (Chemical Engineering Journal, 2026)

Synergistic dual-site passivation via ionic liquid engineering for efficient and stable deep-red CsPbI₃ QLEDs - Xiaoke Li; Jinjian Lu; Rui Han; Xiaoqing Jing; Yuyu Zhang; Jintao Wang; Ren Sheng; Ping Chen (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Pea protein fibrils: Preparation via dynamic high-pressure microfluidization-assisted acid-heating & structure - Xiaoyu Xu; Guihua Sheng; Xinlin Wei; Haimei Bai; Qinshuo Han; Quancheng Zhou (Journal of Food Engineering, 2026)

Magnetic multi-metal oxides composites derived from steel slag for cost-effective phosphate removal and recovery: Characterization, performance, reutilization and mechanism - Sheng-Hui Yu; Xin-Yi Feng; Han-Bao Chong; Li Hua (Hydrometallurgy, 2026)

Mechanisms of high-humidity hot air impingement blanching (HHAIB) on microbial counts, functional properties, phenolic profile transformation, and volatile compounds in celery stalks (Apium graveolens L.) - You-Sheng Shi; Yu-Ting Ding; Jun Zhang; Jing-Shou Zhang; Shi-Han Yu; Fan Yang; Wei-Peng Zhang; Feng-Kui Xiong; Ming-Qiang Xu; Gang Shen; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Exploring hemopexin's antibacterial activity in bony fish: An immunological study of PoHpx-a - Sheng-han Gao; Yi-qi zhou; Wen Du; Qiu Jin; Fei Wang; Xue-peng Li (Fish & Shellfish Immunology, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Facile preparation of highly crystalline polyaniline nanosheets mediated by amphiphilic molecules for aqueous ZnI2 batteries - Gaijuan Guo; Xiaolu Wang; Hao Chen; Wenda Li; Shanze Ke; Hongyi Zhang; Nuo Chen; Kecheng Cao; Sheng Han; Shaohua Liu (Chemical Engineering Journal, 2026)

Ternary BiVO4/ZnIn2S4/Co-Pi photoanode with type-II heterojunction and hole-extraction cocatalyst for boosted photoelectrochemical water splitting - Zhenbiao Dong; Zhujunyan Liu; Bo Wang; Bowen Zhang; Meng Chen; Sheng Han (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

GHK-Cu enabled Zn-CaP biomimetic coating on titanium promotes immunomodulation driven vascularized osseointegration - Tong Sun; Chao Liu; Xinyao Liu; Guodong Zhao; Guowen Duan; Dongbiao Chang; Lulu Han; Mingyang Ma; Kunyue Zhang; Jun Sheng; Jiaojiao Yang; Xingyu Chen; et al. (Chemical Engineering Journal, 2026)

Evolution of swine influenza surveillance and one health governance in Taiwan: from zoonotic risk management to integrated preparedness - Cheng-Han Lin; Tzu-Min Lin; Meng-Wei Lin; Chih-Sheng Lin (Veterinary Research Communications, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Investigation of the contact pressure distribution between TBM disc cutter and rock surface using the 3D discrete element method - Jing-Ke Lu; Xiao-Ping Zhang; Han Zhang; Quan-Sheng Liu; Yong-Bin Liu; Pei-Qi Ji (Tunnelling and Underground Space Technology, 2026)

Rapid assessment method for lateral bearing capacity of row piles in levee-breach closure based on an improved p-y curve - Shu-Han Chen; Xing-Huai Huang; Yu Fang; Zhao-Dong Xu; Sheng-Yu Chang (Ocean Engineering, 2026)

Stronger actions are needed to advance PM2.5 mitigation and its health benefits under population aging in China: Evidence from China’s Clean Air Actions - Jian Qian; Ruoyu Li; You Zou; Jiayi Chen; Junyu Wang; Sheng Li; Na Yang; Tianyue Han; Xin Wang; Chenglin Tao; Nan Wang; Menglu Jiang; et al. (Journal of Hazardous Materials, 2026)

Global perspectives on the curricular integration of nature-based solutions in hydrology and water resources management education - Mark Bryan Alivio; Kristina Potočki; Pavel Raška; Peter Ameh Adegede; Tanveer Mehedi Adyel; Hafzullah Aksoy; Mary Bourke; Yonca Cavus; Mariana Madruga de Brito; Moctar Dembélé; Ashraf M. Elmoustafa; Kristian Förster; et al. (Journal of Cleaner Production, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Synthesis, characterization and application potential of recombinant chicken (Gallus gallus) ferritin with excellent iron-binding capacity and stability - Min Huang; Ranran Pang; Xiaojing Liu; Kai Zhou; Rong Sheng; Yuanyuan Wang; Changyuan Han; Binbin Xu; Han Li; Baocai Xu (Food Bioscience, 2026)

Rapid in-situ enrichment of anammox bacteria from activated sludge via nitrate induction: pilot-scale demonstration and mechanistic insights - Xin Gu; Haixu Shen; Hao Sheng; Xiang Li; Han Wang; Yayi Wang (Environmental Research, 2026)

Function identification of nitrogen forms in nitrogen-doped biochar for promoting methane production in anaerobic digestion - Xiao-Yue Cao; Cong-Cong Tang; Shuo-Han Chen; Sheng-Jie Sun; Chun-Xue Yang; Ai-Juan Zhou; Zewei Liu; Zhang-Wei He (Environmental Research, 2026)

Wave-induced pressure momentum under background currents and its impact on coastal dynamics - Jing Lu; Guoqi Han; Jinyu Sheng; Yong Teng; Chao Ji; Fangli Qiao (Dynamics of Atmospheres and Oceans, 2026)

Programming anisotropy: Magnetic field-assisted stereolithography 3D printing for multifunctional composites - Jinchen Han; Xianlei Shen; Junlu Sheng; Yuanyuan Zhang; Jianhua Yan (Chemical Engineering Journal, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Highly efficient perovskite-based electrocatalyst with in-situ nanoparticle exsolution and oxygen-vacancy enhancement for solid oxide cells - Tian Gan; Xinyu Zhou; Yujun Han; Wenya Zhen; Bin Sheng; Tianqi Li; Haoqi Yang; Ping Li; Yongdan Li (Chemical Engineering Journal, 2026)

F doping-induced interfacial built-in electric field and charge redistribution construction in CoS@NiCoLDH p–p heterojunctions for supercapacitors - Zihan Zhang; Qianqian Shan; Kairan Hu; Jie Yang; Jibo Jiang; Sheng Han (Chemical Engineering Journal, 2026)

A CO2-derived binder compatible with wet and dry cathode fabrication for lithium-ion batteries enabling highly easier materials recycling - Yuhao Wu; Min Xiao; Shuanjin Wang; Lei Zhong; Dongmei Han; Sheng Huang; Yuezhong Meng (Chemical Engineering Journal, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Predefined-time global prescribed performance tracking of ASV via adaptive event-triggered control - Peng Chen; Tao Han; Bo Xiao; Yuan Tan; Xi-Sheng Zhan; Ming-Feng Ge (Ocean Engineering, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

The impact of aftertreatment technology evolution on greenhouse gas emissions from heavy-duty trucks in China - Hongfei Chen; Rencheng Zhu; Gang Li; Yan Ding; Liang Ji; Junfang Wang; Xuexue Jing; Quankang Han; Fengbin Wang; Tengteng Li; Xianglin Zhong; Sheng Su; et al. (Environmental Pollution, 2026)

Effects of mesoscale eddies on near-bottom dynamics in the continental slope of northern South China Sea - Hao Chen; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Xiao-Dong Shang; Jia-Jing Chen; Ze-Yao Weng; Wen-Dong Fang; Yuan-Zheng Lu; Guang-Hui Han (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Decoupling ice lens initiation from growth via interface asymmetry - Han Yan; Sheng Zhang; Jidong Teng; Feng Shan; Jianlong Liu; Guojun Liu (Cold Regions Science and Technology, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

A Predictive Model for the Characterization of the Influence of Thermal Damage Defect Scale on the Mechanical Properties of MICP-Healed Rock Fractures: Insights from Microchanical Testing and Nano-CT Imaging - Qi-Chen Dai; Xiao-Hua Pan; Han-Jiang Lai; Chao-Sheng Tang; Zhi-Hao Dong (Rock Mechanics and Rock Engineering, 2026)

GATESynergy: Integrating Molecular Global-Local Aggregator and Hierarchical Gene-Gated Encoder for Drug Synergy Prediction - Yan Wang; Jiana Ding; Zhiyao Han; Chenxu Si; Yunzhi Liu; Nan Sheng; Lan Huang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

A Functional Limosilactobacillus reuteri ZY18 Strain: Probiotic Properties and Associated Anti-inflammatory Responses Against ETEC K88 Infection - Xin Xu; Jiahao Meng; Hongwei Zhang; Kun Meng; Zihan Zhang; Jiayi Sheng; Hongying Cai; Weiwei Liu; Yunsheng Han; Peilong Yang (Probiotics and Antimicrobial Proteins, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Research on high-efficiency region and condition of pectoral fin - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Ziqiang Ren; Han Ge; Haocai Huang (Ocean Engineering, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The sugar-sensing kinase OSK3-mediated destabilization of OsbZIP58 promotes pre-harvest sprouting in rice under high temperature - Heng Xu; Yuhong Tan; Fudeng Huang; Zhiping Deng; Ningning Zhang; Meihao Sun; Hua Zhang; Heng Zhang; Tao Song; Fulin Wang; Yu Han; Junmin Wang; et al. (Molecular Plant, 2026)

From stability to application: mechanistic insights into the stability and 3d printing of probiotic-loaded pea protein-based high internal phase pickering emulsions - Qinshuo Han; Guihua Sheng; Tingting Guo; Haimei Bai; Xinlin Wei; Xiaoyu Xu; Yaqi Liu; Jingjing Shi; Quancheng Zhou (Food Chemistry, 2026)

Block-structured thermoplastic polycarbonate-based polyurethane films for perovskite solar cells: Enabling low-temperature encapsulation, high barrier properties, and tunable mechanical properties - Yuting Ouyang; Zihan Zhao; Min Xiao; Dongmei Han; Sheng Huang; Dongqin Bi; Shuanjin Wang; Yuezhong Meng (Chemical Engineering Journal, 2026)

PPy/PDMS-functionalized delignified wood aerogel: Photothermal-electrical dual-energy empowerment and all-weather oil–water separation performance - Taipeng Jiang; Jian Wu; Jingjing He; Sheng Chen; Jianyong Tang; Yingying Wang; Lingling Zeng; Ruiyi Han; Haiyang Huang; Jin Li; Zhuwei Gao (Bioresource Technology, 2026)

Field Study of Immobilization Materials and Foliar Inhibitors: Balancing Rice Yield, Safety, and Economy in Cd-As Contaminated Soils - Junchun Li; Longyong Lin; Yirong Deng; Sheng Cheng; Xiao Yang; Xiulan Yan; Qian Yao; Cunliang Han (Water, Air, & Soil Pollution, 2026)

Efficient Reduction Remediation in Cd-Contaminated Farmland Soil Using a Synergistic Electrokinetic, Chemical Activation, And Adsorption Approach - Chenfeng Wang; Sheng Liu; Sheng Gao; Li Peng; Xintong Han; Long Cang; Genmei Wang (Water, Air, & Soil Pollution, 2026)

Invasions of alien plants pose unprecedented challenges to China’s nature reserves under climate change - Jia-Xin Wang; Rainer W. Bussmann; Fei Qin; Yun-Fen Liang; Bao-Cai Han; Hai-Yan Bi; Tian-Tian Xue; Sheng-Xiang Yu (Biodiversity and Conservation, 2026)

Migration and enrichment mechanisms of selenium, zinc, and iodine in the soil–plant–animal continuum of Yushu, Qinghai–Tibet plateau: insights from environmental geochemical factors - Zhao An; Siqi Han; Tao Wang; Haikui Tong; Li He; Changwei Qi; Qinyu Liu; Sheng Xue; Youning Wei; Yulong Li; Xiaojun Dong (Environmental Monitoring and Assessment, 2026)

Investigating Cerebello-Cortical Networks With EEG: Advances and Future Challenges - Ami Kumar; Sheng-Han Kuo (The Cerebellum, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Mechanistic insights into humidity-triggered bioaerosol emissions in greenhouses: Source dynamics and physics-based modeling - Xin Li; Leng Han; Chenyu Zheng; Yanxia Shi; Xuewen Xie; Lei Li; Tengfei Fan; Sheng Xiang; Ali Chai; Baoju Li (Environmental Pollution, 2026)

Unveiling the fate, exposure dynamics, and remediation challenges of emerging organic pollutants in e-waste - Zhuqi Xue; Lingen Zhang; Hui Li; Sheng Han (Chemical Engineering Journal, 2026)

Na-rich and high-voltage Na3V2(PO4)3/C cathode actualizes high-energy-density sodium-ion battery - Sheng Zhou; Donghui Chen; Xinchun Huang; Qile Duan; Han Zhou; Yong Fan; Liangwei Liu; Yi Xiao; Jizhou Jiang; Hui Zeng; Xiang Ding; Lili Han (Chemical Engineering Journal, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Age- and season-modulated water use strategies in mixed plantations of Betula alnoides and Castanopsis hystrix - Yu-han Chang; Bo-yao Chen; Chun-sheng Wang; Kai-li Liu; Hai-feng Yin; Jie Zeng (Agricultural and Forest Meteorology, 2026)

Impact Mechanical Behavior and Energy Dissipation Analysis of Rock-Concrete Composites with different Interface Roughness - Wei-jing Yao; Han-bing Xu; Sheng-qi Yang; Shao-ge Rui; Jian-yong Pang (Applied Geophysics, 2026)

Characterisation of Xianling Cifang Formula and its metabolites in the mice lung tissue and blood by UHPLC–HR-MS method - Rui Yang; Yixuan Wang; Yeying Jin; Guohui Han; Sheng Liu (Natural Product Research, 2026)

Dynamic dose–time proteomic profiling of cadmium exposure in rat prefrontal cortex - Zhijian Hu; Feng Han; Hao Gao; Sheng Wan; Hui Liu; Li Jie; Yinghui Yin; Maoqin Tian; Yong Yang; Wenjie Chen; Xiao Tan; Xinxin Shi; et al. (NeuroToxicology, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Subchronic, low-frequency polystyrene microplastic or nanoplastic exposure elicits molecular perturbations but minimal clinical phenotypes in the mouse gut-brain axis - Sheng-Han Lee; Han Chang; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Environmental Pollution, 2026)

Ecological network construction and resilience optimization of coastal zones in megacity clusters: A case study of the Guangdong–Hong Kong–Macao Greater Bay Area - Yilin Huang; Hui Li; Yun He; Qing Xu; Lixia Liao; Han Sheng; Jiaheng Du (Ecological Engineering, 2026)

The contributions of two fertilization events to the fertilization recovery efficiency in Arabidopsis - Yuan Wang; Yaxiao Liu; Wenhao Li; Han Lu; Li-Jia Qu; Sheng Zhong (Science China Life Sciences, 2026)

Genome-wide identification and promoter activity analysis of fibrillin gene families in different color carrot roots - Yu-Jie Sun; Rong-Rong Zhang; Zi-Han Zhao; Xu Zhang; Xue-Feng Peng; Ya-Hui Wang; Ai-Sheng Xiong (Protoplasma, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Magmatic source effects on Zircon Eu anomalies: Refining the Late Cretaceous–Eocene uplift of the Gangdese Arc, Southern Tibet - Guang-Sheng Ren; Jin-Gen Dai; Xiang-Rui Liu; Xu Han; Bo-Rong Liu; Jia-Qi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Green and scalable design of plant-based MoS2-OA Pickering nanofluids for simultaneous friction reduction and heat dissipation in sustainable metalworking - Wei Wang; Deping Xia; Xin Wang; Hualin Lin; Jingzhou Liu; Shuai Huang; Mingan Zhou; Bin Dai; Sheng Han (Journal of Environmental Chemical Engineering, 2026)

Synergistic improvement of cold flow properties in diesel fuel via urea dewaxing and pour point depressant addition - Yiqi Zhou; Jinyu Guo; Sanyan Du; Feifei Shi; Ke Chen; Bowen Xu; Hanwen Zhang; Jiabin Yin; Yuan Xue; Sheng Han (Fuel, 2026)

The effect of swirler structure on the combustion characteristics of ammonia-hydrogen flames in a miniature swirl combustor - Xiao Yang; Keqin Sheng; Mohan Li; Mengyu Wang; Dongtai Han; Xuanqi Liu; Li Yang; Fang Liu (Fuel, 2026)

Modifying pea protein via dynamic high-pressure microfluidization and polyphenol/polysaccharide incorporation to stabilize high internal phase Pickering emulsions for 3D printing - Leichao Dong; Guihua Sheng; Yajie Li; Tingting Guo; Yidan Ni; Haimei Bai; Qinshuo Han; Quancheng Zhou (Food Chemistry, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Long-term cultivation of indica–japonica hybrid rice reshapes the sustainability of rice systems by simultaneously enhancing yield, nitrogen use efficiency, and soil health - Jinjia Gan; Xinyue Xu; Sheng Tang; Kefeng Han; Tao Sun; Jinzhao Ma; Xiangde Yang; Xiu Liu; Haoran Fu; Zhihao Pang; Lingli Mao; Lianghuan Wu; et al. (European Journal of Agronomy, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

An integrated strategy for the efficient extraction and stabilization of phycocyanin from Limnospira platensis - Yuan-Yuan Li; Zhen-Wei Shi; Sheng-nan Yin; Hai-Bin Ren; Zi-Han Qu; Di-Feng Ren (Journal of Applied Phycology, 2026)

Investigation and Prediction of the Evolution of Medium-Long-Period Waves Across a Coral Reef - Xinyu Han; Sheng Dong (Journal of Ocean University of China, 2026)

USP52 impedes malignant progression and cell stemness in prostate cancer by deubiquitinating RBM5 to down-regulate NCAPG2 - Hongliang Wu; Sheng Wang; Shuai Yang; Wenyan Sun; Han Guan (Molecular and Cellular Biochemistry, 2026)

Study on GPR Forward Modeling and Intelligent Identification of Subgrade Defects Characterized by Hidden Voids - Bin Wu; Yan-li Qi; Qi-guang Cheng; Fan-meng Kong; Yu-xuan Han; Yiguo Xue; Yue-hua Wu; Sheng-yong Dong; Ze-zhou Kang; Zhe Zhang; Yong-feng Shi; Min Han (Applied Geophysics, 2026)

A stem-leaf segmentation method of maize plant point cloud based on region growing and leaf phenotypic parameters measurement - Mengjie Liu; Yanlong Miao; Yida Li; Wenyi Sheng; Ruicheng Qiu; Minjuan Wang; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Characteristics of environmental vibration induced by trains in underground stacked platform station - Anxiang Sheng; Liyun Li; Junyan Han; Xiuli Du (Tunnelling and Underground Space Technology, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Chlorogenic acid-modified pea dietary fiber stabilizes O/W emulsion - Leichao Dong; Guihua Sheng; Tingting Guo; Yajie Li; Yidan Ni; Qinshuo Han; Haimei Bai; Quancheng Zhou (Journal of Food Engineering, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Instantaneous ammonia emissions prediction for light-duty gasoline vehicles using ensemble learning - Jing Wang; Lei Zu; Han Jiang; Huayang Zhao; Haiguang Zhao; Mingliang Fu; Yitu Lai; Yunjing Wang; Sheng Su; Hefeng Zhang; Yan Ding (Fuel, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Development of 3D-printed pea protein-based vitamin D3 carrier emulsion gel system with high stability and its optimization - Qinshuo Han; Guihua Sheng; Haimei Bai; Xiaoyu Xu; Xinlin Wei; Quancheng Zhou (Food Hydrocolloids, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Modulating d-band center to construct Ptδ–Cuδ+ pairs for selective hydrogenation of renewable furfural - Liangmin Ning; Shuai Li; Shiyan Sheng; Jiuheng Ma; Jiawen Wang; Tianyu Zhang; Shun Wang; Jingyi Han; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Continuous flow synthesis of fluconazole monitored by inline ultraviolet spectroscopy: 3D microfluidic platform and Bayesian optimization - Jing Ren; Sheng Han; Guoyue Shi (Chemical Engineering Journal, 2026)

Dual-mode ion regulation via zwitterionic covalent organic frameworks enables high-performance all-solid-state lithium-metal batteries - Keliang Xu; Xiaokang Zhang; Yanbing Shen; Nuo Chen; Sheng Han; Ping Liu; Nana Li (Chemical Engineering Journal, 2026)

Mosses and cyanobacteria increased soil moisture and alleviated soil dehydration caused by dry-wet alternation in subtropical humid region - Ruyi Zi; Zhen Han; Qian Fang; Xiaoai Yin; Fayong Fang; Xiaohe Qian; Sheng Li; Longshan Zhao (CATENA, 2026)

Continuous cadaverine production using κ-carrageenan/polyethylenimine-immobilized cells with exceptional catalytic performance - Gongcheng Peng; Binhao Wang; Jiayu Cheng; Xiaoyu Wang; Junpeng Sheng; Jieyu Zhou; Rui-Zhi Han; Ye Ni; Jin-Jun Dong (Systems Microbiology and Biomanufacturing, 2026)

Physiological and molecular responses to sodium acetate addition and supplementation in the two stages of Haematococcus pluvialis - Yanbin Li; Weizhao Han; Na Li; Tian Xie; Xin Tan; Song Tang; Yequan Sheng; Bangxiang He (Journal of Oceanology and Limnology, 2026)

Dietary carbohydrate fuels a metabolic strategy for osmotic adaptation, enhancing growth and resilience of Litopenaeus vannamei in low-salinity water - Zhao Li; Zhi Luo; Sheng-Wei Lin; Feng-Lu Han; Chang Xu; Er-Chao Li (Aquaculture International, 2026)

A Soft Bionic Pectoral Fin Actuated by a Series of Differential Gear Units - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Peng Zhou; Han Ge; Haocai Huang (Journal of Marine Science and Engineering, 2026)
The bionic pectoral fin serves as the primary propulsion component of ray-inspired robots. In our previous research, a motion equation was proposed for the real pectoral fin, which can be modeled as a series of NACA airfoil-shaped cross-sections distributed along the spanwise direction. Each cross-section undergoes two coupled rotational motions about its chord line and spanwise rotational axis. To achieve this type of motion, this article introduces a novel bionic pectoral fin mechanism driven by a series of differential gear units. The differential unit generates two coupled rotational motions corresponding to the cross-section of the pectoral fin in motion. A series of interconnected differential units provides a unique topology for the bionic mechanism and can generate a diverse range of motions. Through kinematic analysis, the motion equation was mapped onto the rotational angles of motors in the differential units. The proposed bionic mechanism was then fabricated and subjected to experimental test, demonstrating its effectiveness with a maximum thrust of 0.71 N. The distinctive structure of this bionic mechanism differentiates it from conventional designs and is expected to provide some inspiration for bionic pectoral fins and ray-inspired robots.

SEAF-Net: A Sustainable and Lightweight Attention-Enhanced Detection Network for Underwater Fish Species Recognition - Yu-Shan Han; Sheng-Lun Zhao; Chu Chen; Kangning Cui; Pingfan Hu; Rui-Feng Wang (Journal of Marine Science and Engineering, 2026)
This study presents SEAF-Net, a lightweight and efficient detection network designed for low-contrast and highly dynamic underwater environments. Built upon YOLOv11n, SEAF-Net introduces three complementary structural enhancements: (1) Omni-Dimensional Dynamic Convolution (ODConv) to improve adaptive modeling of multi-scale and directional texture variations; (2) SimA-SPPF, which embeds the SimAM attention mechanism into the SPPF module to enable neuron-level saliency reweighting and effective suppression of complex background interference; and (3) GhostC3k2 to reduce redundant computation while preserving sufficient representational capacity. Evaluated on a standardized 13-class underwater fish dataset under a unified training and evaluation protocol, SEAF-Net achieves 6.1 GFLOPs, 92.683% Precision, 88.459% Recall, 93.333% mAP50, 73.445% mAP, and a 90.522% F1-score. Compared with the YOLOv11n baseline, SEAF-Net improves F1-score and Recall by 0.510% and 0.575%, respectively, while reducing computational cost by approximately 6%, demonstrating a favorable accuracy–efficiency trade-off under lightweight constraints. Ablation results further confirm that SimA-SPPF plays a dominant role in background suppression, ODConv consistently enhances deformation and directional texture modeling, and GhostC3k2 effectively controls computational overhead without degrading detection accuracy. To assess deployment feasibility, additional test set evaluations were conducted under deployment-oriented conditions using resource-limited hardware, yielding an F1-score of 88.54%. This result confirms that the proposed model maintains stable detection performance and robustness beyond training and validation stages. Overall, SEAF-Net provides an effective balance of accuracy, efficiency, and robustness, offering practical support for low-carbon, scalable, and sustainable intelligent aquaculture monitoring and underwater ecological assessment in real-world environments.

An efficient, scalable, and high-precision multifunctional intelligent navigation system for agricultural machinery - Jianxing Xiao; Qiang Sheng; Yajun An; Ning Wang; Tianhai Wang; Shunda Li; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Chronic co-exposure to BPA and alcohol synergizes hepatotoxicity via dysregulation of glycerolipid metabolism and ceramide/HtrA2-driven apoptosis in HepG2 cells - Yan Qin Tan; Chia-Lung Shih; Yi-Chia Chen; Sheng-Han Lee; Ji-Rui Yang; Chan-Yen Kuo; Yi-Shiou Chiou (Journal of Hazardous Materials, 2026)

Effects of A-site cations (Sm, Y, Gd) on methanol oxidation over AMn2O5 mullite catalysts - Liangzheng Lin; Zhitao Han; Junhao Jing; Shoujun Zhang; Shaoqin Sheng; Sihan Yin; Tingjun Liu; Chuanqiu Gao (Fuel, 2026)

Prenatal organophosphate esters exposure impacts placental structure and inflammatory markers in a trimester-specific manner - Yuan Liu; Ping Lv; Xing Wang; Mengqian Zhang; Yifan Wang; Sheng Wang; Mengjuan Lu; Han Li; Hong Gan; Juan Tong; Hui Gao; Fangbiao Tao (Environmental Research, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Preparation of Ion-Imprinted Polymer Based on Magnetic Attapulgite and its Adsorption Properties on Cd (II) - Yuliang Han; Jiahui Fang; Xinyuan Ji; Sheng Hu (Water, Air, & Soil Pollution, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

Fluid migration in calcite nanopores under salinity gradients: Insights from molecular dynamics - Yi Chen; Yan Zhang; Run-Sheng Han; Lei Wang (Acta Geochimica, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Carbon dioxide as the primary greenhouse gas emission in hard clam (Meretrix taiwanica) aquaculture - Yin-Yu Chen; Wei-Sheng Zhang; Chien‑Wei Tu; Bo-Ying Chen; Wen-Ping Cheng; Zhen Hao Liao; Yi-Jung Chen; Meng-Chou Lee; Fan-Hua Nan; Han-Yang Yeh (Aquaculture International, 2026)

Implementation of a Deep Learning Ensemble Framework Based on Bidirectional Message Queues - Xin-Jian Wei; Wu-Yang Yang; Xin Xu; Hai-Shan Li; Nan Wang; Wei-Sheng Wang; Han-Wei Lin; Chen Wang (Applied Geophysics, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

From recognition to defense: the multifaceted functions of PoPGRP-2 and PoPGRP-5 in Paralichthys olivaceus immunity - Yue Fang; Xiao-Dong Xu; Sheng-Han Gao; Jian Zhang; Xue-Peng Li (Aquaculture, 2026)

Periplasmic transport channels to accelerate the proton motive force for efficient groundwater bioelectrocatalytic Cr(VI) reduction - Huajing Zhou; Kun Wang; Liang He; Zilian Liu; Dianchao Kong; Qiang Zhang; Song Jin; Ying Han; Qingqing Guan; Guoping Sheng (Water Research, 2026)

Heavy metal distribution in MSW-derived soils and migration within the subjacent soil strata of landfills - Han Ke; Min Liang Fei; Chen Sheng Zhang; Liang Tong Zhan; Gui Bao Zhang; Ji Wu Lan; Xuan Qi Zhang; Shu Ning Zheng; Yun Min Chen (Waste Management, 2026)

More parks, more justice? Unpacking distributional and recognitional justice in Shanghai’s urban greening policies - Yuan Lu; Sun Sheng Han; Judy Bush (Urban Forestry & Urban Greening, 2026)

Hypoxanthine accumulation caused by mutations of Bombyx mori xanthine dehydrogenase triggers female sterility - Wen-qing Lai; Zhan-peng Lu; Qiang Zhang; Zuo-min Shao; Han Gao; Xia Sun; Sheng Qin; Xue-yang Wang; Mu-wang Li (Insect Biochemistry and Molecular Biology, 2026)

Promoting aerobic denitrification in the rhizosphere by vertical spatial stress: A strategy to enhance nitrogen conversion efficiency in constructed wetlands - Sheng-Jing Zhang; Hao-Qi Lu; Lei Yang; Li-De Wang; Bi-Han Zhang; Chao-Wen Deng; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Clumped isotopes tracing methane cycle and budget: a review - Xinchu Wang; Cong-Qiang Liu; Jiaxu Han; Jiarui Liu; Timothy Csernica; Naizhong Zhang; Hu Ding; Jonathan Gropp; Jennifer McIntosh; Si-Liang Li; Sheng Xu; Rob M. Ellam (Earth-Science Reviews, 2026)

Environmentally adaptive self-healing hydrogels via multiscale control of water molecules for human-machine interaction - Liping Li; Yang Yang; Wanhui Shi; Yunzhen Chang; Ying Zhang; Wenjing Hou; Sheng Zhu; Gaoyi Han (Chemical Engineering Journal, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Effect of clay content on the coupled seabed response and local scour around a free-spanning pipeline under combined waves and currents - Hongyi Zhao; Fei Lin; Yaru Gao; Zheng Wang; Mengxiao Li; Xiaoli Liu; Shuang Han; Dong-Sheng Jeng (Coastal Engineering, 2026)

Identification of a bHLH transcription factor (PcSPT) associated with the accumulation of differential volatile aroma compounds between occidental (Pyrus communis) and oriental (Pyrus pyrifolia) pear cultivars - Jiao Wang; Xian-Ping Guo; Dong-Sheng Wang; Zhong-Ying Wu; Peng Guo; Hui Jiang; Zhen-Zhen Lü; Yong-Ping Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Oxymatrine Alleviates Cerebral Ischemia/Reperfusion Injury By Targeting HDAC1 to Regulate Mitochondria-Related Autophagy and Oxidative Stress - Chang-Sheng Ma; Bo Han; Yu-Xi Liu; Chang-Ku Shi; Dong-Lun Li; Jin-Fen Guo; Min Bai; Shu-Chen Meng; Li-Ying Zhang; Meng-Yuan Duan; Mao-Tao He (Molecular Neurobiology, 2026)
Oxymatrine (OMT), a major alkaloid extracted from Sophora flavescens, has been widely recognized for its anti-inflammatory and anti-cancer properties. However, its precise neuroprotective mechanisms in cerebral ischemia/reperfusion (I/R) injury remain to be fully elucidated. In this study, we combined in vivo and in vitro models to investigate the therapeutic effects of OMT on cerebral I/R injury and glutamate-induced neuronal toxicity during the reperfusion process. In vivo, a mouse middle cerebral artery occlusion (MCAO) model was established to recapitulate I/R injury, whereas glutamate-exposed HT22 hippocampal neurons were utilized as an in vitro model to mimic excitotoxic damage. Bioinformatics analysis, integrated with molecular docking, identified histone deacetylase 1 (HDAC1) as a potential direct target of OMT. Subsequent experimental validation demonstrated that OMT attenuates I/R-induced brain damage by modulating HDAC1-mediated pathways involved in autophagy and oxidative stress regulation. OMT treatment significantly reduced infarct volume and improved neurological function in mice. At the cellular level, OMT suppressed mitochondrial apoptosis and reactive oxygen species (ROS) accumulation, restored mitochondrial membrane integrity, and rebalanced mitochondrial dynamics by downregulating fission-related proteins (Fis1) and upregulating fusion markers (Mfn2). Additionally, OMT inhibited excessive autophagy through modulation of the PINK1/Parkin signaling pathway, as evidenced by decreased expression of LC3-II/I ratio, PINK1, Parkin, and NBR1, along with restored levels of P62.These findings suggest that OMT exerts its neuroprotective effects in cerebral I/R injury by targeting HDAC1, thereby alleviating oxidative stress and excessive autophagy. This study provides new mechanistic insights and supports OMT as a promising therapeutic candidate for ischemic stroke treatment. Graphical Abstract

Comparison of soil enzyme activity and stoichiometry between urban park and forest in the Pearl River Delta region, China - Han Sheng; Xu Li; Luis Carlos Ramos Aguila; Fasih Ullah Haider; Shu-Yi-Dan Zhou; Guopeng Wu; Chushu Meng; Yunxuan Deng; Juxiu Liu (Applied Soil Ecology, 2026)

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

A 3D phenotyping pipeline for peanut plants using point cloud - Bo Zhang; Xin Yang; Xiaodan Han; Guowei Li; Xianju Lu; Bo Bai; Haisheng Liu; Teng Miao; Sheng Wu; Xinyu Guo (Computers and Electronics in Agriculture, 2025)

Boosting carbonate radicals production to enhance photocatalytic Degradation of micropollutants - Keng-Qiang Zhong; Han-Chao Zhang; Dong-Hua Xie; Pu-Can Guo; Xin Zhang; Wen-Hua Zhang; Guo-Ping Sheng (Water Research, 2025)

Physics-inspired dynamic boosting framework for capturing water and mud inrush evolution in tunnel fault fracture zones - Guorong Han; Jinchang Sheng; Ruiqing Han; Huimin Wang (Tunnelling and Underground Space Technology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Nonlinear hydrodynamic investigation of medium-long period waves and BSB - Xinyu Han; Sheng Dong (Ocean Engineering, 2025)

Application of infrared thermal imaging based on HSV images in identification of sludge volume characteristics in the settling tank - Yang Liu; Wenzhuo Wang; Zhiwu Han; Yansong Wu; Sheng Wei; Dong Li; Hanbing Qi (Journal of Water Process Engineering, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

6-PPD induces mitochondrial dysfunction and reduces healthspan and lifespan through SKN-1 in Caenorhabditis elegans - Moonjung Hyun; Laxmi Rathor; Hye-Jin Kim; Ho-Jeong Lee; Taylor McElroy; Moongi Ji; Min-Seok Choi; Steven Beck; Julia Bailey; Hun Hwan Kim; Yi Sheng; Jeong-Doo Heo; et al. (Journal of Hazardous Materials, 2025)

Strategic bidding for coal-fired generation units considering China's deep peak regulation capacity market - Liuhan Lan; Xingping Zhang; Tsan Sheng Ng; Qinliang Tan; Yingzhu Han (Journal of Cleaner Production, 2025)

Soil organic carbon decline under bamboo invasion: The role of microbial carbon cycling - Chushu Meng; Chaotang Lei; Xu Li; Han Sheng; Guopeng Wu; Juxiu Liu; Shu-Yi-Dan Zhou (Journal of Environmental Management, 2025)

S-scheme WO3-x/MoS2 heterojunction photocatalysis coupling with micro-nano bubbles technology for enhanced antibacterial disinfection in water - Qiang Mao; Kai Wei; Tianyu Li; Jiasheng Zhu; Huarui Han; Kan Hu; Changchang Ma; Sheng Feng (Environmental Research, 2025)

Translational–torsional coupling adaptive variable-stiffness control of large podium multi-tower structure - Han Zhang; Sheng Li; Liangkun Wang; Weixing Shi (Engineering Structures, 2025)

Machine learning-aided design of adapted water treatment adsorbents: Advances, challenges, and opportunities - Ling Yuan; Sheng Li; Yujia Ma; Han Zhang; Chen Chen; Weiming Zhang; Yanyang Zhang; Ming Hua; Lu Lv; Bingcai Pan (Chemical Engineering Journal, 2025)

Photo-driven valorization of lactate in human sweat for controllable production of fuels and value-added chemicals - Yu Gao; Rui Zhu; Tengteng Han; Tianran Sheng; Xiaodong Liu; Ming Zhou; Yuchen Ding; Yude Su (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Lignin nanoparticles mediated self-adhesive and conductive hydrogel electrolytes for high-performance flexible supercapacitors - Jiabin Han; Yuxin Song; Jiangbo Li; Bing Wang; Jian Zhang; Shuyi Li; Xingwen Wang; Na Li; Xueru Sheng; Haiqiang Shi; Changyou Shao; Runcang Sun (Chemical Engineering Journal, 2025)

Optimal design of a solar and geothermal system for improving the indoor thermal environment of temporary houses in cold climates - Wei Han; Yongcai Li; Fangqi Lu; Sheng Li; Wuyan Li; Zixiong Qin (Building and Environment, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

CircNOX4 promotes proliferation and resistance by regulating the hsa-miR-6884-5p/YWHAG Axis and ERK signaling pathway in cholangiocarcinoma - Zhangdi Yan; Lixin Du; Yingdi Han; Kangshuai Li; Guoli Sheng; Xudong Wang; Yunjia Liu; Yuankun Zhang; Jian Deng; Zengli Liu; Yunfei Xu; Zongli Zhang; et al. (Functional & Integrative Genomics, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

New aromatic butenolides from the plant endophytic fungus Malbranchea umbrina D16 - Xian-An Chen; Han-Zhuang Weng; Lei-Ming Wu; Shu-Qi Wu; Rong Pu; Tao Yuan; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Comparative transcriptome analysis reveals defense mechanisms of Bacillus velezensis ZY1 against bacterial fruit blotch in watermelon - Haoyu Wei; Tingchang Zhao; Yushanjiang Maimaiti; Tielin Wang; Sheng Han; Wei Guan; Yuwen Yang (Physiological and Molecular Plant Pathology, 2025)

Retraction notice to “Bivariate validation of the Gaidai natural hazard evaluation method for climate dynamics” [Ocean Eng. 313, (3) (2024) 119630] - Chaoshuai Han; Oleg Gaidai; Mahmoud El-Wazery; Shicheng He; Alia Ashraf; Jinlu Sheng; Yan Zhu (Ocean Engineering, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

A systematic survey and meta-analysis of the segment anything model in remote sensing image processing: Challenges, advances, applications, and opportunities - Zhipeng Wan; Sheng Wang; Wei Han; Yuewei Wang; Xiaohui Huang; Xiaohan Zhang; Xiaodao Chen; Yunliang Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Thermally triggered tunable-thermal-conductivity phase-change composites for lithium-ion battery thermal management and runaway mitigation - Tianyi Li; Junxiu Piao; Dongliang Xu; Yuhui Meng; Lifu Zhang; Xu Han; Xiaoran Yang; Linze Jin; Sheng Bi (Chemical Engineering Journal, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

[3 + 2 + 1] iridium(III) complexes for high-efficiency saturated red organic light-emitting diodes - Ping Chen; Qingwu Wu; Gui-Yan Yang; Qifei Xie; Sheng Yu; Ming-Yu Teng; Huabo Han; Guo-Li Huang; You-Xuan Zheng; Guangzhao Lu (Chemical Engineering Journal, 2025)

Z-scheme heterojunction engineered covalent organic polymer for thermodynamically optimized CO2 photoreduction - Jiaxin Rong; Xuejing Li; Qiang Xu; Jingwei Han; Jing Zhang; Ke Ren; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

The response of plant-derived lignin phenols accumulation to nutrient addition depends on soil depth in a subtropical plantation - Jin He; Dong Bu; Yuan-Huang Zeng; Shui-Bo Han; Wen-Qing Li; Fu-Sheng Chen; Ying-Ying Zong; Yu-Xin Huang; Yang Zhang; Xiang-Min Fang (Plant and Soil, 2025)

4-Hydroxychalcone alleviated Angiotensin II-induced atrial fibrillation via immunoproteasome-IKK-NF-κB signaling pathway modulation - Yun-Long Zhang; Ze-Yan Xu; Yan Sun; Qian-Qiu Zhu; Sheng-Xing Tang; Qing-Hua Zhong; Xiao Han (Journal of Molecular Medicine, 2025)

Hanging drop culture reprograms mesenchymal stem cell transcriptome to enhance cell delivery efficiency via attenuated pulmonary entrapment - Hsiang-Tzu Lee; Sheng-Yung Fu; Wei-Han Weng; Wei-Chen Chao; Yu-Pao Hsu; Nan-Ping Yang; Yu-Hsu Chen; Shau-Kwaun Chen; Chien-Wen Chang (Drug Delivery and Translational Research, 2025)
The three-dimensional (3D) culture system has emerged as an indispensable platform for modulating stem cell function in biomedicine, drug screening, and cell therapy. Despite a few studies confirming the functionality of 3D culture, the molecular factors underlying this process remain obscure. Here, we have utilized a hanging drop method to generate 3D spheroid-derived mesenchymal stem cells (3D MSCs) and compared them to conventionally 2D-cultured MSCs. The results showed that 3D MSCs exhibited distinct phenotypic features than 2D-cultured MSCs and expressed different transcriptional responses, as found from RNA-Seq analysis. Gene ontology (GO) annotations and KEGG pathway mapping pinpointed that the 3D MSCs responded more actively to incoming signals as they upregulated receptors and cytokine production while downregulating proteolysis-, cytoskeletal-, extracellular matrix-, and adhesion-related genes. Functionally, these MSCs also displayed enhanced chemotaxis and improved pulmonary transgression post-intravenous injection. This study provides mechanistic insights on addressing a significant limitation of MSC therapy: pulmonary entrapment after systemic delivery. Moreover, upregulated pluripotency-associated genes, such as Oct4, Sox2, and Nanog, suggest that the 3D MSCs possessed enhanced stemness and regenerative capacity. The results indicate that 3D spheroid culture reshapes MSC transcriptomic and functional profiles and emerges as a promising strategy for improving their therapeutic potential in regenerative medicine. Graphical abstract

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Hematological metabolic characteristics and dynamic regulation of free amino acids in muscle and ink in response to inkjet-induced stress in Sepia pharaonis - Ao Meng; Wencheng Xiao; Ruibing Peng; Xiamin Jiang; Qingxi Han; Sheng Li; Maowang Jiang (Aquaculture International, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Novel arneomas A-B and other naphthoquinone active components in Arnebia euchroma I. M. Johnst - Li-Li Han; Yibanuer Reheman; Reyilanmu Maisaidi; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Natural Product Research, 2025)

Harnessing PoSAP, a serum amyloid P component in Japanese flounder (Paralichthys olivaceus) for superior antibacterial immunity in teleost fish - Sheng-han Gao; Jia-qi Sun; Kun-yu Zhao; Gang Li; Jian Zhang; Xue-peng Li (Aquaculture, 2025)

The roles of non-governmental organizations in the co-production of urban greenspaces in Beijing - Luquan Liang; Jennifer Day; Sun Sheng Han (Urban Forestry & Urban Greening, 2025)

Numerical simulation of the methanol spray combustion process in a confined tube with obstacles - Zhuangzhuang Xu; Zhonghua Sheng; Han Sun; Xiaoxing Yang; Shengzheng Ji; Yue Yu; Guogang Yang (Process Safety and Environmental Protection, 2025)

Structures and antitumor activities of Arnegutones A–C: A study of three novel active components extracted from Arnebia euchroma - Li-Li Han; Guang-Jie Pan; Si-Qi Li; Yibanuer Reheman; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Phytochemistry Letters, 2025)

Beyond nitrate: NRT1.1B as an ABA receptor - Han-Qing Wang; Sheng Luan (Molecular Plant, 2025)

From fragmentation to integration: Evolving community structure of the Asia-Pacific shipping network since 1890 - Han Su; Liehui Wang; Sheng Zhang; Debin Du; Cesar Ducruet (Journal of Transport Geography, 2025)

Perfluorohexanoic acid exhibits more potential for the proliferation, migration, and invasion of triple-negative breast cancer cells under the 3D culture model - Jing Han; Huan Wang; Sheng Wei; Yawen Chen; Ting Xu; Daqiang Yin (Journal of Hazardous Materials, 2025)

Acid-treated chestnut shell-derived carbon dots for sensitive detection of dinotefuran in urban domestic wastewater - Tianyu Li; Huarui Han; Qiang Mao; Jiasheng Zhu; Liying Cai; Kai Wei; Changchang Ma; Kan Hu; Sheng Feng (Journal of Environmental Chemical Engineering, 2025)

A label-free and naked-eye fluorescence turn-on assay for one-pot LAMP detection of foodborne pathogens using AuNCs-Cu2+ complex - Fuyuan Huang; Paner Jiang; Yiliang Chen; Weiwei Wang; Yaxin Han; Chenlu Chen; Guangxin Xiang; Sheng Ye; Laibao Zheng (Food Chemistry, 2025)

Experimental and numerical study on vibration attenuation performance of 3D printed single-phase metamaterial plate with broad low-frequency complete bandgap - Te-Han Chu; Sheng-Hsiang Tsai; Yu-Jui Liang (Engineering Structures, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Dual-photons coupling over NiCo2S4-based composite photoelectrode for solar-driven supercapacitors - Zhenbiao Dong; Qiange Zhang; Junyao Li; Jin Li; Bowen Zhang; Sheng Han (Chemical Engineering Journal, 2025)

Optimizing metal-organic frameworks for adsorption-based atmospheric water harvesting: A systematic evaluation of pristine and modified MOFs for enhanced performance in diverse climates - Bo Han; Mai Sheng Ng; Anutosh Chakraborty (Chemical Engineering Journal, 2025)

Microtremor survey for exploring intermediate-to-deep geothermal resources in the urban periphery: A case study of Xining city - Sheng He; Xiao-long Han; Jing-he Li; Yu-guo Lu; De-ming Zhang; Jian-jun Hou (Applied Geophysics, 2025)

Seismic Data Interpolation by AVO-Preserving Hyperbolic Radon Transform Using FISTA and Polynomial Fitting - Sheng-chao Wang; Han-feng Liu; De-fu Zhang; Hui Sun; Wei Zhang; Song-da Ji (Applied Geophysics, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Insight into the spread potential of antibiotic resistance genes during aerobic biofilm treatment of ofloxacin-containing rural domestic sewage - Bingbing Feng; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bo Zhang; Jingjing Zhang; Sheng Sheng (Process Safety and Environmental Protection, 2025)

Utilization of oxided tamarind polysaccharide gum as novel selective depressant in the flotation separation of copper-lead-zinc sulfide ore - Tichen Wang; Jiushuai Deng; Hao Zhang; Dingquan Xing; Zhiguo Han; Jie Sheng; Chul B. Park (Process Safety and Environmental Protection, 2025)

Revisiting the quantitative relationship between groundwater evapotranspiration and water table depth: A numerical study - Shu-Cong Tan; Xiao-Wei Jiang; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Li Wan; Yi-Jian Zeng (Journal of Hydrology, 2025)

Application of spectral induced polarization technique in monitoring zinc removal by activated carbon as a permeable reactive barrier material - Sheng Zhou; Yi-Xin Yang; Jing-Jing Cao; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Contaminant Hydrology, 2025)

An analytical drained solution based on graphical method for wellbore drilling problem in dilatant Mohr-Coulomb rock formations - Xu Wang; Yan-Hui Han; Sheng-Li Chen; Younane Abousleiman (International Journal of Rock Mechanics and Mining Sciences, 2025)

Particle size distribution (PSD) of mine waste dump via unmanned aerial vehicle (UAV) image recognition and sieving - Han Ke; Zi Han Lin; Xiao Fei Wei; Bing Zhou; Tian Shou Hu; Shuai Zhang; Jie Hu; Chen Sheng Zhang (Engineering Geology, 2025)

Bioactive Cu/Zn-loaded micro/nano coatings on titanium promoting antibacterial effects, immune response, and bone integration - Zian Wang; Xinyao Liu; Guowen Duan; Long Chen; Lulu Han; Zili Guo; Dongbiao Chang; Chengdong Zhang; Chao Liu; Mingyang Ma; Jun Sheng; Tong Sun; et al. (Chemical Engineering Journal, 2025)

Prolonging the operation of lithium metal batteries by inhibiting corrosion with a polymer binder coating - Lanhang Li; Hongyan Li; Qingyue Han; Yiyu Huang; Tianyu Wang; Lei Sun; Hongxian Zhang; Ziyue Zhang; Lijing Yan; Chengbin Jin; Ouwei Sheng (Chemical Engineering Journal, 2025)

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Geochemical remediation and spectral induced polarization monitoring of Cu2+ by geographically abundant paleosol and loess - Yi-Xin Yang; Sheng Zhou; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Water Process Engineering, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Investigation of ternary vapor-liquid equilibrium for refrigerant mixtures containing HFOs: Simple and accurate predictive models - Hong Yuan; Zhiqiang Yang; Christophe Coquelet; Yuanhao Liao; Jijun Zeng; Bo Zhao; Sheng Han; Wei Zhang; Jian Lu (International Journal of Refrigeration, 2025)

Modes of occurrence of rare earth elements and yttrium in bituminous coals with different ranks from the Hedong Coalfield, northern China - Zhenyu Xu; Xiaomei Wang; Fan Deng; Xingxing Guo; Yuxuan Han; Ke Sheng; Yuanhe Mu; Qin Yang (International Journal of Coal Geology, 2025)

Characteristics and influence factors of ammonia emissions from light-duty vehicles under real-world driving conditions - Xian Wu; Han Jiang; Haiguang Zhao; Yitu Lai; Lei Zu; Yunjing Wang; Mingliang Fu; Sheng Su; Yan Ding (Fuel, 2025)

Ionic liquid-functionalized metal-organic frameworks adsorbents for effective extraction of dibutyl phthalate in edible oil: A new strategy for selectivity and low cost - Qian Yang; Yuwei Zhang; Lei Han; Jun Sheng; Yang Tian (Food Chemistry, 2025)

Single-cell sequencing and spatial transcriptomics reveal FAS+ T cell and autophagy-related signatures predicting chemoimmunotherapy response in diffuse large B-cell lymphoma patients - Ning Lou; Liyuan Dai; Ruyun Gao; Jianliang Yang; Lin Gui; Sheng Yang; Peng Liu; Yuankai Shi; Xiaohong Han (Science China Life Sciences, 2025)

Stratigraphic information underneath Chang’e-4 landing area as revealed by the ejecta of Zhinyu crater - Bingyao Han; Zongyu Yue; Sheng Gou; Huacheng Li (Advances in Space Research, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Single-Session Feasibility of Cough Skill Training in Cerebellar Ataxia - James C. Borders; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2025)

Activation of the CNGC2–CNGC4 channel complex by P2K1-mediated phosphorylation links extracellular ATP perception to calcium signaling in plant immunity - Yujia Sun; Lei Gao; Yiping Han; Changxin Feng; Zebin Liu; Chunyan Li; Yuxin Dong; Shuxin Yin; Laihao Liu; Ming Yang; Qi Niu; Dongdong Kong; et al. (Molecular Plant, 2025)

A vision-language foundation model-based multi-modal retrieval-augmented generation framework for remote sensing lithological recognition - Xiaodao Chen; Yupeng Liu; Wei Han; Xiongwei Zheng; Sheng Wang; Jun Wang; Lizhe Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Two-step cascade degradation of Dongming lignite over Mo/N co-doped ZIF-67-based Co-Mo15@NC - Guang-Hui Liu; Hao-Dong An; Han Wang; Ya-Jun Ma; Yan-Jun Li; Yu-Hong Kang; Jie Kang; Wei Zhao; Sheng-Kang Wang; Xian-Yong Wei (Fuel, 2025)

MoSe2 hybrid superlattice with expanded interlayer spacing and enriched 1T phase for aqueous zinc ion batteries - Jia-Ning Yang; Han Tian; Shang-Qi Li; Kai-Xue Wang; Jie-Sheng Chen (Chemical Engineering Journal, 2025)

A Rock Strength Prediction Model Utilizing Real-Time Data from Percussion–Rotary Drilling Measurements - Guo-Hua Zhang; Jia-Cheng Yu; Zhao-Yang Han; Sheng-Lian Li; Lu-Zhao Dan; Dong-Jie Hua; Feng Xiong; Yu-Yong Jiao (Rock Mechanics and Rock Engineering, 2025)

Synergistic effects of low-concentration nanoparticles and Bacillus megaterium on the growth of roses and rhizosphere microbial communities - Meng Zou; Hao Liu; Kai Yu; Ying Chen; Yu Huang; Ning Feng; Jing Bai; Dexing Ma; Guodong Xu; Dou Dou; Han Ma; Yunjiao Han; et al. (Plant and Soil, 2025)

Physiological and molecular insights into color variation and light intensity adaptation in Eucheuma perplexum with applications for selective cultivation - Ji-Long Liao; Zih-Ning Ding; Ya-Han Hsu; Jui-Sheng Chang (Algal Research, 2025)

Converting larch monocultures to mixed-species forests: Ten-year impacts of canopy manipulation on understory regeneration - Yuan Gao; Xiaoyu Wang; Qiang Liu; Jinxin Zhang; Xiaoyi Han; Sheng-I Yang; Deliang Lu (Forest Ecology and Management, 2025)

Intercatenation weaves MOFs with conductive networks as iodine hosts for zinc-iodine batteries - Gaijuan Guo; Qiaoling Dai; Wenda Li; Shanzhe Ke; Hao Chen; Hongyi Zhang; Liguo Ma; Sheng Han; Shaohua Liu (Chemical Engineering Journal, 2025)

Mechanistic insights into effects of the electronic configurations and crystal structures of iron sulfides on the two-stage Fenton degradation for benzene - Cong Liang; Lei Yang; Jing Li; Lu Han; Yudong Feng; Mengfang Chen; Hangyu Li; Zhen Ni; Zhenyu Kang; Hongtao Sheng; Linbo Qian (Chemical Engineering Journal, 2025)

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Behind greenspace provision: Stakeholders’ perceptions of the co-production of urban parks in Beijing - Luquan Liang; Sun Sheng Han (Urban Forestry & Urban Greening, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The molecular mechanism of transcription factor regulation of grain size in rice - Yanxiu Du; Chun Ye; Peijie Han; Yile Sheng; Fei Li; Hongzheng Sun; Jing Zhang; Junzhou Li (Plant Science, 2025)

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

Engineered injection and extraction combined with in situ oxidation remediation at an industrial site and evaluation of contaminant plume dynamics - Shu Ning Zheng; Zhan Hong Qiu; Jie Hu; Hai Jie He; Min Liang Fei; Chen Sheng Zhang; Han Ke (Journal of Contaminant Hydrology, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Influence of natural aromatic ether extracts (estragole, methyleugenol and α-asarone) on the depressive effects of polymethacrylate copolymers as additives for diesel fuel - Wenjing Zhu; Xiuwei Lei; Honggang Wang; Hualin Lin; Sheng Han (Fuel, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Surface SnO2 Decoration: An economical and efficient alternative to Pt shells in Pt-Co catalysts for enhanced oxygen reduction reaction - Yongjun Jiang; Tzu-Hsi Huang; Kuang-Yen Chiu; Sheng-Wei Lee; Tsan-Yao Chen; Yanyan Jia; Jeng-Han Wang; Kuan-Wen Wang; Sheng Dai (Chemical Engineering Journal, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

A dual-cycle DNA walker sensor for sensitive clinical detection of microRNAs - Yu Han; Xudan Shen; Haihong Hu; Su Zeng; Jun Zhe Min; Jiabin Li; Sheng Cai (Analytica Chimica Acta, 2025)

Transitional behavior of calcareous sand with different clay contents - Hongyi Zhao; Yaru Gao; Fei Lin; Jinhai Zheng; Dong-Sheng Jeng; Shuang Han; Junwei Liu; Yifei Sun (Frontiers in Marine Science, 2025)
Calcareous sand with fines content was often encountered in offshore and onshore engineering. However, most previous research has primarily focused on the mechanical properties of clean calcareous sand. This study conducted a series of drained and undrained triaxial tests on calcareous sand-clay binary mixtures to investigate the impact of fines content on the strength and deformation characteristics of calcareous sand. The results indicate that specimens with varying fines content exhibit both strain hardening and softening behaviors under different confining pressures. With the addition of fines content from 0% to 10%, the extent of dilatancy decreases, resulting in a smaller peak friction angle compared to clean sand specimens. However, when fines content increases further to 25%, both the maximum dilatancy angle and peak friction angle show an increase. A similar trend is observed for the friction angle at the phase transition state (PTS). In the p ′ − q plane, the critical state line (CSL) remains constant despite changes in fines content, whereas in the e − p ′ 0 . 7 plane, the CSL shifts with variations in fines content. A unified CSL in the e − p ′ 0 . 7 plane can be obtained by applying the concept of equivalent skeleton void ratio. Additionally, the state dependence of the material is analyzed using both the modified state parameter and the state index. It was observed that the friction angles at both the PTS and the peak state (PS) are influenced by the state of the material, with the PTS friction angle showing a stronger correlation with the state index, while the PS friction angle is more closely linked to the state parameter.

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

In-situ nitrogen fixation during sludge pyrolysis integrated with biomass gasification process - Aishu Li; Hengda Han; Liping Du; Zhijie Gong; Song Hu; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Jun Xiang (Journal of Environmental Management, 2025)

Interfacial electron transfer promoted greigite Fenton oxidation of benzene by tungsten disulfide: Enhanced regeneration of dissolved and surface-bounded ferrous iron via W/S-mediated electron donor-shuttle mechanism - Cong Liang; Lei Yang; Jing Li; Lu Han; Yudong Feng; Mengfang Chen; Hangyu Li; Zhen Ni; Zhenyu Kang; Hongtao Sheng; Linbo Qian (Journal of Environmental Chemical Engineering, 2025)

Explosion suppressing effects of Mg(OH)2/NH4H2PO4 compound powders on the methane explosion and its microscopic mechanism about capturing intermediate products - Qiuhong Wang; Leilei Zhu; Jun Deng; Qingfeng Wang; Jing Han; Dong Zhao; Youjie Sheng; Ting Pan; Jianxiong Liu (Fuel, 2025)

Pickering emulsion stabilized by egg derived reconstituted lipid nanoparticles for encapsulation and oral delivery of curcumin - Dan Han; Lihua Ji; Mingzhou Lu; Dingran Li; Xiangling Sheng; Jiaxing Zhang; Cheng Wang (Food Chemistry, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Bottom-Up approach to synthesize polycarbonate-type polyurethanes from CO2 for high-performance cathode binder in Li-ion batteries - Tingting Zhao; Shangru Yang; Shuanjin Wang; Dongmei Han; Sheng Huang; Hui Guo; Min Xiao; Yuezhong Meng (Chemical Engineering Journal, 2025)

Regulating pH distribution of soda saline-alkali soil during electrochemical treatment by conditioning catholyte pH coupled with approaching anodes - Yinyin Zhang; Jiangtao Han; Changhui Luan; Yuyan Zhao; Sheng Xu; Qiaoqiao Wei; Libin Zang (Environmental Geochemistry and Health, 2025)

A Global Synthesis of How Plants Respond to Climate Warming From Traits to Fitness - Pengyan Jia; Rong Zhang; Bernhard Schmid; Han Wang; Jin‐Sheng He; Jiaxi Liu; Sijie Liu; Sipeng Jian; Yanhao Feng (Ecology Letters, 2025)
Despite intensive research, our understanding of how plants respond to warming by coordinating their full arsenal of traits to adjust fitness is lacking. To fill this gap, we applied a trait‐based framework with three clusters (two functional clusters: “carbon‐fixation rate” and “carbon‐fixation area”; a third cluster: “total carbon fixation”) to a global dataset compiled from 572 studies of warming experiments with 677 species and a comprehensive list of traits and fitness components. The pairwise correlation analysis complemented with SEM and PCA showed that plants increased biomass (the core variable in the third cluster) under warming by coordinating satellite traits in two functional clusters to adjust their core traits, net photosynthesis rate and total leaf area, respectively. In particular, the trait coordination was characterised by the maintenance of net photosynthesis rate and the increase of total leaf area, which was robust across ecological contexts although warming responses of the variables per se displayed context‐dependences. Moreover, the trade‐offs between biomass and reproduction (itself bearing mass vs. number trade‐offs) in their warming responses scaled the coordination to enhance fitness except in the contexts where reproduction was reduced. These findings could help explain and predict plant form and function in a warming world.

17α-methyltestosterone exposure disrupted growth, liver physiology and intestinal microbial on fish: A case study on migratory bony fishes (Takifugu fasciatus) - Yuxi Liu; Sijin Wang; Mengbo Han; Sheng Luo; Peng Chu; Xiaodong Tang; Cheng Zhao; Shiqun Han; Shaowu Yin; Tao Wang (Marine Pollution Bulletin, 2025)

Evolution of Dynamic Characteristics of Solidified Dredge Sludge during Long-Term Traffic Loading under Environmental Actions - Xie-qun Wang; Wei Kai; Xiang-wei Yu; Zhong Han; Sheng Zhu; Wei-lie Zou (Transportation Geotechnics, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

A receptance method for assigning frequencies using multiple connecting springs - Shi Yingsha; Li Han; Guo Yanqi; Li Sheng (Ocean Engineering, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

MnxCo3-xO4 spinel activates peroxymonosulfate for highly effective bisphenol A degradation with ultralow catalyst and persulfate usage - Lu-Lu Zhou; Hengyue Xu; Yi-Han Sheng; Wei-Kang Wang; Juan Xu (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

In situ construction of cobalt phthalocyanine covalent organic polymer on mesoporous graphitic carbon nitride for boosting photocatalytic CO2 reduction - Jiaxin Rong; Qiang Xu; Jingwei Han; Ke Ren; Jing Zhang; Xue Zhao; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

Synthesis of furan-based cationic biopolyamides and their removal abilities for perfluoroalkyl and polyfluoroalkyl substances - Hong-Hui Shu; Liu-Qi Shi; Hui-Qin Zhang; Yun Liu; Sheng-Li Han; Jing-Yi Rao; Cheng-Mei Liu (Chemical Engineering Journal, 2025)

Vagus nerve stimulation (VNS) preventing postoperative cognitive dysfunction (POCD): two potential mechanisms in cognitive function - Zi-Feng Xie; Sheng-Yu Wang; Yuan Gao; Yi-Dan Zhang; Ya-Nan Han; Jin Huang; Mei-Na Gao; Chun-Guang Wang (Molecular and Cellular Biochemistry, 2025)

Differential induction of JA/SA determines plant defense against successive leaf-chewing and phloem-feeding insects - Yu-Xiao Liu; Wen-Hao Han; Jun-Xia Wang; Feng-Bin Zhang; Shun-Xia Ji; Yu-Wei Zhong; Shu-Sheng Liu; Xiao-Wei Wang (Journal of Pest Science, 2025)

Mechanical properties and energy dissipation characteristics of oil-saturated sandstone under triaxial compression: an experimental investigation - Sheng Zhang; Rui Zhou; Xulong Zhang; Xiaoliang Wang; Guiwu Han (Bulletin of Engineering Geology and the Environment, 2025)

Unraveling carbon mineralization patterns and mechanisms in conservation agriculture: A global synthesis and multi-point experiment - Cong He; Jin-Sai Chen; Shou-Wei Han; Wen-Sheng Liu; Wen-Xuan Liu; Olatunde Pelumi Oladele; Yash Pal Dang; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Journal of Cleaner Production, 2025)

Correlation between foam performance and molecular structure of fully biodegradable PPC-P enhanced by chain extension - Change Wu; Tianwei Zhang; Min Xiao; Dongmei Han; Sheng Huang; Shuanjin Wang; Yuezhong Meng (Journal of Environmental Chemical Engineering, 2025)

Identification and pharmacological characterization of pH-sensitive chloride channels in the fall armyworm, Spodoptera frugiperda - Wei Wang; Jia-Sheng Chen; Pei-Yun He; Mo-Han Zhang; Hai-Qun Cao; Subba Reddy Palli; Cheng-Wang Sheng (Insect Biochemistry and Molecular Biology, 2025)

Combined high voltage atmospheric cold plasma and ultraviolet-cold plasma inhibited Aspergillus flavus growth and improved physicochemical properties of protein in peanuts - Luling Zhao; Jiarong Zheng; Wenjing Yan; Jing Qian; Jianhao Zhang; Jin Wang; Xiaowei Sheng; Vijaya Raghavan; Xiaohan Yang; Yuxuan Han; Taotao Cao; Yating Chen (Food Chemistry, 2025)

Carbon emissions assessment of ultra-high performance concrete in construction industry: Calculation method and case study - Sheng Li; Ge Han; Boshi Du; Zhisheng Jiang; Linqi Sun (Energy and Buildings, 2025)

Canadian record-breaking wildfires in 2023 and their impact on US air quality - Han Chen; Weihang Zhang; Lifang Sheng (Atmospheric Environment, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Pilot-scale experimental study on the enhanced natural attenuation of complex organic contaminants based on the recharge of electron acceptors - Shuxuan Wu; Yu Yang; Xu Han; Sheng Deng; Jiayu Kang; Beidou Xi; Yonghai Jiang (Water Research, 2025)

Driving force shapes the biocake characteristics in membrane-based bioreactors - Jing-Xiao Zhang; Yu-Sheng Li; Wen-Jie Du; Tian Tian; Liang Xuan; Han-Qing Yu (Water Research, 2025)

Iron oxides promote physicochemical stabilization of carbon despite enhancing microbial activity in the rice rhizosphere - Han Sun; Xiaomin Ma; Lukas Van Zwieten; Yu Luo; Robert W. Brown; Georg Guggenberger; Sheng Tang; Yakov Kuzyakov; Peduruhewa H. Jeewani (Science of The Total Environment, 2025)

Effects of turbulence intensity and integral length scale on wind-induced vibrations of a three-dimensional aeroelastic square cylinder - Xu-Liang Han; Qiu-Sheng Li (Engineering Structures, 2025)

Characterization of droplet freezing on superhydrophobic surfaces with different microstructures - Xu Han; Dan Zhang; Haikun Zheng; Wei Sheng; Xiaoru Hao; Xiaozhuan Chen; Chaobin Dang; Mengjie Song (Energy and Buildings, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Synergistically networked 1D/2D/3D phase change composites with Ultra-Fast contactless thermal energy conversion and enhanced electromagnetic interference shielding performance - Xinpeng Hu; Bin Ai; Bingqing Quan; Zhanjin Shi; Zhigang Liu; Mengjie Sheng; Yang Ding; Han Yan; Yang Xiao; Gangchen Lu; Shuang Liu; Hao Wu; et al. (Chemical Engineering Journal, 2025)

Paper-like foldable shape memory wood actuator with consecutive gesture programming by water and thermal dual stimuli for soft robots - Linze Jin; Xu Han; Junxiu Piao; Yuhui Meng; Xiaoran Yang; Lifu Zhang; Zitian Zhang; Chengming Jiang; Sheng Bi (Chemical Engineering Journal, 2025)

PET/CT-guided and OPN-targeted melanin nanoparticle platform for early diagnosis and precision therapy of idiopathic pulmonary fibrosis (IPF) - Jie Ji; Jie Sheng; Pengjun Zhang; Feng Wang; Yutong Xu; Xingyue Feng; Rui Xu; Yi Shen; Longjiang Zhang; Xiaodong Han (Chemical Engineering Journal, 2025)

A comprehensive optimization of highly efficient MA-Free wide-bandgap perovskites for 4-T Perovskite/Silicon tandem solar cells - Yu-Ching Huang; Sheng-Wen Huang; Chia-Feng Li; Shih-Han Huang; Feng-Yu Tsai; Wei-Fang Su (Chemical Engineering Journal, 2025)

Polypeptide-PNP2 in Corn Cervi Pantotrichum Ameliorates Cognitive Impairment in Alzheimer’s Disease Mice by Inhibiting Microglial Cell Activation - Hongyan Pei; Zhongmie He; Rui Du; Yi Yang; Shasha Wu; Wenyan Li; Jian Sheng; Chenyang Han (Molecular Neurobiology, 2025)

Long-term intake of sulforaphene alleviates d-galactose-induced skin senescence by activating AMPK-Sirt 1 pathway - Bo Zhang; Pengtao Liu; Huakang Sheng; Yongzhi Han; Qipeng Yuan (Molecular and Cellular Biochemistry, 2025)

Multi objective motion planning of fruit harvesting manipulator based on improved BIT* algorithm - Peifeng Ma; Aibin Zhu; Yihao Chen; Yao Tu; Han Mao; Jiyuan Song; Xin Wang; Sheng Su; Dangchao Li; Xia Dong (Computers and Electronics in Agriculture, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Modeling ground vibration excited by a high-speed train running along a viaduct railway using a new structure-soil interaction method - Yuanpeng He; Xiaozhen Sheng; Jian Han; Yang Zhang; Xinbiao Xiao (Science of The Total Environment, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

RETRACTED: Bivariate validation of the Gaidai natural hazard evaluation method for climate dynamics - Chaoshuai Han; Oleg Gaidai; Mahmoud El-Wazery; Shicheng He; Alia Ashraf; Jinlu Sheng; Yan Zhu (Ocean Engineering, 2024)

Multivariate Gaidai reliability methodology for marine riser dynamics in the Red Sea with memory effects included - Chaoshuai Han; Oleg Gaidai; Yan Zhu; Alia Ashraf; Peijiang Qin; Jinlu Sheng (Ocean Engineering, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Black rice phenolics alleviate T2DM through comprehensive regulation of oxidative stress, metabolic pathways and gut microbiota - Shuyan Xu; Xianbao Li; Natalia S. Podio; Yuna Han; Xiao-Yin Wang; Er Sheng Gong (Food Bioscience, 2024)

Fe-MOF derived Fe3O4/C-based hydrogel for efficient solar-driven photothermal evaporation - You Zhou; Lei Xu; Sheng-Jie Han; Cai-Hua Liu; Yi-Bin Li; Ming-Lai Fu; Baoling Yuan (Desalination, 2024)

MST1R Gene Variants Predispose Individuals to Tetralogy of Fallot - Zhiyu Feng; Xianghui Huang; Yuan Gao; Han Gao; Weilan Na; Chaozhong Tan; Shaojie Min; Yuquan Lu; Quannan Zhuang; Siyi Lin; Xiaojing Ma; Weicheng Chen; et al. (Phenomics, 2024)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart malformation. While a few susceptibility genes for TOF have been identified, research on the genetic basis of TOF is limited. The Macrophage stimulating 1 receptor ( MST1R ) gene encodes the macrophage-stimulating protein receptor with tyrosine phosphatase activity that is involved in immune defense. In this study, we performed whole-exome sequencing (WES) on 10 TOF families and 50 sporadic TOF patients and identified a recessive homozygous missense mutation in MST1R , c.T2009G: p.V670G, in two offspring with TOF in a single family. Targeted sequencing of the MST1R gene showed enrichment for rare variants in 417 TOF patients compared with East Asians in Genome Aggregation Database Version 2 (gnomADv2_EAS). MST1R -deficient human induced pluripotent stem cells (hiPSCs) maintained normal pluripotency but differentiated into non-functional cardiomyocytes (CMs). Taken together, our findings indicate that MST1R may play a critical role in cardiac differentiation and genetic variations in MST1R may be associated with the pathogenesis of TOF.

Strength Evolution Characteristics of Coal with Different Pore Structures and Mineral Inclusions Based on CT Scanning Reconstruction - Cun Zhang; Sheng Jia; Zhaopeng Ren; Qingsheng Bai; Lei Wang; Penghua Han (Natural Resources Research, 2024)

Circular RNA and its potential diagnostic and therapeutic values in breast cancer - Di Gao; Can Cui; Yaoxuan Jiao; Han Zhang; Min Li; Junjie Wang; Xiumei Sheng (Molecular Biology Reports, 2024)

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Comparative analyses of immune gene profiles and antioxidant capabilities in the midgut and liver of three species of grass carps (Ctenopharyngodon idella) following gut infection with Aeromonas hydrophila - Wei-Sheng Luo; Zi-Han Xu; Qin-Yang He; Jie Peng; Fei Wang; Jian Li; Sheng-Wei Luo (Aquaculture International, 2024)

Radar forward modeling and intelligent identification of shallow subgrade defects - Li Xin; Chen Han-qing; Liu Chen-yang; Su Dong; Chen Xiang-sheng; He Bo-hu; Shen Xiang (Transportation Geotechnics, 2024)

A framework for achieving urban sustainable development goals (SDGs): Evaluation and interaction - Kun Jia; Qianyu Sheng; Yihui Liu; Yanzhao Yang; Guanglong Dong; Zhi Qiao; Meng Wang; Chuhao Sun; Dongrui Han (Sustainable Cities and Society, 2024)

Decomposing high uncertainty in greenhouse gas mitigation pathways in emerging regions: An approach to evaluate risks toward carbon neutrality - Hui Han; Xinxin Ye; Yahui Bian; Shuifa Lin; Yu-Sheng Shen; Zhi Huang; Jianyi Lin (Science of The Total Environment, 2024)

Effect of climate warming on subsurface temperature in basins with topography-driven groundwater flow - Yi-Peng Zhang; Xiao-Wei Jiang; Shemin Ge; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Lizhi Wang; Qing Liu; Li Wan (Journal of Hydrology, 2024)

In-situ growth of NH2-MIL(FeCo) organic framework with bimetallic active centers over TiO2 photoanode toward superior solar water oxidation - Yanjie Pan; Jiantao Hu; Dongmei Qin; Sheng Han; Zhenbiao Dong; Hualin Lin (Fuel, 2024)

Prediction of BTEX volatilization in polluted soil based on the sorption potential energy theory - Yongxiang Han; Yaqi Sheng; Jiating Zhao; Lizhong Zhu (Environmental Pollution, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

In situ reconstruction of multi-phase heterostructured anodes for efficient and durable solid oxide fuel cells - Tian Gan; Bin Sheng; Quanyu Zeng; Yuchen Li; Yujun Han; Wenya Zhen; Ping Li; Yongdan Li (Chemical Engineering Journal, 2024)

Boosting electrochemical performance by regulating rigid-flexible microphase separation of multiblock copolymers - Gang Su; Zexian Zhang; Min Xiao; Shuanjin Wang; Sheng Huang; Hui Guo; Dongmei Han; Yuezhong Meng (Chemical Engineering Journal, 2024)

Improving the removal rate of bisphenol A and Cu2+ from water using P/N coexisting β-cyclodextrin-based adsorbents by enhancing adsorbents-pollutants interactions - Xiuqin Fang; Chang Wang; Hong-Hui Shu; Sheng-Li Han; Cheng-Mei Liu (Carbohydrate Polymers, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Study on biological zero and effective accumulated temperature of embryonic development and gonadal development of cuttlefish Sepia pharaonis - Huan Zeng; Wencheng Xiao; Xiamin Jiang; Qingxi Han; Ruibing Peng; Sheng Li; Maowang Jiang (Molluscan Research, 2024)

Discovering transformation products of pharmaceuticals in domestic wastewaters and receiving rivers by using non-target screening and machine learning approaches - Yu Han; Li-Xin Hu; Ting Liu; Liang-Li Dong; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2024)

Robust resiliency-oriented planning of electricity-hydrogen island energy systems under contingency uncertainty - Yulong Gu; Zhinong Wei; Yizhou Zhou; Sheng Chen; Haiteng Han; Guoqiang Sun; Haixiang Zang (Journal of Cleaner Production, 2024)

Minimizing energy footprint of seawater desalination system via wind power generation in coastal areas - Pei Guo; Zihan Liu; Sheng Huang; Siyuan Liu; Mengyao Han (Journal of Environmental Management, 2024)

Recent advances and perspective of modified TiO2-based photoanodes toward photoelectrochemical water splitting - Zhenbiao Dong; Meng Chen; Dongmei Qin; Sheng Han (Fuel, 2024)

Characterization of phospholipidome in milk, yogurt and cream, and phospholipid differences related to various dairy processing methods - Yue-Han Liu; Ting-Ting Liu; Jing-Qi Niu; Xue-Song Zhang; Wei-Sheng Xu; Shuang Song; Zhu Wang (Food Chemistry, 2024)

Plastic debris mediates bacterial community coalescence by breaking dispersal limitation in the sediments of a large river - Sheng Liu; Zixuan Zhang; Jie Hao; Chuanfu Zhao; Fei Han; Qingrong Xiong; Xun Wang; Chenggong Du; Hongzhe Xu (Environmental Pollution, 2024)

Dual-Functional group passivation to foster buried interface Cohesion for High-Performance perovskite photovoltaics - Namatullah Nizamani; Kai-Li Wang; Run-Jun Jin; Chun-Hao Chen; Jing Chen; Yu Xia; Lei Huang; Yu-Han Li; Mary Donnabelle Balela; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2024)

A low-cost salt-tolerant solar evaporator prepared from graphite in spent LIBs for high efficiency seawater desalination - Sheng-Jie Han; Lei Xu; Zhen-Yu Wang; Cai-Hua Liu; Ming-Lai Fu; Baoling Yuan (Chemical Engineering Journal, 2024)

Effects of 6-methoxybenzoxazolinone (6-MBOA) on animals: state of knowledge and open questions - Jia-Yi Shi; Ke-Han Gu; Sheng-Mei Yang; Wan-Hong Wei; Xin Dai (The Science of Nature, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Rapid tear screening of diabetic retinopathy by a detachable surface acoustic wave enabled immunosensor - Dhrubajyoti Das; Hsuan-An Chen; Chao-Li Weng; Yung-Chun Lee; Sheng-Min Hsu; Jae-Sung Kwon; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Enzyme- and label-free cascade isothermal amplification aptasensor for the ultrasensitive detection of ochratoxin A - Ming Li; Yu Xiao; Zexuan Wang; Enze Sheng; Rujin Zhao; Chenfei Han; Daolin Du (Analytica Chimica Acta, 2024)

Robust control algorithm designed for robotic legs of lunar-based equipment: Modeling and experiment - Zheng-Han Chen; Zhao-Dong Xu; Rui-Heng Wang; Hong-Fang Lu; Deng-Yun Yu; Jian-Zhong Yang; Xue-Liang Zhao; Zhong-Wei Hu; Sheng-Chao Zhen (Advances in Space Research, 2024)

Purkinje Cell Dendritic Swellings: A Postmortem Study of Essential Tremor and Other Cerebellar Degenerative Disorders - Elan D. Louis; Sheng-Han Kuo; Phyllis L. Faust (The Cerebellum, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Evidence of hybridization of cattle and aurochs on the Tibetan Plateau ∼3750 years ago - Shungang Chen; Lele Ren; Yu Gao; Guanghui Dong; Guilian Sheng; Jianlin Han; Xinyi Liu; Ningbo Chen; Fahu Chen (Science Bulletin, 2024)

Molluscicidal activity and biochemical impacts of borrelidins against an aquatic invasive snail Pomacea canaliculata for crop protection - Jingyan Wang; Zhihang Shi; Zihuan Wu; Han Wang; Huan Qi; Qiang Sheng; Shaoyong Zhang; Junhuan Song; Jidong Wang; Liqin Zhang; Chihang Cheng (Pesticide Biochemistry and Physiology, 2024)

Non-target discovery and risk prediction of per- and polyfluoroalkyl substances (PFAS) and transformation products in wastewater treatment systems - Ting Liu; Li-Xin Hu; Yu Han; Sheng Xiao; Liang-Li Dong; Yuan-Yuan Yang; You-Sheng Liu; Jian-Liang Zhao; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

Long-term non-flooded cultivation with straw return maintains rice yield by increasing soil pH and soil quality in acidic soil - Jingjie Zhou; Sheng Tang; Wankun Pan; Xiu Liu; Kefeng Han; Linlin Si; Qingxu Ma; Xiali Mao; Haoran Fu; Lianghuan Wu (European Journal of Agronomy, 2024)

Modulating charge distribution of MIL@CuFe-Se by in-situ interface engineering for high performance supercapacitors - Ziyun Zhang; Lei Li; Xiaomin Chen; Wentao Ding; Sheng Han; Jibo Jiang (Chemical Engineering Journal, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Actn2 defects accelerates H9c2 hypertrophy via ERK phosphorylation under chronic stress - Kang Wang; Ye Wang; Hua Wan; Jie Wang; Li Hu; Shuainan Huang; Mingchen Sheng; Jiayi Wu; Xing Han; Youjia Yu; Peng Chen; Feng Chen (Genes & Genomics, 2024)

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Study on scale effect and particle crushing characteristics of continuously graded coarse-grained soil - Huayang Ye; Sheng Zhu; Jiangyang Pan; Chunxin Zhong; Chaojun Han; Yun Jia (European Journal of Environmental and Civil Engineering, 2024)

Prenylated dihydroflavones from the root barks of Morus alba - Jun-Yu Zhu; Han-Zhuang Weng; Di-Kai Tang; Jin-Chen Long; Zhuo-Ya Tang; Ye Chen; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

Unlocking the potential of surface modification with phosphate on ball milled zero-valent iron reactivity:Implications for radioactive metal ions removal - Sheng Deng; Yu Yang; Xu Han; Qiyuan Liu; Mingxiao Li; Jing Su; Yonghai Jiang; Beidou Xi; YuHui Liu (Water Research, 2024)

Quantitative assessment of the impact factors upon remediation performance of the PRB technique in conjunction with pumping/recharge - Han Xiao; Yu Yang; Xiangjian Xu; Sheng Deng; Xu Han; Fu Xia; Yonghai Jiang (Groundwater for Sustainable Development, 2024)

Unveiling the CoFe LDH generated by partial in situ conversion strategy: Synergistic effect of modified MXene and cationic vacancies for overall water splitting - Chang Xi; Wentao Ding; Jibo Jiang; Yucheng Wang; Shilong Wang; Ziyun Zhang; Sheng Han (Fuel, 2024)

Insights into heavy components evolution in the condensed volatiles from amino acids pyrolysis - Hengda Han; Aishu Li; Song Hu; Grzegorz Lisak; Donglin Wang; Xu Kai; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2024)

Anion substitution-induced CuCoSe hollow nanotubes as multifunctional electrode materials for supercapacitors and overall water splitting - Zifeng Zeng; Zhifeng Gao; Zicheng Guo; Xiaowei Xu; Ying Li; Lin Lin; Runping Jia; Sheng Han (Fuel, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Insight into effect of polyethylene microplastic on nitrogen removal in moving bed biofilm reactor: Focusing on microbial community and species interactions - Tong Wu; Jie Ding; Sheng Wang; Ji-Wei Pang; Han-Jun Sun; Le Zhong; Nan-Qi Ren; Shan-Shan Yang (Science of The Total Environment, 2024)

Nonlinear responses of biofilm bacteria to alkyl-chain length of parabens by DFT calculation - Sheng Liu; Zixuan Zhang; Chuanfu Zhao; Mengru Zhang; Fei Han; Jie Hao; Xun Wang; Xiaorong Shan; Weizhi Zhou (Journal of Hazardous Materials, 2024)

Molecular mechanism for the unusual enhancement of the second-step chemiluminescence production from the carcinogenic tetrabromohydroquinone and H2O2 - Zi-Han Wang; Chun-Hua Huang; Zhi-Sheng Liu; Li Mao; Ben-Zhan Zhu (Journal of Environmental Sciences, 2024)

Quick measurement method of three components in lignocellulosic biomass based on kinetic mechanism analysis of PT-TGA - Gongxiang Song; Dexin Huang; Aishu Li; Ruochen Li; Song Hu; Kai Xu; Qiangqiang Ren; Hengda Han; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2024)

STAT3 phosphorylation at Tyr705 affects DRP1 (dynamin-related protein 1) controlled-mitochondrial fission during the development of apoptotic-resistance in pulmonary arterial endothelial cells - Han Zhang; Li Chen; Jiachen Li; Jiashu Sun; Qixu Zhao; Sheng Wang; Gang Li (Genes & Genomics, 2024)
Background The apoptosis-resistant pulmonary arterial endothelial cells (PAECs) are known to be major players in the pulmonary remodeling of pulmonary arterial hypertension (PAH) and exhibit an abnormal metabolic profile with mitochondrial dysfunction. Mitochondrial fission has been shown to regulate the apoptosis of several cell types, but this is largely unexplored in the PAECs. Objective The roles of mitochondrial fission control by Dynamin related protein-1 (DRP1) in the development of PAECs apoptosis suppression were investigated in present study and the potential mechanisms behind this were furtherly explored. Methods The mitochondrial morphology was investigated in PAECs from PAH rats with the pulmonary plexiform lesions, and the relations of it with DRP1 expression and apoptosis were furtherly identified in apoptosis-resistant PAECs induced by hypoxia. PAECs were isolated from rats with severe PAH and from normal subjects, the apoptotic-resistant PAECs were induced by hypoxia. DRP1 gene knockdown was achieved via DRP1-siRNA, DRP1 and STAT3 phosphorylation were blocked using its inhibitors, respectively. Apoptosis was analyzed by flow cytometry, and mitochondrial morphology was investigated by transmission electron microscope and confocal microscopy. Results The PAECs isolated from PAH rats with the pulmonary plexiform-like lesions and displayed lower apoptotic rate with increased DRP1 expression and mitochondrial fragmentation. In addition, similar observations were achieved in apoptosis-resistant PAECs induced by hypoxia. Targeting DRP1 using siRNA and pharmacologic blockade prevented the mitochondrial fission and subsequent apoptotic resistance in PAECs under hypoxia. Mechanistically, STAT3 phosphorylation at Tyr705 was shown to be activated in both PAH and hypoxia-treated PAECs, leading to the regulation of DRP1 expression. Of importance, targeting STAT3Tyr705 phosphorylation prevented DRP1 disruption on apoptosis in PAECs under hypoxia. Conclusions These data indicated that STAT3 phosphorylation at Tyr705 impacted DRP1-controlled mitochondrial fission during the development of apoptosis-resistance in PAECs, suggesting mitochondrial dynamics may represent a therapeutic target for PAH.

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Sustainable campus dining: Evaluating food waste practices and awareness at Hainan Tropical Ocean University - Bahareh Asefi; Moughni Said Maenrouf; François Nkinahamira; Chin Yao Xian; Sheng Jie Han; Peizheng Wang (Sustainable Chemistry and Pharmacy, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Targeting the undruggables—the power of protein degraders - Chao Zhang; Yongbo Liu; Guangchen Li; Zhouli Yang; Chi Han; Xiuyun Sun; Chunquan Sheng; Ke Ding; Yu Rao (Science Bulletin, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Occurrence and prevalence of per- and polyfluoroalkyl substances in the sediment pore water of mariculture sites: Novel findings of PFASs from the Bohai and Yellow Seas using a newly established analytical method - Nan Shen; Jiale Tang; Junhui Chen; Cancan Sheng; Tongzhu Han; Xiuping He; Chenguang Liu; Chao Han; Xianguo Li (Journal of Hazardous Materials, 2024)

Co-migration behavior of toluene coupled with trichloroethylene and the response of the pristine groundwater ecosystems – A mesoscale indoor experiment - Shuxuan Wu; Yu Yang; Zhifei Ma; Fan Feng; Xiangjian Xu; Sheng Deng; Xu Han; Beidou Xi; Yonghai Jiang (Journal of Hazardous Materials, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Utilizing waste corn straw to photodegrade methyl orange and methylene blue: Photothermal effect of biochar enhances photodegradation efficiency - Peng Jiang; Li Zhou; Yongfen Han; Wei Fu; Sheng Su; Maoqin Zeng (Journal of Environmental Chemical Engineering, 2024)

Dextral shear initiation of the Kangguer Shear Zone in the East Tianshan: Constraints from a “porphyroclast” system - Bo Liu; Zhengle Chen; Mengmeng Qu; Feng Yuan; Awei Mabi; Mingqiang Sheng; Jing Liu; Fengbin Han; Wengao Zhang; Hailong Huo (Journal of Asian Earth Sciences, 2024)

The unique Z-scheme g-C3N4/Ti3C2/Sn-Bi-MOF photocatalyst for enhancing CO2 reduction activity - Ziheng Song; Shushan Song; Weijie Zhang; Huarui Han; Kai Wei; Dandan Liu; Qianyu Wang; Changchang Ma; Sheng Feng (Fuel, 2024)

WO3·nH2O-based photocatalysts: Structural analysis, rational design, and applications in energy conversion and environmental remediation - Fangyuan Zhang; Weiguang Han; Jinyuan Cai; Boxiong Shen; Sheng-Qi Guo (Fuel, 2024)

Identification of the causes of aroma differences in white tea under different withering methods by targeted metabolomics - Huiting Wu; Caiyan Sheng; Mingxia Lu; Han Ke; Tiehan Li; Yuming Wei; Shanshan Shen; Xuchao Yin; Chengye Lu; Yujie Wang; Jingming Ning (Food Bioscience, 2024)

Preparation, characterization, and stability of nano-emulsions loaded with the Moringa oleifera seed hypoglycemic peptide MoHpP-2 - Xuefeng Wang; Yiyan Li; Mengying Han; Xiaoyu Gao; Jun Sheng; Yang Tian (Food Hydrocolloids, 2024)

Modulations of ocean-atmosphere interactions on squid abundance over Southwest Atlantic - Chia-Ying Ko; Yu-Chi Lee; Yi-Chi Wang; Huang-Hsiung Hsu; Chun Hoe Chow; Ruei-Gu Chen; Tsung-Han Liu; Chih-Shin Chen; Tai-Sheng Chiu; Don-Hsieh Chiang; Ren-Fen Wu; Wan-Ling Tseng (Environmental Research, 2024)

Optimization of Schottky barrier height and LSPR effect by dual defect induced work function changes for efficient solar-driven hydrogen production - Xiu-Qing Qiao; Chen Li; Wenxuan Chen; Hui Guo; Dongfang Hou; Bojing Sun; Qingwen Han; Chenghua Sun; Dong-Sheng Li (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Molecular epidemiological and clinical infection characteristics analysis of Ralstonia - Zhaojun Sheng; Jiaxin Li; Guojing Han; Ru Fan; Pingjun Zhu; Xiangqun Fang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose This study was to clarify the molecular epidemiology and clinical infection characteristics of Ralstonia pickettii and establish sequence typing system. Methods 48 nonrepetitive Ralstonia pickettii strains were collected from January 2008 to December 2013 at the Chinese People’s Liberation Army General Hospital (PLAGH) and were identified through a specific PCR experiment, 16 S rDNA experiment and VITEK 2 system to compare the identification accuracy. The sequence types of the strains were analyzed by multilocus sequence typing (MLST) method. The antibiotic sensitivity of these strains was determined with disc diffusion tests and broth microdilution method. The clinical data of Ralstonia pickettii infected patients were collected. Results All of the 48 strains were identified as Ralstonia pickettii by VITEK 2 system. 30 and 34 strains were identified as Ralstonia pickettii by PCR and 16 S rDNA experiment respectively. ST9 was the most sequence types (STs) in these 18 STs of 42 strains. 42 strains were divided into 2 groups (A and B) and 18 genotypes. Ralstonia pickettii was sensitive to some cephalosporins, β-lactam/β-lactamase inhibitor, levofloxacin and trimethoprim/sulfamethoxazole. Cough, sputum, shortness of breath and pulmonary rales were the common clinical symptoms of most Ralstonia pickettii infected patients. Conclusion We established a sequence typing system with a relatively fine resolution and the PCR assay is a faster and more sensitive method for clinical identification of Ralstonia pickettii . ST9 is the most common sequence types of Ralstonia pickettii . The most common clinical characteristics of Ralstonia pickettii infected patients were cough, sputum, shortness of breath and pulmonary rales.

Consensus Paper: Cerebellum and Reward - Mario Manto; Michael Adamaszek; Richard Apps; Erik Carlson; Julian Guarque-Chabrera; Elien Heleven; Shinji Kakei; Kamran Khodakhah; Sheng-Han Kuo; Chi-Ying R. Lin; Mati Joshua; Marta Miquel; et al. (The Cerebellum, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Content Validity of the Modified Functional Scale for the Assessment and Rating of Ataxia (f-SARA) Instrument in Spinocerebellar Ataxia - Michele Potashman; Katja Rudell; Ivanna Pavisic; Naomi Suminski; Rinchen Doma; Maggie Heinrich; Linda Abetz-Webb; Melissa Wolfe Beiner; Sheng-Han Kuo; Liana S. Rosenthal; Theresa Zesiwicz; Terry D. Fife; et al. (The Cerebellum, 2024)
The functional Scale for the Assessment and Rating of Ataxia (f-SARA) assesses Gait, Stance, Sitting, and Speech. It was developed as a potentially clinically meaningful measure of spinocerebellar ataxia (SCA) progression for clinical trial use. Here, we evaluated content validity of the f-SARA. Qualitative interviews were conducted among individuals with SCA1 ( n = 1) and SCA3 ( n = 6) and healthcare professionals (HCPs) with SCA expertise (USA, n = 5; Europe, n = 3). Interviews evaluated symptoms and signs of SCA and relevance of f-SARA concepts for SCA. HCP cognitive debriefing was conducted. Interviews were recorded, transcribed, coded, and analyzed by ATLAS.TI software. Individuals with SCA1 and 3 reported 85 symptoms, signs, and impacts of SCA. All indicated difficulties with walking, stance, balance, speech, fatigue, emotions, and work. All individuals with SCA1 and 3 considered Gait, Stance, and Speech relevant f-SARA concepts; 3 considered Sitting relevant (42.9%). All HCPs considered Gait and Speech relevant; 5 (62.5%) indicated Stance was relevant. Sitting was considered a late-stage disease indicator. Most HCPs suggested inclusion of appendicular items would enhance clinical relevance. Cognitive debriefing supported clarity and comprehension of f-SARA. Maintaining current abilities on f-SARA items for 1 year was considered meaningful for most individuals with SCA1 and 3. All HCPs considered meaningful changes as stability in f-SARA score over 1–2 years, 1–2-point change in total f-SARA score, and deviation from natural history. These results support content validity of f-SARA for assessing SCA disease progression in clinical trials.

Significant differences in usage of antibiotics in three Chinese cities measured by wastewater-based epidemiology - Xiaozhe Luo; Sheng Han; Yue Wang; Peng Du; Xiqing Li; Phong K. Thai (Water Research, 2024)

Lightweight, ultra-broadband SiOC-based triply periodic minimal surface meta-structures for electromagnetic absorption - Junbin Lu; Mingming Sheng; Hongyu Gong; Jie Jing; Xiaobin Zhou; Jianqiang Bi; Weibin Zhang; Guifang Han; Zidong Zhang; Haoyu Fang; Yijie Zhou; Ke Bi (Chemical Engineering Journal, 2024)

Enhanced near-infrared absorption of Cs0.32WO3 nanoparticles for efficient interfacial solar steam generation - Bo Yang; Hui Quan; Haoran Pei; Wenjing Wang; Min Zhang; Qiangchun Liu; Weiguang Han; Fangyuan Zhang; Xueqin Zuo; Guang Li; Sheng-Qi Guo (Chemical Engineering Journal, 2024)

Confined grotthuss proton-conduction along polyoxometalate chains inside carbon nanotubes for high-rate charge storage - Sheng Zhu; Xiaoxin Yang; Lan Li; Xiao Wang; Gaoyi Han (Chemical Engineering Journal, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Liver Injury Induced by Exposure to Polystyrene Microplastics Alone or in Combination with Cadmium in Mice Is Mediated by Oxidative Stress and Apoptosis - Shuai Sheng; Ningxin Han; Yufeng Wei; Jinghan Wang; Wei Han; Boyu Xing; Mingwei Xing; Wen Zhang (Biological Trace Element Research, 2024)

A New Dy(III) Complex: Fluorescence Performances, Loading with Resveratrol-Hydrogels Against Skin Aging and Molecular Docking - Yu-Sheng Peng; Kai Han; Jin-Xue Zhao; Wei-Cheng Song; Si-Qi Dai (Journal of Fluorescence, 2024)

Four new compounds from the fruits of Chinese dwarf cherry ( Prunus humilis Bunge) - Sheng Dong; Ying Zhou; Ji-Chao Wang; Yi-Lin Zhuo; Yi-Han Sun; Jun-Gang Wang; Guo-Gang Zhang (Natural Product Research, 2024)

Microbial contribution estimated by clumped isotopologues (13CH3D and 12CH2D2) characteristics in a CO2 enhanced coal bed methane reservoir - Xinchu Wang; Biying Chen; Guannan Dong; Naizhong Zhang; Weiyi Liu; Jiaxu Han; Cong-Qiang Liu; Si-Liang Li; John M. Eiler; Sheng Xu (Science of The Total Environment, 2024)

Gamma-ray irradiation as an effective method for mitigating antibiotic resistant bacteria and antibiotic resistance genes in aquatic environments - Ming-Qi Zhang; Xiao-Yong Zhang; Han-Chao Zhang; Hai-Bin Qiu; Zheng-Hao Li; Dong-Hua Xie; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2024)

The genesis of the Tianbaoshan PbZn deposit in Sichuan, SW China: Insights from sphalerite and fluid inclusion compositions - Lian-Qing Zhao; Pei Ni; Wen-Sheng Li; Stefano Albanese; Kai-Han Zhang; Guo-Guang Wang; Jun-Yi Pan (Journal of Geochemical Exploration, 2024)

Analytical evaluation of stress–strain behavior of rubberized concrete incorporating waste tire crumb rubber - Xiaoyan Han; Shanshan Zhou; Aijiu Chen; Lingyun Feng; Yanting Ji; Zhihao Wang; Sheng Sun; Keliang Li; Xiaozhou Xia; Qing Zhang (Journal of Cleaner Production, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

A theoretical investigation on the transformer oil pyrolysis mechanism and the effect of the small molecule acid in oils - Huijuan Wang; Wei Xia; Huimin Yu; Hua Chen; Yongli Pan; Yingxin Sun; Shengtao Li; Sheng Han (Fuel, 2024)

Janus biopolymer nanocomposite coating with excellent antibacterial and water/oxygen barrier performance for fruit preservation - Liubo Yuan; Ruiqi Liu; Yifan Zhou; Rongya Zhang; Sheng Chen; Qin Yang; Yingchun Gu; Linbo Han; Bin Yan (Food Hydrocolloids, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Designing hollow mesoporous carbon sphere for high-rate supercapacitor in water-in-salt electrolyte - Liping Feng; Huichao Liu; Wenyan Zan; Sidian Li; Yunzhen Chang; Ying Zhang; Wenjing Hou; Yun Zhao; Sheng Zhu; Gaoyi Han (Chemical Engineering Journal, 2024)

Unveiling the activation mechanism: The role of nitrogen-doped biochar in enhancing Fe(VI) catalysis - Sheng Deng; Xu Han; Ningqing Lv; Xiaochun Yang; Qiyuan Liu; Yonghai Jiang; Yu Yang; Beidou Xi (Chemical Engineering Journal, 2024)

Novel Aliphatic polycarbonate binders for Solvent‑free manufacturing High‑loading cathodes of high-performance lithium-ion batteries - Guan Xi; Zhe Zhang; Lei Zhong; Shuanjin Wang; Min Xiao; Dongmei Han; Sheng Huang; Yuezhong Meng (Chemical Engineering Journal, 2024)

Improving impact of heparan sulfate on the endothelial glycocalyx abnormalities in atherosclerosis as revealed by glycan-protein interactome - Qingqing Chen; Xiaohui Xu; Shaoshuai Xie; Anran Sheng; Naihan Han; Zhenyu Tian; Xiaowei Wang; Fuchuan Li; Robert J. Linhardt; Fuming Zhang; Lan Jin; Qunye Zhang; et al. (Carbohydrate Polymers, 2024)

Engineering RuBisCO-based shunt for improved cadaverine production in Escherichia coli - Jia Feng; Ye Han; Shuang Xu; Yang Liao; Yongtao Wang; Sheng Xu; Hui Li; Xin Wang; Kequan Chen (Bioresource Technology, 2024)

Chemical constituents of Wikstroemia alternifolia and their neuroprotective activities - Qing-Ren Lu; Yan Wang; Zhuo-Ya Tang; Ye Chen; Han-Zhuang Weng; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

Nutrients recovery by coupled bioreactor of heterotrophic ammonia assimilation and microbial fuel cell in saline wastewater - Chuanfu Zhao; Tong Jiao; Wenhao Zhang; Wenchao Zhang; Man Jia; Sheng Liu; Mengru Zhang; Fei Han; Yufei Han; Jianhua Lei; Xianfeng Wang; Weizhi Zhou (Science of The Total Environment, 2024)

Impact of COVID-19 emission reduction on dust aerosols and marine chlorophyll-a concentration - Yundan Li; Wencai Wang; Yongqing Han; Wenjing Liu; Ronghao Wang; Ruonan Zhang; Zhixin Zhao; Lifang Sheng; Yang Zhou (Science of The Total Environment, 2024)

Mixed plantations do not necessarily provide higher ecosystem multifunctionality than monoculture plantations - Xu Li; Yue Liu; Guopeng Wu; Zhiyang Lie; Han Sheng; Luis Carlos Ramos Aguila; Muhammmad Sadiq Khan; Xujun Liu; Shuyidan Zhou; Ting Wu; Wenfang Xu; Juxiu Liu (Science of The Total Environment, 2024)

New particle tracking method for 2D steady-state groundwater flow around wells: A modified algorithm using the stream function - Shuai Zhang; Xu-Sheng Wang; Peng-Fei Han; Xiao-Wei Jiang (Journal of Hydrology, 2024)

Controls of groundwater-dependent vegetation coverage in the yellow river basin, china: Insights from interpretable machine learning - Taiya Bai; Xu-Sheng Wang; Peng-Fei Han (Journal of Hydrology, 2024)

Insight into the differential toxicity of PFOA and PFBA based on a 3D-cultured MDA-MB-231 cell model - Huan Wang; Hongchang Zhang; Shuangqing Hu; Ting Xu; Yiheng Yang; Miao Cao; Sheng Wei; Yiqun Song; Jing Han; Daqiang Yin (Journal of Hazardous Materials, 2024)

Trustworthy remote sensing interpretation: Concepts, technologies, and applications - Sheng Wang; Wei Han; Xiaohui Huang; Xiaohan Zhang; Lizhe Wang; Jun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Unusual weakening trend of the East Asian winter monsoon during MIS 8 revealed by Chinese loess deposits and its implications for ice age dynamics - Qingzhen Hao; Shuzhen Peng; Xinbo Gao; Slobodan B. Marković; Sheng-Hua Li; Junjie Zhang; Fengjiang Li; Long Han; Yu Fu; Xuechao Wu; Luo Wang; Bing Xu; et al. (Global and Planetary Change, 2024)

Bio-adhesive barrier with active ROS-scavenging ability for simultaneous management of dura tear and epidural inflammatory fibrosis - Meng Han; Jincheng Tang; Haiyue Zhao; Yachao Sheng; Ziang Li; Wenxiao Shi; Jiahao Wang; Chao Ma; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2024)

Accelerating the generation of NiOOH by in-situ surface phosphating nickel sulfide for promoting the proton-coupled electron transfer kinetics of urea electrolysis - Xin Guo; Longyu Qiu; Menggang Li; Fenyang Tian; Xue Ren; Sheng Jie; Shuo Geng; Guanghui Han; Yarong Huang; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

CCL2 Knockdown Attenuates Inflammatory Response After Spinal Cord Injury Through the PI3K/Akt Signaling Pathway: Bioinformatics Analysis and Experimental Validation - Sheng Fang; Hao Tang; Hai-long Li; Ti-Chao Han; Zi-Jie Li; Zong-Sheng Yin; Jian-Jun Chu (Molecular Neurobiology, 2024)

Hessian Regularized $$L_{2,1}$$-Nonnegative Matrix Factorization and Deep Learning for miRNA–Disease Associations Prediction - Guo-Sheng Han; Qi Gao; Ling-Zhi Peng; Jing Tang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Sinoflavonoids NJ and NK, anti-inflammatory prenylated flavonoids from the fruits of Podophyllum hexandrum Royle - Junyang Wang; Han Li; Yanhui Li; Aiping Yang; Sheng Bao; Yuntian Zhang; Qing Du; Zongping Zheng; Xiachang Wang (Natural Product Research, 2024)

Microbiota-mediated metabolic perturbations in the gut and brain of mice after microplastic exposure - Sheng-Han Lee; Wan-Yu Lin; Tsun-Jen Cheng (Chemosphere, 2024)

Metabolic perturbations and bacterial communities dysbiosis associated with skin ulcer disease progression in Sepia pharaonis - Liting Xu; Maowang Jiang; Ruibing Peng; Xiamin Jiang; Sheng Li; Weiwei Zhang; Qingxi Han (Aquaculture, 2024)

Excitation force on a pump-jet propeller: The clocking effect of pre-swirl stator - Yu Zhang; Jieting Han; Sheng Ji; Rui Wu; Bin Huang; Dahai Zhang; Dazhuan Wu (Ocean Engineering, 2024)

Three-dimensional inter-basin groundwater flow toward a groundwater-fed stream: Identification, partition, and quantification - Peng-Fei Han; Xu-Sheng Wang; Yangxiao Zhou; Zhi Yang; Li Wan; Jinsong Chen; Xiao-Wei Jiang (Journal of Hydrology, 2024)

Hierarchical electronic coupling engineering of bimetallic sulfide driven by CoFe bimetal MOFs anchored on MXene promotes efficient overall water splitting - Mingjing Li; Shaobo Zhou; Ran Sun; Sheng Han; Jibo Jiang (Fuel, 2024)

Influence of inertinite on coal physicochemical thermal transformation properties and liquefaction behaviors - Wenchao Qian; Chunyang Yan; Xiaoyin Mu; Jiahao Chen; Lulu Cui; Hualin Lin; Sheng Han; Zongqing Bai (Fuel, 2024)

Heterogeneous interface engineering of cationic vacancy defects layered double hydroxides and molybdenum-nickel-based selenium compounds to facilitate overall water splitting - Shaobo Zhou; Xiaomin Chen; Tingting Li; Ying Wei; Ran Sun; Sheng Han; Jibo Jiang (Fuel, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

Multiple Pathways for the Enhancement of Wheat Growth by Chlorella vulgaris - Sheng-Nan Wang; Shu-Han Ge; Lin-Lan Zhuang; Jian Zhang (Journal of Plant Growth Regulation, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Fabrication and performance of novel multifunctional sodium alginate/polyvinylpyrrolidone hydrogels - Deli Lu; Chen Liu; Fengtian Zhu; Ying Liu; Yushi Lin; Qidong Yang; Sheng Han (Chemosphere, 2024)

Weed control performance of different sowing modes in organic wheat production - Zhiwei Zhao; Li Han; Mengyuan Li; Yangyang Sheng; Min Xie; Qiang Wu; Yongping Zhang (Crop Protection, 2024)

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

Sludge pyrolysis integrated biomass gasification to promote syngas: Comparison of different biomass - Aishu Li; Hengda Han; Kaiyue Zheng; Meng Zhu; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Science of The Total Environment, 2024)

Ensifer sp. GMS14 enhances soybean salt tolerance for potential application in saline soil reclamation - Youqiang Wang; Yanzhe Yang; Donglin Zhao; Zhe Li; Xiaona Sui; Han Zhang; Jin Liu; Yiqiang Li; Cheng-Sheng Zhang; Yanfen Zheng (Journal of Environmental Management, 2024)

Effects of comb-like poly-α-olefins on the cold flow properties of diesel fuel - Honggang Wang; Xiaokang Zhang; Xiuwei Lei; Li Chen; Songyue Wang; Hualin Lin; Sheng Han (Fuel, 2024)

Preparation of high-performance asymmetric supercapacitors based on NiCo2S4 nanospheres and CuO-MOF nanosheets on carbon fibers - Baopeng Liu; Jun Zhang; Jiawei Xu; Yanjie Pan; Yanshan Huang; Sheng Han; Yuanting Li (Fuel, 2024)

NaGdF4-based magnetic resonance nanoprobes for qualitative inflammation imaging in glioma: Hot or cold? - Jing Wang; Haiyan Guo; Han Wang; Zhenwei Yao; Xiuru Ji; Yaru Sheng; Yuwen Zhang; He Wang; Xiangming Fang; Yu Luo; Dalong Ni (Chemical Engineering Journal, 2024)

Novel oxygen vacancy-rich Bi2MoO6-SOVs/MgFe2O4 S-scheme heterojunction piezo-photocatalytic for efficient degradation of norfloxacin and theoretical calculations - Hainan Wei; Fanming Meng; Han Zhang; Wenqing Yu; Jialong Li; Sheng Yao (Chemical Engineering Journal, 2024)

Cyclophosphamide reduces gene transcriptional activity and embryo in vitro development by inhibiting NF-κB expression through decreasing AcH4K12 - Zhao-Bo Luo; Liu-Hui Yang; Sheng-Zhong Han; Shuang-Yan Chang; Hongye Liu; Zhi-Yong An; Xiu-Li Zhang; Biao-Hu Quan; Xi-Jun Yin; Jin-Dan Kang (Chemico-Biological Interactions, 2024)

The Role of the Cerebellum in Learning to Predict Reward: Evidence from Cerebellar Ataxia - Jonathan Nicholas; Christian Amlang; Chi-Ying R. Lin; Leila Montaser-Kouhsari; Natasha Desai; Ming-Kai Pan; Sheng-Han Kuo; Daphna Shohamy (The Cerebellum, 2023)

Migration and transformation of trace elements during sewage sludge and coal slime Co-combustion - Hengda Han; Kuan Du; Xiaoxue An; Yajie Song; Zheng Zhao; Jun Xu; Long Jiang; Guang Wang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Chemosphere, 2023)

Demethylation of ethanol organosolv lignin by Na2SO3 for enhancing antioxidant performance - Ying Han; Zihao Ma; Xing Wang; Yuanyuan Sheng; Yu Liu (Sustainable Chemistry and Pharmacy, 2023)

Regional proximity effects of landscape pattern evolution: Evidence from 325 county-level areas in the middle reaches of the Yangtze River, China - Han Wang; Danni Zhang; Songyue Liu; Sheng Ye; Xueru Jin; Jiansheng Wu (Science of The Total Environment, 2023)

Limits on scalar-induced gravitational waves from the stochastic background by pulsar timing array observations - Yi-Fu Cai; Xin-Chen He; Xiao-Han Ma; Sheng-Feng Yan; Guan-Wen Yuan (Science Bulletin, 2023)

Influence of extractable organic components on shale wettability: Dongyuemiao member of Jurassic Ziliujing formation in the Fuxing area, Eastern Sichuan Basin - Weihang Zhang; Rui Yang; Zhiliang He; Hanyong Bao; Hui Yu; Shuling Xiong; Yuanjia Han; Qinhong Hu; Sheng He (Marine and Petroleum Geology, 2023)

Protective effects of camellia oil and gac oil against corticosterone-induced neurotoxicity in Neuro-2a cells - Jo-Han Chiu; Sheng-Yi Chen; I-Chen Chiang; Gow-Chin Yen (Food Bioscience, 2023)

Highly stable multi-responsive yellow-emissive fluoride RbCdF3:Mn2+,Yb3+ for advanced optical anti-counterfeiting - Chuanyu Zeng; Xinxin Han; Enhai Song; Dongxi Liu; Chao Liu; Juan Wang; Sheng Cao; Ruosheng Zeng; Jialong Zhao; Bingsuo Zou (Chemical Engineering Journal, 2023)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

New insights into muscularis macrophages in the gut: from their origin to therapeutic targeting - Li Zhou; Hui Lian; Yue Yin; Yuan-sheng Zheng; Yu-xin Han; Gao-qi Liu; Zhi-yong Wang (Immunologic Research, 2023)

The expression characteristics and allelic variation of AnVromindoline-1/3 in Avena nuda L. - Jiang-hong An; Jin-sheng Nan; Hui-yan Liu; Ming-na Chai; Bing Han; Yan Yang (Euphytica, 2023)
Oat is a worldwide cultivated crop with nutritional, ecological and economic value. The hardness of oat is closely related to the damage to the grain during harvesting, washing, threshing and hulling, and has an important impact on the processing quality and eating quality of oats. Vromindolines are a group of proteins specific to the Avena genus and are responsible for the softness of oat endosperm. Avena nuda is an allohexaploid, and is an important grain and feed crop in China. Vromindolines have been studied in the genus Oat, but have not been reported in Avena nuda . In this study, we performed paraffin sectioning and scanning electron microscopy analysis on oat kernels with different hardness, and the sequence characteristics, allelic variation, expression patterns and subcellular localization of Vromindoline-1 and Vromindoline-3 genes in Avena nuda were also analyzed. The results showed that the cell structure and ultrastructure of soft oat variety grains are significantly different from those of hard oats variety. PCR amplification and sequence analysis showed that the lengths of AnVin-1 and AnVin-3 genes were 444 and 429 bp, respectively, and AnVin-1 existed in the oat A, C and D genomes. Expression analysis in different tissues showed that AnVin-1A , AnVin-1C , AnVin-1D and AnVin-3C were expressed to varying degree in roots, stems and leaves. Expression analysis at the panicle developmental stage showed that the expression levels of these four genes first increased and then decreased, with the highest expression levels at 14 days after pollination. In addition, the expression levels of AnVin-1C and AnVin-3C in soft oat variety were higher than those in hard oats at 14 DAP. Among the single nucleotide polymorphisms among 18 AnVin-1C and 9 AnVin-3C gene sequences, AnVin-1C6 and AnVin-3C2 genes had three haplotypes in a oat natural population. Based on the allelic variation sites of AnVin-1C6 , a cleavage amplified polymorphic sequence marker was established, which explained 1.44% of the variation in hardness. The above results of this study indicated that AnVin-1 and AnVin-3 genes were involved in kernel development and might affect kernel firmness.

Quantitative Estimation on Methane Storage Capacity of Organic-Rich Shales from the Lower Silurian Longmaxi Formation in the Eastern Sichuan Basin, China - Xiaowen Guo; Tao Luo; Tian Dong; Rui Yang; Yuanjia Han; Jizheng Yi; Sheng He; Zhiguo Shu; Hanyong Bao (Journal of Earth Science, 2023)

Long-term application of controlled-release fertilizer enhances rice production and soil quality under non-flooded plastic film mulching cultivation conditions - Jingjie Zhou; Sheng Tang; Wankun Pan; Meng Xu; Xiu Liu; Liang Ni; Xiali Mao; Tao Sun; Haoran Fu; Kefeng Han; Qingxu Ma; Lianghuan Wu (Agriculture, Ecosystems & Environment, 2023)

A study on the application of ATEM in hydrogeological investigation - Miao-xin Yang; Sheng-qing Xiong; Sheng-jun Liang; Han-dong Tan (Applied Geophysics, 2023)

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Erratum to: Comparison of growth and nutrient uptake capacities of three domsinant species of Qinhuangdao green tides - Hongbin Han; Ruobing Wen; Hui Wang; Sheng Zhao (Acta Oceanologica Sinica, 2023)

Occurrence and phase distribution of lipophilic marine algal toxins in the bottom boundary layer and sediment-porewater system of two mariculture sites - Cancan Sheng; Xiuping He; Nan Shen; Tongzhu Han; Junhui Chen; Chenguang Liu; Xianguo Li (Chemosphere, 2023)

Re-evaluation and modification of dehydrogenase activity tests in assessing microbial activity for wastewater treatment plant operation - Yuan Pan; Sheng-Song Yu; Zhi-Chao Xiao; Yuan Min; Tian Tian; Yu-Ming Zheng; Quan-Bao Zhao; Zhi-Hua Yuan; Han-Qing Yu (Water Research, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Interaction between regular waves and floating breakwater with protruding plates: Laboratory experiments and SPH simulations - Xinyu Han; Sheng Dong (Ocean Engineering, 2023)

Study on potential antigenicity and functional properties of whey protein treated by high hydrostatic pressure based on structural analysis - Xin-Xin Yu; Xiao-Hui Wang; Sheng-Ao Zhang; Ying-Hua Zhang; Han-Lin Zhang; Yu-Qi Yin (Food Research International, 2023)

Design of rich defects carbon coated MnFe2O4/LaMnO3/LaFeO3 heterostructure nanocomposites for broadband electromagnetic wave absorption - Xinyang Liu; Lin He; Guanghui Han; Jie Sheng; Yongsheng Yu; Weiwei Yang (Chemical Engineering Journal, 2023)

Effect and mechanism of a concentration-dependent inorganic ion biomimetic periosteum in a repairing bone defect - Lichen Zhang; Jincheng Tang; Meng Han; Yang Sun; Wei Wang; Zhuojun Wu; Yachao Sheng; Kun Xi; Yong Gu; Liang Chen (Chemical Engineering Journal, 2023)

Rapid In-Situ Stress Measurement in Vertical Borehole Based on Borehole Diametrical Deformation Analysis - Chao Wang; Zengqiang Han; Yiteng Wang; Chuanying Wang; Jinchao Wang; Sheng Hu (Rock Mechanics and Rock Engineering, 2023)

Enhanced degradation of tetracycline hydrochloride with in situ prepared ferrate supernatant based on calcium hypochlorite: Compare with purified and commercial ferrate - Xiaochun Yang; Yu Yang; Xu Han; Yonghai Jiang; Beidou Xi; Han Xiao; Xiangjian Xu; Yuhan Hu; Sheng Deng; Jiao Zhang (Journal of Environmental Chemical Engineering, 2023)

Potentialities of Ganoderma lucidum extracts as functional ingredients in food formulation - Mohammed Sharif Swallah; Precious Bondzie-Quaye; Han Wang; Chang-Sheng Shao; Pei Hua; Mona Alrasheed Bashir; Joseph Benjamin Holman; Frederick Leo Sossah; Qing Huang (Food Research International, 2023)

Synergistic single-atom Ru and MOF-derived oxygen vacancy ZrO2-porous carbon to boost the efficiency for electrochemical nitrogen fixation - Zhiya Han; Senhe Huang; Boxu Feng; Jingshun Zhang; Sheng Han; Xiaodong Zhuang; Rongbin Li (Chemical Engineering Journal, 2023)

Fenton/Fenton-like microreactor in inflammatory microenvironment: Photothermal enhanced catalytic oxidation strategy for chemodynamic treatment of rheumatoid arthritis - Xiunan Wu; Guojun Cao; Han Chen; Weiwei Sheng; Shanrong Lv; Zheng Li; Zetai Bai; Zhiyuan Hua; Zhili Qiu; Minghao Chao; Kaijin Guo; Xin Zheng; et al. (Chemical Engineering Journal, 2023)

Evaluation of Agricultural Non-point Source Pollution: a Review - Mei Luo; Xiaoxiao Liu; Nebiyou Legesse; Ying Liu; Sheng Wu; Fengxiang X. Han; Youhua Ma (Water, Air, & Soil Pollution, 2023)

Arsenic pollution, geochemical fractions, and leaching characteristics in soil samples from four contaminated sites in the Beijiang River Basin, South China - Yu-Zhong Liu; Jun-Feng Wang; Han-Yun Fan; Tao He; Dao-Yuan Wang; Huan-Zhan Zhou; Qu-Sheng Li (Environmental Science and Pollution Research, 2023)

Molecular characterization, spatiotemporal expression patterns of fatty acid elongase (elovl8) gene, and its transcription changes in response to different diet stimuli in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Xiu-Ying Wei; Wei Qin; Chuan-Jie Qin; Qiong Shi; Sheng-Tao Guo; Panita Prathomya; Shi-Yong Zhang; Peng Fu; Wei Hu; Han-Wen Yuan; Zheng-Yong Wen (Frontiers in Marine Science, 2023)
Elongase of very long-chain fatty acid 8 (Elovl8) is a new member identified in the Elovl family that is involved in the synthesis of highly unsaturated fatty acids (HUFAs). However, the evolutionary and physiological roles of this enzyme are still largely unknown. In the present study, the elovl8 gene was identified and characterized from yellow catfish Pelteobagrus fulvidraco , and then its evolutionary and molecular characteristics as well as transcriptional changes in response to various nutritional status were determined. Results showed that the open reading frame (ORF) of elovl8 was 795 bp in length, encoding a protein of 264 amino acids. Multiple sequences alignment showed that the yellow catfish Elovl8 was highly conserved with other homologs in teleosts, sharing similar structural characteristics (including six conserved transmembrane α-helical domains, four conserved elongase motifs, and three highly conserved cysteine residues). Meanwhile, comparisons of genetic synteny confirmed that the elovl8 gene identified from the yellow catfish was the homolog of elovl8b in other teleosts, and thus, the elovl8a gene was lost in the genome of the yellow catfish. Gene structure analysis revealed that the elovl8b gene contained eight exons and seven introns, which was highly conserved in teleosts, implying the functional conservation among various fish species. Tissue distribution analysis detected by real-time quantitative PCR (RT-qPCR) showed that the elovl8 gene was extensively expressed in all detected tissues except eyes, with high expression levels in the intestine and liver. Temporal expression analysis revealed that the expression level of elovl8 was stably expressed in the early 12 h after fertilization, and then dramatically decreased at 24, 48, 72, and 96 h after fertilization, implying that elovl8 is required for HUFA biosynthesis in the early development stages. Functional experiments showed that the expression of the elovl8 gene was stimulated after feeding with egg yolk but was not obviously affected after feeding with halogenated worms, indicating that diets full of HUFAs can inhibit the expression of elovl8 in yellow catfish. Our findings will help us to better understand the evolutionary and functional characteristics of elovl8 in teleosts, and lay a solid basis for investigating the regulation mechanism of HUFA biosynthesis.

Natural phosphorus-ferromanganese ore-based composites for the simultaneous remediation of arsenic- and lead-co-contaminated groundwater: synergistic effectiveness, kinetics, and mechanisms - Hongli Lu; Xiangjian Xu; Yu Yang; Han Xiao; Fu Xia; Xu Han; Sheng Deng; Shuxuan Wu; Xingang Wang; Yonghai Jiang; Qinghua Yan (Environmental Science and Pollution Research, 2023)

Characteristics of persulfate gel materials in groundwater remediation: Column and tank experiments investigations - Yu Yang; Xiangjian Xu; Fu Xia; Shuoyang Wan; Xu Han; Han Xiao; Sheng Deng; Yonghai Jiang; Xiang Li (Science of The Total Environment, 2023)

Telomere length, oxidative stress and their links with growth and survival in a lizard facing climate warming - Qiong Zhang; Xing-Zhi Han; Pablo Burraco; Xin Hao; Li-Wei Teng; Zhen-Sheng Liu; Fu-Shun Zhang; Wei-Guo Du (Science of The Total Environment, 2023)

Elevated O2 alleviated anaerobic metabolism in postharvest winter jujube fruit by regulating pyruvic acid and energy metabolism - Dong Li; Li Li; Wenxuan Li; Yanqun Xu; Xueyuan Han; Nina Bao; Zhanwu Sheng; Yaya Yuan; Xingtao Zhang; Zisheng Luo (Postharvest Biology and Technology, 2023)

Identification of Brassica rapa BrEBF1 homologs and their characterization in cold signaling - Wangze Wu; Haobo Yang; Juan Shen; Peng Xing; Xueyan Han; Yun Dong; Guofan Wu; Sheng Zheng; Kun Gao; Ning Yang; Lina Zhang; Yujun Wu (Journal of Plant Physiology, 2023)

Pollution Prevention- Recovery of Copper Resource from Desalination Brine through LIX 984N/Kerosene System - Cheng-Han Lee; Wei-Sheng Chen; Jun-Yi Wu (Water, Air, & Soil Pollution, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Long non-coding RNA in coronary artery disease: the role of PDXDC1-AS1 and SFI1-AS1 - Shu He; Sheng Zhang; Yan-Jun Wang; Xiong-Kang Gan; Jia-Xin Chen; Han-Xiao Zhou; En-Zhi Jia (Functional & Integrative Genomics, 2023)

Weight–Length Relationship and Condition Factor of Gibel Carp (Carassius auratus gibelio var. CAS V) at Different Growth Stages and Feed Formulations - Han Zhang; Shouqi Xie; Sheng Wang (Fishes, 2023)
Accurate recording of growth indicators for aquaculture species at different stages is essential for evaluating aquaculture production effectiveness and the rationality of feed formulations. Due to their convenience and non-invasiveness, weight, length, and condition factor are commonly used to assess the growth of aquaculture species. However, fish growth indicators, can vary significantly with age structure and feed components (nutrition), and relying on a single indicator may lead to misjudgments. In this study, we investigated the growth indicators of Gibel carp (Carassius auratus gibelio var. CAS V) at different growth stages (juvenile and adult) and different feed formulations. Meanwhile, the fish weight–length relationship (W=bLa) was used to assess the growth indicators. The results showed that the weight–length relationship of Gibel carp varied significantly with age and feed formulation. Additionally, the condition factor calculated depended on the weight–length relationship being more similar with weight and length change trend than the condition factor was measured. Weight analysis indicated that weight, length, depth, body width, and carcass ratio had higher weights when analyzing fish growth. Therefore, during aquaculture production, fish growth evaluating requires considering diverse indicators such as weight, length, body depth, body width, and carcass ratio, as well as the condition factor, to avoid misjudging the actual growth situation. Meanwhile, the use of the condition factor should consider the sufficient number of data and whether the assumptions (such as being in an isometric growth period) are met.

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Satellite-derived sediment distribution mapping using ICESat-2 and SuperDove - Xiaohan Zhang; Lizhe Wang; Jun Li; Wei Han; Runyu Fan; Sheng Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

A survey of machine learning and deep learning in remote sensing of geological environment: Challenges, advances, and opportunities - Wei Han; Xiaohan Zhang; Yi Wang; Lizhe Wang; Xiaohui Huang; Jun Li; Sheng Wang; Weitao Chen; Xianju Li; Ruyi Feng; Runyu Fan; Xinyu Zhang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Effect of flow number of pilot-stage centrifugal atomizer on idle performance of internally staged combustor - Jie Zhang; Minghong Jiang; Xinggui Wang; Sheng Huang; Huaizhi Han; Zerong Li (Fuel, 2023)

Formation mechanism of Pickering emulsion gels stabilized by proanthocyanidin particles: Experimental and molecular dynamics studies - Sheng Geng; Fenxia Han; Xiaofan Lv; Sheng Zhang; Hanjun Ma; Benguo Liu (Food Chemistry, 2023)

PEO-based solid-state electrolyte modified by cationic covalent organic frameworks enabling high-performance all-solid-state Li metal and graphite anode batteries - Jing Chen; Sheng Han (Chemical Engineering Journal, 2023)

Performance, community structure, metabolic pathway, and mechanism in a three-dimensional electrocatalytic biofilter (3DEBF) for the degradation of multiple concentrations of clofibric acid (CA) - Qingling Huang; Yan Feng; Wenwen Han; Juanting Wang; Huihui Sheng; Zhijie Zhang; YanZhen Yu (Bioresource Technology, 2023)

Response of rice yield to organic amendments was regulated by soil chemical properties, microbial functional genes and bacterial community rather than fungal community - Tao Sun; Xiali Mao; Qingxu Ma; Kefeng Han; Xiangjie Wang; Qi Cheng; Xiongchao Sheng; Wenhai Mi; Lianghuan Wu (Applied Soil Ecology, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Excessive disinfection aggravated the environmental prevalence of antimicrobial resistance during COVID-19 pandemic - Zhichao Hu; Lihua Yang; Zishu Liu; Jian Han; Yuxiang Zhao; Yihao Jin; Yaqi Sheng; Lizhong Zhu; Baolan Hu (Science of The Total Environment, 2023)

Interaction between medium-long period waves and smoothed mound breakwater with crown wall based on experiments and multi-phase simulations - Xinyu Han; Sheng Dong (Ocean Engineering, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Short-term effects of asymmetric day and night warming on soil N2O, CO2 and CH4 emissions: A field experiment with an invasive and native plant - Xue Han; Na-Na Yao; Xiao-Jing Wang; Hao-Hui Deng; Hui-Xuan Liao; Sheng-Qi Fan; Bao-Ming Chen (Applied Soil Ecology, 2023)

Efficient utilization of biogenic manganese oxides in bioaugmentation columns for remediation of thallium(I) contaminated groundwater - Liangjing Zhang; Yu Yang; Xiangjian Xu; Sheng Deng; Han Xiao; Xu Han; Fu Xia; Yonghai Jiang (Journal of Hazardous Materials, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Integrating the flow regime and water quality effects into a niche-based metacommunity dynamics model for river ecosystems - Yibo Wang; Pan Liu; Dimitri Solomatine; Liping Li; Chen Wu; Dongyang Han; Xiaojing Zhang; Zhikai Yang; Sheng Yang (Journal of Environmental Management, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Endophytic fungus Trichoderma atroviride D16 increases tanshinone accumulation in Salvia miltiorrhiza plantlets by enhancing abscisic acid and salicylic acid signaling - Xing-Guang Xie; Ke-Xin Sheng; Wei-Lan Lu; Hao-Ran Wang; Khalid Rahman; Kun-Miao Feng; Ting Han (Symbiosis, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Combining mechanisms of black carbon and magnetic minerals in power plant fly ash - Meng Yao Li; Zhou Xin Peng; You Ying Chen; Shi Yun Xiao; Bo Wen Zhang; Yi Xin Shen; Sheng Kang Wang; Xue Song Wang; Zhao Xiang Han (Science of The Total Environment, 2023)

Semi-analytical solution of single-well push–pull test under transient flow conditions - Heejun Suk; Weon Shik Han; Jui-Sheng Chen; Minjune Yang (Journal of Hydrology, 2023)

Impacts of drought and heat events on vegetative growth in a typical humid zone of the middle and lower reaches of the Yangtze River, China - Huiming Han; Hongfu Jian; Mingchao Liu; Sheng Lei; Siyang Yao; Feng Yan (Journal of Hydrology, 2023)

Clinical Heterogeneity of Essential Tremor: Understanding Neural Substrates of Action Tremor Subtypes - Alexander Fanning; Sheng-Han Kuo (The Cerebellum, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

Single-cell transcriptomic analysis reveals the developmental trajectory and transcriptional regulatory networks of pigment glands in Gossypium bickii - Yue Sun; Yifei Han; Kuang Sheng; Ping Yang; Yuefen Cao; Huazu Li; Qian-Hao Zhu; Jinhong Chen; Shuijin Zhu; Tianlun Zhao (Molecular Plant, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

The structural model of coal is studied by quantum chemistry calculation and separation of coal liquefied oil group components - Xiaoyin Mu; Wenchao Qian; Chunyang Yan; Hualin Lin; Sheng Han (Fuel, 2023)

LiMYB108 is involved in floral monoterpene biosynthesis induced by light intensity in Lilium ‘Siberia’ - Yang Yun-Yao; Zhang Xi; Han Ming-Zheng; Hu Zeng-Hui; Wu Jing; Ma Nan; Leng Ping-Sheng; Zhou Xiao-Feng (Plant Cell Reports, 2023)

Mineral carbonation using alkaline waste and byproducts to reduce CO2 emissions in Taiwan - Hsing-Jung Ho; Atsushi Iizuka; Cheng-Han Lee; Wei-Sheng Chen (Environmental Chemistry Letters, 2023)

The Overwintering Capability of Ulva prolifera Spores and Gametes in the Yellow Sea, China - Hongbin Han; Sheng Zhao; Xiaoli Song; Hui Wang (Journal of Ocean University of China, 2023)

Comparison of growth and nutrient uptake capacities of three dominant species of Qinhuangdao green tides - Hongbin Han; Ruobing Wen; Hui Wang; Sheng Zhao (Acta Oceanologica Sinica, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

A novel thermosensitive persulfate controlled-release hydrogel based on agarose/silica composite for sustained nitrobenzene degradation from groundwater - Shuxuan Wu; Sheng Deng; Fu Xia; Xu Han; Tianyu Ju; Han Xiao; Xiangjian Xu; Yu Yang; Yonghai Jiang; Beidou Xi (Journal of Hazardous Materials, 2023)

Thermomechanically micronized sugar beet pulp: Emulsification performance and the contribution of soluble elements and insoluble fibrous particles - Jiawei Lin; Zhong-Sheng Tang; Charles S. Brennan; Jayani Chandrapala; Wenhong Gao; Zhong Han; Xin-An Zeng (Food Research International, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

Experimental Investigation on Optimization of Highly Porous Materials in Saline Soil Remediation - Ke-Sheng Li; Yu-Han Geng; Chuan-Xiao Liu (Journal of Soil Science and Plant Nutrition, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Genotoxicity of organic contaminants in the soil: A review based on bibliometric analysis and methodological progress - Miao Han; Zaifeng Zhang; Si Liu; Youying Sheng; Michael Gatheru Waigi; Xiaojie Hu; Chao Qin; Wanting Ling (Chemosphere, 2023)

Experiment and evaluation model of liner design for renewal of deteriorated reinforced concrete pipes utilizing cured-in-place-pipe technology - Zhao Yahong; Huang Sheng; Ma Baosong; Zeng Cong; Yan Xuefeng; Ti Zhongsen; Liu Han; Deng Caiying (Tunnelling and Underground Space Technology, 2023)

Two new monoterpenoids from the stems of Ephedra sinica - Chen He; Yan-gang Cao; Meng-nan Zeng; Yu-han Zhang; Ying-jie Ren; Yan-ling Liu; Xu Chen; Xi-ling Fan; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry Letters, 2023)

Predicting the hydraulic conductivity of frozen coarse-grained soils - Jidong Teng; Antai Dong; Han Yan; Chenxi Tong; Sheng Zhang (Journal of Hydrology, 2023)

Study on the dynamic process of premixed hydrogen-air deflagration flame propagating in a closed space with obstacles - Zhonghua Sheng; Guogang Yang; Wei Gao; Shian Li; Qiuwan Shen; Han Sun (Fuel, 2023)

A study on the release characteristics and formation mechanism of SO2 during co-combustion of sewage sludge and coal slime - Xin Wang; Jun Xu; Peng Ling; Xiaoxue An; Hengda Han; Yifeng Chen; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2023)

Elucidation of the cellulose nanocrystal-sugar beet pectin interactions for emulsification enhancement - Jiawei Lin; Zhong-Sheng Tang; Jayani Chandrapala; Charles Stephen Brennan; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Wave Force on the Crown Wall of Rubble Mound Breakwaters at Intermediate Depths - Xinyu Han; Sheng Dong (Journal of Ocean University of China, 2023)

Hydrostatic pressure shock induced diploid/tetraploid mosaic in mandarin fish (Siniperca chuatsi), with the observation of embryo development and change in body spots - Zhilun Zhang; Huadong Yi; Yuqin Su; Chenlei Huang; Xuchong Wei; Qiuxian Chen; Jiahui Chen; Haiyang Li; Sheng Bi; Han Lai; Xuange Liu; Shuang Liu; et al. (Aquaculture, 2023)

Dexamethasone affects the chemotaxis and phagocytic activity of neutrophils for boar spermatozoa and the quality of liquid preserved boar semen in vitro - Jing-Chun Li; Shuo Wang; He-Chuan Wang; Qun Zhang; Qian Wang; Ming-Hui Guo; Han Zhang; Tian-Feng Li; Qing Guo; Yan-Bing Li; Guo-Sheng Wei (Theriogenology, 2023)

Interaction between medium-long period waves and smoothed mound breakwater: Physical model tests and SPH simulations - Xinyu Han; Sheng Dong (Ocean Engineering, 2023)

Bifunctional additive phenolic acids grafted ethylene-vinyl acetate copolymers for improving the cold flow properties and oxidative stability of waste cooking oil biodiesel-diesel blends - Bin Sun; Xiaokang Zhang; Yuzhuang Zhao; Fengfei Chen; Feihe Ren; Hualin Lin; Yuan Xue; Sheng Han (Fuel, 2023)

Distribution and toxicity of submicron plastic particles in mice - Tsung-Yen Tsou; Sheng-Han Lee; Tzu-Hsuan Kuo; Chu-Chun Chien; Hsin-Chang Chen; Tsun-Jen Cheng (Environmental Toxicology and Pharmacology, 2023)

Improving tea (Camellia sinensis) quality, economic income, and environmental benefits by optimizing agronomic nitrogen efficiency: A synergistic strategy - Sheng Tang; Haoran Fu; Wankun Pan; Jingjie Zhou; Meng Xu; Kefeng Han; Kaijun Chen; Qingxu Ma; Lianghuan Wu (European Journal of Agronomy, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Numerical study of steel plate shear walls with diverse construction configurations - Chen Wang; Li-yan Xu; Ling-han Song; Jian-sheng Fan (Engineering Structures, 2023)

Investigation of modal parameters of a 600-m-tall skyscraper based on two-year-long structural health monitoring data and five typhoons measurements - Kang Zhou; Qiu-Sheng Li; Lun-Hai Zhi; Xu-Liang Han; Kang Xu (Engineering Structures, 2023)

Single atom Co-anchored nitrogen‑doped graphene for peroxymonosulfate activation with high selectivity of singlet oxygen generation - Han-Qing Zhao; Jun-Sheng Song; Peili Lu; Yang Mu (Chemical Engineering Journal, 2023)

Can phosphobacteria simultaneously achieve phosphorus recovery and Pb2+ removal from wastewater by biomineralization? - Pei Zhang; Yi-Min Ding; Tian-Lei Zhao; Yu-Han Wang; Qi-Zhi Yao; Sheng-Quan Fu; Gen-Tao Zhou (Chemical Engineering Journal, 2023)

Physiological equivalent temperature-based and universal thermal climate index-based adaptive-rational outdoor thermal comfort models - Sheng Zhang; Xia Zhang; Dun Niu; Zhaosong Fang; Han Chang; Zhang Lin (Building and Environment, 2023)

Characterization, expression patterns and functional analysis of PcMPK12 gene in Phytophthora capsici - Tong-tong Zhu; Sheng-han Xiang; Lei Yang; Fang Tang; Wei Li; Ying-bao Liu; Wen-xiu Sun (European Journal of Plant Pathology, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Global pattern of soil priming effect intensity and its environmental drivers - Fei Mo; Chengjie Ren; Kailiang Yu; Zhenghu Zhou; Richard P. Phillips; Zhongkui Luo; Yeye Zhang; Yuteng Dang; Juan Han; Jian‐Sheng Ye; Nangia Vinay; Yuncheng Liao; et al. (Ecology, 2022)
The microbial priming effect—the decomposition of soil organic carbon (SOC) induced by plant inputs—has long been considered an important driver of SOC dynamics, yet we have limited understanding about the direction, intensity, and drivers of priming across ecosystem types and biomes. This gap hinders our ability to predict how shifts in litter inputs under global change can affect climate feedbacks. Here, we synthesized 18,919 observations of CO 2 effluxes in 802 soils across the globe to test the relative effects (i.e., log response ratio [RR]) of litter additions on native SOC decomposition and identified the dominant environmental drivers in natural ecosystems and agricultural lands. Globally, litter additions enhanced native SOC decomposition (RR = 0.35, 95% CI: 0.32–0.38), with greater priming effects occurring with decreasing latitude and more in agricultural soils (RR = 0.43) than in uncultivated soils (RR = 0.28). In natural ecosystems, soil pH and microbial community composition (e.g., bacteria: fungi ratio) were the best predictors of priming, with greater effects occurring in acidic, bacteria‐dominated sandy soils. In contrast, the substrate properties of plant litter and soils were the most important drivers of priming in agricultural systems since soils with high C:N ratios and those receiving large inputs of low‐quality litter had the highest priming effects. Collectively, our results suggest that, though different factors may control priming effects, the ubiquitous nature of priming means that alterations of litter quality and quantity owing to global changes will likely have consequences for global C cycling and climate forcing.

A new tigliane-type diterpenoid from Euphorbia tirucalli - Han-Zhuang Weng; Yang Tian; Jun-Sheng Zhang; Jia-Luo Huang; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Gene Expression Analysis of Laser-Captured Purkinje Cells in the Essential Tremor Cerebellum - Regina T. Martuscello; Karthigayini Sivaprakasam; Whitney Hartstone; Sheng-Han Kuo; Genevieve Konopka; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

Potential therapeutic strategies for myocardial infarction: the role of Toll-like receptors - Sumra Komal; Nimrah Komal; Ali Mujtaba; Shu-Hui Wang; Li-Rong Zhang; Sheng-Na Han (Immunologic Research, 2022)

Physiological Recordings of the Cerebellum in Movement Disorders - Ami Kumar; Chih-Chun Lin; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)
The cerebellum plays an important role in movement disorders, specifically in symptoms of ataxia, tremor, and dystonia. Understanding the physiological signals of the cerebellum contributes to insights into the pathophysiology of these movement disorders and holds promise in advancing therapeutic development. Non-invasive techniques such as electroencephalogram and magnetoencephalogram can record neural signals with high temporal resolution at the millisecond level, which is uniquely suitable to interrogate cerebellar physiology. These techniques have recently been implemented to study cerebellar physiology in healthy subjects as well as individuals with movement disorders. In the present review, we focus on the current understanding of cerebellar physiology using these techniques to study movement disorders.

Elastic simulation method in an irregular polar coordinate system - Yu Yang; Qi Ran; Kang Chen; Cheng Lei; Yu-sheng Zhang; Song Han (Applied Geophysics, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Stachybotranes A–D, phenylspirodrimanes from the wetland fungus Stachybotrys chartarum with cytotoxic activities - Yan-Ru Bao; Han-Lin Feng; Xin-Sheng Yao (Natural Product Research, 2022)

Silicon isotope fractionation dynamics during uptake and translocation by various crop species under three soil types - Jingjie Zhou; Sheng Tang; Wankun Pan; Han Xiao; Qingxu Ma; Yan Sun; Meng Xu; Mengjiao Liu; Lianghuan Wu (Plant and Soil, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Stress Distribution of Four-Unit Implant-Supported Fixed Partial Prosthesis with Different Numbers and Positions of Fixtures in Maxilla Anterior Region-3D FEA - Kai-Chun Cheng; Pao-Hsin Liu; Han-Sheng Chen; Ting-Hsun Lan (Journal of Medical and Biological Engineering, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Integrative epigenomic and transcriptomic analyses reveal metabolic switching by intermittent fasting in brain - Gavin Yong-Quan Ng; Dominic Paul Lee Kok Sheng; Han-Gyu Bae; Sung Wook Kang; David Yang-Wei Fann; Jinsu Park; Joonki Kim; Asfa Alli-Shaik; Jeongmi Lee; Eunae Kim; Sunyoung Park; Jeung-Whan Han; et al. (GeroScience, 2022)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Occurrence Characteristics of Saline-Lacustrine Shale-Oil in the Qianjiang Depression, Jianghan Basin, Central China - Zhongliang Sun; Zhiliang He; Furong Wang; Yuanjia Han; Sheng He; Yuguang Hou; Jing Luo; Youheng Zheng; Shiqiang Wu (Journal of Earth Science, 2022)

The Chinese Carbon-Neutral Goal: Challenges and Prospects - Ning Zeng; Kejun Jiang; Pengfei Han; Zeke Hausfather; Junji Cao; Daniel Kirk-Davidoff; Shaukat Ali; Sheng Zhou (Advances in Atmospheric Sciences, 2022)

Species and Functional Dynamics of the Demersal Fish Community and Responses to Disturbances in the Pearl River Estuary - Zeyu Zeng; William W. L. Cheung; Han Lai; Huadong Yi; Sheng Bi; Haiyang Li; Xiaoli Chen; Yuqin Su; Xuange Liu; Qiuxian Chen; Zhilun Zhang; Xuchong Wei; et al. (Frontiers in Marine Science, 2022)
Fishery resources are threatened by environmental changes and anthropogenic pressures, particularly in coastal ecosystems. It is crucial to understand the changes of fish communities and their responses to environmental changes and human disturbances to formulate rational fisheries and ecosystem-based management. The Pearl River Estuary (PRE) is a typical sub-tropic coastal ecosystem located in the center of the Guangdong-Hong Kong-Macao Greater Bay Area in the northern South China Sea. The demersal fish in the PRE is traditionally targeted as commercial fishing and severely impacted by overexploitation and hypoxia in the last few decades. In this study, we analyze the fish survey data during the period of 2020~2021 using multivariate statistics to investigate the impacts of human disturbances on the species and functional dynamics of the demersal fish community in the PRE. The results reveal that dissolved oxygen and temperature have significant correlations with the functional traits of the demersal fish community. The impacts of hypoxia on the demersal fish vary with species and locations. We found that the mean functional redundancy of the demersal fish community in the PRE was high across three surveys, but the functional diversity was low in this region. The abundance and richness of the demersal fish community increased during the summer fishing moratorium in the South China Sea in 2021, but the functional diversity did not increase significantly. We conclude that the high functional redundancy in the PRE might not be sufficient to buffer against environmental disturbances because of its low functional diversity. Our study highlights the complicated interactions between the demersal fish community and disturbances in the PRE. Understanding the traits structure and functional diversity of the fish community can help elucidate the factors determining the dynamic responses of the fish community to disturbances.

An Exploratory Survey on the Care for Ataxic Patients in the American Continents and the Caribbean - Laura Bannach Jardim; Ali Hasan; Sheng-han Kuo; Jonathan Javier Magaña; Marcondes França; Wilson Marques; Claudia Camejo; Luiz Carlos Santana-da-Silva; Emília Embiruçu Leão; Gisele Espíndola; Francisca Canals; Marcelo Miranda; et al. (The Cerebellum, 2022)

Visible Particle Identification Using Raman Spectroscopy and Machine Learning - Han Sheng; Yinping Zhao; Xiangan Long; Liwen Chen; Bei Li; Yiyan Fei; Lan Mi; Jiong Ma (AAPS PharmSciTech, 2022)

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

Design, synthesis of amide derivatives of scutellarin and their antileukemia and neuroprotective activities - Tong Han; Chunyu Jiang; Xing Wei; Meilin Sheng; Qin Xie; Jiqiang Zhang; Yongyi Zhang; Chenghao Jin (Medicinal Chemistry Research, 2022)

The potential mechanism of Bupleurum against anxiety was predicted by network pharmacology study and molecular docking - Han-Biao Wu; Yu-Gang Xiao; Ji-Sheng Chen; Zhi-Kun Qiu (Metabolic Brain Disease, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

Exploring the Potential Antidepressant Mechanisms of Pinellia by Using the Network Pharmacology and Molecular Docking - Yu-Gang Xiao; Han-Biao Wu; Ji-Sheng Chen; Xiong Li; Zhi-Kun Qiu (Metabolic Brain Disease, 2022)

Analysis of Time-Dependent Soil Behavior Above High-Filled Cut-and-Cover Tunnels Using Discrete Element Method - Sheng Li; Guoqiang Han; I-Hsuan Ho; Li Ma; Balasingam Muhunthan; Qicai Wang; Changdan Wang (Geotechnical and Geological Engineering, 2022)

Expansion of bilin‐based red light sensors in the subaerial desert cyanobacterium Nostoc flagelliforme - Hai‐Feng Xu; Guo‐Zheng Dai; Yu‐Jie Wang; Chao Cheng; Jin‐Long Shang; Ren‐Han Li; Ke Liu; Deqiang Duanmu; Bao‐Sheng Qiu (Environmental Microbiology, 2022)
Summary Light is the crucial environmental signal for desiccation‐tolerant cyanobacteria to activate photosynthesis and prepare for desiccation at dawn. However, the photobiological characteristics of desert cyanobacteria adaptation to one of the harshest habitats on Earth remain unresolved. In this study, we surveyed the genome of a subaerial desert cyanobacterium Nostoc flagelliforme and identified two phytochromes and seven cyanobacteriochromes (CBCRs) with one or more bilin‐binding GAF (cGMP phosphodiesterase/adenylyl cyclase/FhlA) domains. Biochemical and spectroscopic analyses of 69 purified GAF‐containing proteins from recombinant phycocyanobilin (PCB), biliverdin or phycoerythrobilin‐producing Escherichia coli indicated that nine of these proteins bind chromophores. Further investigation revealed that 11 GAFs form covalent adducts responsive to near‐UV and visible light: eight GAFs contained PCB chromophores, three GAFs contained biliverdin chromophores and one contained the PCB isomer, phycoviolobilin. Interestingly, COO91_03972 is the first‐ever reported GAF‐only CBCR capable of sensing five wavelengths of light. Bioinformatics and biochemical analyses revealed that residue P132 of COO91_03972 is essential for chromophore binding to dual‐cysteine CBCRs. Furthermore, the complement of N . flagelliforme CBCRs is enriched in red light sensors. We hypothesize that these sensors are critical for the acclimatization of N . flagelliforme to weak light environments at dawn.

Unexpected role of electron‐transfer hub in direct degradation of pollutants by exoelectrogenic bacteria - Ting‐Ting Zhu; Zhou‐Hua Cheng; Sheng‐Song Yu; Wen‐Wei Li; Dong‐Feng Liu; Han‐Qing Yu (Environmental Microbiology, 2022)
Summary Exoelectrogenic bacteria (EEB) are capable of anaerobic respiration with diverse extracellular electron acceptors including insoluble minerals, electrodes and flavins, but the detailed electron transfer pathways and reaction mechanisms remain elusive. Here, we discover that CymA, which is usually considered to solely serve as an inner‐membrane electron transfer hub in Shewanella oneidensis MR‐1 (a model EEB), might also function as a reductase for direct reducing diverse nitroaromatic compounds (e.g. 2,4‐dichloronitrobenzene) and azo dyes. Such a process can be accelerated by dosing anthraquinone‐2,6‐disulfonate. The CymA‐based reduction pathways in S . oneidensis MR‐1 for different contaminants could be functionally reconstructed and strengthened in Escherichia coli . The direct reduction of lowly polar contaminants by quinol oxidases like CymA homologues might be universal in diverse microbes. This work offers new insights into the pollutant reduction mechanisms of EEB and unveils a new function of CymA to act as a terminal reductase.

Home Aerobic Training for Cerebellar Degenerative Diseases: a Randomized Controlled Trial - Scott Barbuto; Sheng-Han Kuo; Lauren Winterbottom; Seonjoo Lee; Yaakov Stern; Michael O’Dell; Joel Stein (The Cerebellum, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Assessment of genetic diversity among Chinese high-oleic peanut genotypes using miniature inverted-repeat transposable element markers - Chuan Tang Wang; Guo Sheng Song; Zhi Wei Wang; Hong Ju Li; Hong Wei Han; Xiao Yuan Chi; Xiu Zhen Wang; Xiu Shan Sun (Genetic Resources and Crop Evolution, 2022)

Evaluation of leachate production and level in municipal solid waste landfills considering secondary compression - Han Ke; Chen Sheng Zhang; Jie Hu; Rui Qin; Yun Min Chen; Ji Wu Lan (Environmental Science and Pollution Research, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

Essential Tremor versus “ET-plus”: A Detailed Postmortem Study of Cerebellar Pathology - John T. Gionco; Whitney G. Hartstone; Regina T. Martuscello; Sheng-Han Kuo; Phyllis L. Faust; Elan D. Louis (The Cerebellum, 2021)

Interaction of Irregular Waves with Vertical Breakwater and Characteristics of Secondary Wave Generated by Overtopping - Xinyu Han; Yunpeng Jiang; Sheng Dong (Journal of Ocean University of China, 2021)

A network pharmacology study with molecular docking to investigate the possibility of licorice against posttraumatic stress disorder - Zhi-Kun Qiu; Zhi-Ting Liu; Jia-Li Pang; Han-Biao Wu; Xu Liu; Ze-Min Yang; Xiong Li; Ji-Sheng Chen (Metabolic Brain Disease, 2021)

Association of myostatin deficiency with collagen related disease-umbilical hernia and tippy toe standing in pigs - Hyo-Jin Paek; Zhao-Bo Luo; Hak-Myong Choe; Biao-Hu Quan; Kai Gao; Sheng-Zhong Han; Zhou-Yan Li; Jin-Dan Kang; Xi-Jun Yin (Transgenic Research, 2021)

Sesquiterpenoids from Artemisia argyi and their NO production inhibitory activity in RAW264.7 cells - Gui-Min Xue; Jin-Feng Xue; Chen-Guang Zhao; Zhen-Zhu Zhao; Yan-Jun Sun; Kun Du; Han-Wei Li; Wei-Sheng Feng (Natural Product Research, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Distinctive role of fluG in the adaptation of Beauveria bassiana to insect‐pathogenic lifecycle and environmental stresses - Chong‐Tao Guo; Han Peng; Sen‐Miao Tong; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2021)
Summary The upstream developmental activation (UDA) pathway comprises three fluG ‐cored cascades ( fluG‐flbA , fluG‐flbE/B/D and fluG‐flbC ) that activate the key gene brlA of central developmental pathway (CDP) to initiate conidiation in aspergilli. However, the core role of fluG remains poorly understood in other fungi. Here, we report distinctive role of fluG in the insect‐pathogenic lifecycle of Beauveria bassiana . Disruption of fluG resulted in limited conidiation defect, which was mitigated with incubation time and associated with time‐course up‐regulation/down‐regulation of all flb and CDP genes and another fluG ‐like gene (BBA_06309). In Δ fluG , increased sensitivities to various stresses correlated with repression of corresponding stress‐responsive genes. Its virulence through normal cuticle infection was attenuated greatly due to blocked secretion of cuticle‐degrading enzymes and delayed formation of hyphal bodies (blastospores) to accelerate proliferation in vivo and host death. In submerged Δ fluG cultures mimicking insect haemolymph, largely increased blastospore production concurred with drastic up‐regulation of the CDP genes brlA and abaA , which was associated with earlier up‐regulation of most flb genes in the cultures. Our results unveil an essentiality of fluG for fungal adaptation to insect‐pathogenic lifecycle and suggest the other fluG ‐like gene to act as an alternative player in the UDA pathway of B . bassiana .

Two white collar proteins protect fungal cells from solar UV damage by their interactions with two photolyases in Metarhizium robertsii - Han Peng; Chong‐Tao Guo; Sen‐Miao Tong; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2021)
Summary The photolyases PHR1 and PHR2 enable photorepair of fungal DNA lesions in the forms of UV‐induced cyclobutane pyrimidine dimer (CPD) and (6‐4)‐pyrimidine‐pyrimidone (6‐4PP) photoproducts, but their regulation remains mechanistically elusive. Here, we report that the white collar proteins WC1 and WC2 mutually interacting to form a light‐responsive transcription factor regulate photolyase expression required for fungal UV resistance in the insect‐pathogenic fungus Metharhizum robertsii . Conidial UVB resistance decreased by 54% in Δ wc1 and 67% in Δ wc2 . Five‐hour exposure of UVB‐inactivated conidia to visible light resulted in photoreactivation rates of 30% and 9% for the Δ wc1 and Δ wc2 mutants, contrasting to 79%–82% for wild‐type and complemented strains. Importantly, abolished transcription of phr1 in Δ wc‐2 and of phr2 in Δ wc1 resulted in incapable photorepair of CDP and 6‐4PP DNA lesions in UVB‐impaired Δ wc2 and Δ wc1 cells respectively. Yeast two‐hybrid assays revealed interactions of either WC protein with both PHR1 and PHR2. Therefore, the essential roles for WC1 and WC2 in both photorepair of UVB‐induced DNA lesions and photoreactivation of UVB‐inactivated conidia rely upon their interactions with, and hence transcriptional activation of, PHR1 and PHR2. These findings uncover a novel WC‐cored pathway that mediates filamentous fungal response and adaptation to solar UV irradiation.

Shrub‐rings used to reconstruct drought history of the central Alxa desert, northwest China - Ai‐Jun Ding; Sheng‐Chun Xiao; Xiao‐Mei Peng; Quan‐Yan Tian; Chao Han (International Journal of Climatology, 2021)
The climate history of the Alxa desert of northwestern China must be sought both in recent instrumental records (dating from 1960) and in high‐resolution proxy data. Climate proxies are scarce in desert areas; however, long‐lived desert shrubs can offer one such proxy. We have used shrub‐ring data from Zygophyllum xanthoxylum , collected in the central Alxa desert, to reconstruct the Self‐calibrating Palmer Drought Severity Index (scPDSI) for the period 1880–2015. The data covers the May–July growth season. When we compared the history constructed from the shrub‐ring data with the instrumental data collected 1960–2015, we found that the reconstructed history explained 41% of the variance in scPDSI data (40% after adjusting for loss of degrees of freedom). The reconstructed history shows that this region has experienced six persistent droughts and four seasons wetter than usual during the period under study. Of note is a severe drought event in 1920s that affected much of northern China (as noted in contemporary documents). The droughts and wet seasons identified in our reconstruction are consistent with reports from other researchers who have studied the climate history or the region. Our study suggests that it is feasible to reconstruct climate history using shrub‐ring data from long‐lived desert shrubs.

Dietary Shifts and Risks of Artifact Ingestion for Argentine Shortfin Squid Illex argentinus in the Southwest Atlantic - Ssu-Wei Chang; Ruei-Gu Chen; Tsung-Han Liu; Yao-Chang Lee; Chih-Shin Chen; Tai-Sheng Chiu; Chia-Ying Ko (Frontiers in Marine Science, 2021)
Cephalopods play an important role in both ecology and fisheries. Variations in the dietary compositions of squids with large populations further promote interactions between different trophic levels in marine ecosystems. Moreover, due to marine pollution, squids are also at risks of artifact ingestion, and there is limited understanding about the influence of artifacts on the feeding behavior of squids. We examined 296 stomachs of the Argentine shortfin squid Illex argentinus collected through commercial catches across the Southwest Atlantic from February to April of 2018 and 2019 to establish the monthly dietary compositions and risks of artifact ingestion. The results supported typical observations that the Argentine shortfin squids switched from a diet dominated by crustaceans at small sizes to consuming larger prey, predominantly fishes and/or cephalopods, at large sizes during their growth and southward migration. Significantly higher consumption of fishes was observed in recent years compared with that observed in other studies since 1992. The ingested artifacts examined were composed of plastic and non-plastic materials. Artifacts were observed in 19.9% of the total number of stomachs, with 20.5% of the empty stomachs containing artifact remains. The results indicate that although the main dietary compositions of the Argentine shortfin squid maintain the taxonomic groups of prey compositions, the dietary structure, i.e., composition percentage, is varying. The detection of artifacts suggests that environmental monitoring is needed in this region in order to manage and conserve the squid and safeguard aquatic food safety.

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Resolvin D1 Attenuates Innate Immune Reactions in Experimental Subarachnoid Hemorrhage Rat Model - Guang-Jie Liu; Tao Tao; Xiang-Sheng Zhang; Yue Lu; Ling-Yun Wu; Yong-Yue Gao; Han Wang; Hai-Bin Dai; Yan Zhou; Zong Zhuang; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2021)

Greater toxic potency of bisphenol AF than bisphenol A in growth, reproduction, and transcription of genes in Daphnia magna - Sheng Chen; Xiaodong Li; Han Li; Siliang Yuan; Jun Li; Chunsheng Liu (Environmental Science and Pollution Research, 2021)

Several natural products isolated from a red alga Gracilaria lemaneiformis and its evaluation of antialgal activity against six common red tide microalgae - Ying-ying Sun; Jing Zhou; Xiu Han; Nai-sheng Zhang; Zi-xuan Yang; Xin Zhang (Environmental Science and Pollution Research, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Cladosporine A, a new indole diterpenoid alkaloid with antimicrobial activities from Cladosporium sp. - Xue Han; Xue-Feng Bao; Chuan-Xi Wang; Jun Xie; Xiao-Jun Song; Ping Dai; Guo-Dong Chen; Dan Hu; Xin-Sheng Yao; Hao Gao (Natural Product Research, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

A novel role of the mitochondrial iron-sulfur cluster assembly protein ISCU-1/ISCU in longevity and stress response - Yi Sheng; Guang Yang; Kaitlyn Casey; Shayla Curry; Mason Oliver; Sung Min Han; Christiaan Leeuwenburgh; Rui Xiao (GeroScience, 2021)

Se Deficiency Induced Inflammation Resulting to a Diminished Contraction of the Small Intestinal Smooth Muscle in Mice - Yong-sheng Wang; Guo-qing Teng; Han Zhou (Biological Trace Element Research, 2021)

New secondary metabolite with cytotoxicity from spawning soft coral Asterospicularia laurae in Taiwan - Jui-Hsin Su; Chih-I Liu; Mei-Chin Lu; Chi-I Chang; Min-Ying Hsieh; Yu-Chi Lin; Chang-Feng Dai; Ya-Han Zhang; Zheng-Yu Lin; Yun-Sheng Lin (Natural Product Research, 2021)

Spatial Analysis of the Fishing Behaviour of Tuna Purse Seiners in the Western and Central Pacific Based on Vessel Trajectory Data - Han Zhang; Sheng-Long Yang; Wei Fan; Hui-Min Shi; San-Ling Yuan (Journal of Marine Science and Engineering, 2021)
The Western and Central Pacific Oceans are the primary operational areas of tuna purse seiners worldwide. Describing and analysing the fishing behaviour of vessels is highly significant for the protection of sustainable tuna resources. This study uses Automatic Identification System (AIS) data of 130 tuna purse seiners from July 2017 to May 2018 and uses data mining methods to identify the operating status of tuna purse seiners; describes the spatial characteristics of fishing intensity and the distribution of hot spots; and analyses vessel spatial characteristics to describe their fishing behaviour. The results show that the tuna purse seiner speed has a marked bimodal distribution, which corresponds to high-speed transiting and low-speed seine operation. Additionally, from July to September 2017, the amount of fishing effort invested by tuna purse seiners was lower than that in other months. The tuna purse seiner activity range includes 120° E–60° W, 30° S–30° N, and the activities for fish and seine operations are primarily concentrated at 140° E–150° W, 15° S–15° N. There are differences between the space for fishing search operations and space where fishing events took place in each month. Spatial analysis shows that the high-speed transiting fishing effort map covers a large area, while seine fishing covers a small area. The global spatial autocorrelation analysis shows that the fishing effort devoted to searching for fish stocks has a spatial distribution pattern of aggregation and close aggregation. The results of a hot-spot analysis show that the hot spots on a heat map for finding fish, which are closely spatially clustered, correspond to vessels searching for fish concentration areas and seine operation areas. Correlation testing shows that under a 5° × 5° grid, there is a high positive correlation between the fishing effort invested in finding fish stocks and the yield data, nets (r > 0.8), and a moderate correlation with catch per unit of effort(CPUE) (r > 0.3). Based on vessel behaviour, the location of the fish school can be directly determined, and the distribution of fish clusters and fishing grounds can be predicted. This study can aid in managing tuna purse seiners in the Western and Central Pacific Oceans and analysing changes in fishery resources.

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Correction to: Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2021)

Detection and genetic characteristics of porcine bocavirus in central China - Lan-Lan Zheng; Jian-Tao Cui; Han Qiao; Xin-Sheng Li; Xiao-Kang Li; Hong-Ying Chen (Archives of Virology, 2021)

Isolation and characterization of two new chroman-4-ones from the endophytic fungus Penicillium chrysogenum obtained from Eucommia ulmoides Oliver - Sheng-Yue Liu; Li-Zhi Wang; Yue-Fei Wang; Lin Li; Guo-Ying Han; Bing-Yang Zhang; Ying Guo; Yong-Zhi He; Shi-Ming Fang; Han Zhang (Natural Product Research, 2020)

Two new alkaloids from the tubers of Corydalis ambigua subsp. amurensis and their anti-proliferative activity - Zhihui Liu; Zhenru Mi; Panpan Wang; Sheng Chang; Na Han; Jun Yin (Natural Product Research, 2020)

Fucoxanthin Mitigates Subarachnoid Hemorrhage-Induced Oxidative Damage via Sirtuin 1-Dependent Pathway - Xiang-Sheng Zhang; Yue Lu; Tao Tao; Han Wang; Guang-Jie Liu; Xun-Zhi Liu; Cang Liu; Da-Yong Xia; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2020)

Germanium Reduces Inflammatory Damage in Mammary Glands During Lipopolysaccharide-Induced Mastitis in Mice - Yong-sheng Wang; Guo-qing Teng; Han Zhou; Chun-liu Dong (Biological Trace Element Research, 2020)

Effects of Different Weaning Protocols on Survival, Growth and Nutritional Composition of Pharaoh Cuttlefish (Sepia pharaonis) Juvenile - Maowang Jiang; Ziru Han; Peng Sheng; Ruibing Peng; Qingxi Han; Xiamin Jiang (Journal of Ocean University of China, 2020)

Continuous time-varying Q-factor estimation method in the time-frequency domain - Qing-Han Wang; Yang Liu; Cai Liu; Zhi-Sheng Zheng (Applied Geophysics, 2020)

Effects of Plant Diversity and Plant Density on Ecosystem Functions in Floating Constructed Wetlands - Wenjuan Han; Xiaoling Sheng; Jiongni Shao; Jia Jiang; Qinru He; Ying Lin (Water, Air, & Soil Pollution, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Identification and analysis of new mycoviruses from melon powdery mildew - Yushanjiang Maimaiti; Lei Ding; Min Chai; Xiaoya Jing; Du Yang; Sheng Han; Liuqing Sun; Wei Chen (Journal of Plant Pathology, 2020)

Spatial variability of soil hydraulic conductivity and runoff generation types in a small mountainous catchment - Yong Yang; Ren-sheng Chen; Yao-xuan Song; Chun-tan Han; Zhang-wen Liu; Jun-feng Liu (Journal of Mountain Science, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Characteristics of the spike and ORF3 genes of porcine epidemic diarrhea virus in Henan and Shanxi provinces of China - Jian-tao Cui; Han Qiao; Cheng-yao Hou; Hui-Hua Zheng; Xin-Sheng Li; Lan-lan Zheng; Hong-Ying Chen (Archives of Virology, 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Classification of Alzheimer’s Disease from 18F-FDG and 11C-PiB PET Imaging Biomarkers Using Support Vector Machine - Bang-Hung Yang; Jyh-Cheng Chen; Wen-Hsiang Chou; Wen-Sheng Huang; Jong-Ling Fuh; Ren‑Shyan Liu; Cheng-Han Wu (Journal of Medical and Biological Engineering, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Bisexual Fertile Triploid Zebrafish (Danio rerio): a Rare Case - Liangyue Peng; Wen Fu; Xianlong Wu; Sheng He; Han Zhao; Jinhui Liu; Wenbin Liu; Yamei Xiao (Marine Biotechnology, 2020)

Response of traditional and taxonomic distinctness diversity indices of benthic macroinvertebrates to environmental degradation gradient in a large Chinese shallow lake - Lei Ji; Xiaoming Jiang; Chunxiang Liu; Ziyi Xu; Jinhui Wang; Sheng Qian; Han Zhou (Environmental Science and Pollution Research, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Pictalignans D-F, three new neolignan derivatives from Selaginella picta - Fei Cheng; Zhen-Xing Zou; Ping-Sheng Xu; Shui-Han Zhang; Yan Zhang; Cai-Ping Yao; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Mitigating off-target effects in CRISPR/Cas9-mediated in vivo gene editing - Hua Alexander Han; Jeremy Kah Sheng Pang; Boon-Seng Soh (Journal of Molecular Medicine, 2020)
The rapid advancement of genome editing technologies has opened up new possibilities in the field of medicine. Nuclease-based techniques such as the CRISPR/Cas9 system are now used to target genetically linked disorders that were previously hard-to-treat. The CRISPR/Cas9 gene editing approach wields several advantages over its contemporary editing systems, notably in the ease of component design, implementation and the option of multiplex genome editing. While results from the early phase clinical trials have been encouraging, the small patient population recruited into these trials hinders a conclusive assessment on the safety aspects of the CRISPR/Cas9 therapy. Potential safety concerns include the lack of fidelity in the CRISPR/Cas9 system which may lead to unintended DNA modifications at non-targeted gene loci. This review focuses modifications to the CRISPR/Cas9 components that can mitigate off-target effects in in vitro and preclinical models and its translatability to gene therapy in patient populations.

Cerebellar Volume Is Associated with Cognitive Decline in Mild Cognitive Impairment: Results from ADNI - Chi-Ying Lin; Chi-Hua Chen; Sarah E. Tom; Sheng-Han Kuo (The Cerebellum, 2020)

Molecular characterization of soil organic carbon in water-stable aggregate fractions during the early pedogenesis from parent material of Mollisols - Na Li; Jinghong Long; Xiaozeng Han; Yaru Yuan; Ming Sheng (Journal of Soils and Sediments, 2020)

Effect of Organic Matter Type and Maturity on Organic Matter Pore Formation of Transitional Facies Shales: A Case Study on Upper Permian Longtan and Dalong Shales in Middle Yangtze Region, China - Zhongrui Wu; Sheng He; Yuanjia Han; Gangyi Zhai; Xipeng He; Zhi Zhou (Journal of Earth Science, 2020)

Optimization and Evaluation of the Thermosensitive In Situ and Adhesive Gel for Rectal Delivery of Budesonide - Lin Chen; Xue Han; Xiaohong Xu; Quan Zhang; Yingchun Zeng; Qing Su; Yujie Liu; Yanmei Sheng; Xingliang Xie (AAPS PharmSciTech, 2020)

Incidence and Clinical Features of TRPV4-Linked Axonal Neuropathies in a USA Cohort of Charcot–Marie–Tooth Disease Type 2 - Sheng Deng; Shawna M. E. Feely; Yong Shi; Hong Zhai; Luna Zhan; Teepu Siddique; Han-Xiang Deng; Michael E. Shy (NeuroMolecular Medicine, 2020)

Fungal community succession under influence of biochar in cow manure composting - Xin Jiang; Liting Deng; Qingxin Meng; Yu Sun; Yue Han; Xiaotong Wu; Siyuan Sheng; Haifeng Zhu; Bello Ayodeji; Ugochi Uzoamaka Egbeagu; Xiuhong Xu (Environmental Science and Pollution Research, 2020)

Isolation of urease-producing bacteria and their effects on reducing Cd and Pb accumulation in lettuce (Lactuca sativa L.) - Tiejun Wang; Shilin Wang; Xingchun Tang; Xianpeng Fan; Sheng Yang; Lunguang Yao; Yadong Li; Hui Han (Environmental Science and Pollution Research, 2020)

Vertical variations in plant- and microbial-derived carbon components in grassland soils - Tian Ma; Guohua Dai; Shanshan Zhu; Dima Chen; Litong Chen; Xiaotao Lü; Xiaobo Wang; Juntao Zhu; Yangjian Zhang; Jin-Sheng He; Yongfei Bai; Xingguo Han; et al. (Plant and Soil, 2020)

A numerical model predicting indoor volatile organic compound Volatile Organic Compounds emissions from multiple building materials - Miao Guo; Wei Yu; Sheng Zhang; Han Wang; Shen Wei (Environmental Science and Pollution Research, 2020)

Climate‐dependent variation in cold tolerance of weedy rice and rice mediated by OsICE1 promoter methylation - Hongjie Xie; Yihao Han; Xinyue Li; Weimin Dai; Xiaoling Song; Kenneth M. Olsen; Sheng Qiang (Molecular Ecology, 2020)
The mechanisms by which weedy rice ( Oryza sativa f. spontanea ) has adapted to endure low‐temperature stress in northern latitudes remain unresolved. In this study, we assessed cold tolerance of 100 rice varieties and 100 co‐occurring weedy rice populations, which were sampled across a broad range of climates in China. A parallel pattern of latitude‐dependent variation in cold tolerance was detected in cultivated rice and weedy rice. At the molecular level, differential cold tolerance was strongly correlated with relative expression levels of CBF cold response pathway genes and with methylation levels in the promoter region of OsICE1 , a regulator of this pathway. Among all methylated cytosine sites of the OsICE1 promoter, levels of CHG and CHH methylation were found to be significantly correlated with cold tolerance among accessions. Furthermore, within many of the collection locales, weedy rice shared identical or near‐identical OsICE1 methylation patterns with co‐occurring cultivated rice. These findings provide new insights on the possible roles that methylation variation in the OsICE1 promoter may play in cold tolerance, and they suggest that weedy rice can rapidly acquire cold tolerance via methylation patterns that are shared with co‐occurring rice cultivars.

Consensus Paper: Experimental Neurostimulation of the Cerebellum - Lauren N. Miterko; Kenneth B. Baker; Jaclyn Beckinghausen; Lynley V. Bradnam; Michelle Y. Cheng; Jessica Cooperrider; Mahlon R. DeLong; Simona V. Gornati; Mark Hallett; Detlef H. Heck; Freek E. Hoebeek; Abbas Z. Kouzani; et al. (The Cerebellum, 2019)

Current Opinions and Consensus for Studying Tremor in Animal Models - Sheng-Han Kuo; Elan D. Louis; Phyllis L. Faust; Adrian Handforth; Su-youne Chang; Billur Avlar; Eric J. Lang; Ming-Kai Pan; Lauren N. Miterko; Amanda M. Brown; Roy V. Sillitoe; Collin J. Anderson; et al. (The Cerebellum, 2019)

Jurassic granitic magmatism in the lesser Xing’an-Zhangguangcai ranges of NE China: the Dong’an example - Ji-Long Han; Jing-Gui Sun; Yang Liu; Liang Ren; Chang-Sheng Wang; Xiao-Tian Zhang; Yun-Peng He; Ri-Dong Yu; Qian Lu (International Geology Review, 2019)

Negative regulation of cadmium tolerance in Arabidopsis by MMDH2 - Xi Wu; Yangyang Han; Xiangyu Zhu; Alia Shah; Wei Wang; Yibao Sheng; Tingting Fan; Shuqing Cao (Plant Molecular Biology, 2019)

Response of a Porous Seabed around an Immersed Tunnel under Wave Loading: Meshfree Model - Shuang Han; Dong-Sheng Jeng; Chia-Cheng Tsai (Journal of Marine Science and Engineering, 2019)
Seabed instability surrounding an immersed tunnel is a vital engineering issue regarding the design and maintenance for submarine tunnel projects. In this study, a numerical model based on the local radial basis function collocation method (LRBFCM) is developed to evaluate the seabed behaviour in a marine environment, in which the seabed is treated as the porous medium and governed by Biot’s “ u − p ” approximation. As for the flow field above the seabed, the VARANS equations are used to simulate the fluid motion and properties. The present model is validated with analytical solutions and experimental data which show a good capacity of the integrated model. Both wave and current loading are considered in this study. Parametric studies are carried out to investigate the effects of wave characteristics and soil properties. Based on the numerical results, the maximum liquefaction depth around the immersed tunnel could be deeper under the wave loading with long wave period (T) and large wave height (H). Moreover, a seabed with lower permeability ( K s ) and degree of saturation ( S r ) is more likely to be liquefied.

Stability of Twin Shallow Tunnels in Unsaturated Soils Considering Vertical Steady State Flow - Zi-han Yang; Shui-sheng Li; Dong Yang; Shuai Zhou; Quan Zhou (Geotechnical and Geological Engineering, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

Tremor in the Degenerative Cerebellum: Towards the Understanding of Brain Circuitry for Tremor - Ruo-Yah Lai; Darya Tomishon; Karla P. Figueroa; Stefan M. Pulst; Susan Perlman; George Wilmot; Christopher M. Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G. Shakkottai; Sarah H. Ying; Theresa Zesiewicz; et al. (The Cerebellum, 2019)

Distribution of lignin phenols in comparison with plant-derived lipids in the alpine versus temperate grassland soils - Shanshan Zhu; Guohua Dai; Tian Ma; Litong Chen; Dima Chen; Xiaotao Lü; Xiaobo Wang; Juntao Zhu; Yangjian Zhang; Yongfei Bai; Xingguo Han; Jin-Sheng He; et al. (Plant and Soil, 2019)

Hispanic Spinocerebellar Ataxia Type 35 (SCA35) with a Novel Frameshift Mutation - Chih-Chun Lin; Shi-Rui Gan; Deepak Gupta; Armin Alaedini; Peter H Green; Sheng-Han Kuo (The Cerebellum, 2019)

Estimating the spatial distribution of environmental suitability for female lung cancer mortality in China based on a novel statistical method - Xiao Han; Yanlong Guo; Hong Gao; Jianmin Ma; Manjie Sang; Sheng Zhou; Tao Huang; Xiaoxuan Mao (Environmental Science and Pollution Research, 2019)

Essential oil of Chrysanthemum indicum L.: potential biocontrol agent against plant pathogen Phytophthora nicotianae - Xiao-Bin Han; Jian Zhao; Jian-Min Cao; Cheng-Sheng Zhang (Environmental Science and Pollution Research, 2019)

Cortical Inflammation is Increased in a DSS-Induced Colitis Mouse Model - Ying Han; Tong Zhao; Xiang Cheng; Ming Zhao; Sheng-Hui Gong; Yong-Qi Zhao; Hai-Tao Wu; Ming Fan; Ling-Ling Zhu (Neuroscience Bulletin, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Adjusting precipitation measurements from the TRwS204 automatic weighing gauge in the Qilian Mountains, China - Qin Zheng; Ren-sheng Chen; Chun-tan Han; Jun-feng Liu; Yao-xuan Song; Zhang-wen Liu; Yong Yang; Lei Wang; Xi-qiang Wang; Xiao-jiao Liu; Shu-hai Guo; Guo-hua Liu (Journal of Mountain Science, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Microsatellite records for volume 10, issue 3 - Ling Ding; Dandan Gao; Jie Han; Zhihong Liu; Tao Pan; Luye Shi; Xiujun Sun; Zhong-lou Sun; Hui Wang; Biao Wu; Gui-you Wu; Yao Xu; et al. (Conservation Genetics Resources, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Risk factors, outcomes and genotypes of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream infection: a three-year retrospective study in a large tertiary hospital in Northern China - Si-Han Zheng; Sheng-Ji Cao; Hui Xu; Dan Feng; Li-Ping Wan; Guang-Jie Wang; Xiao-Guang Xiao (Infectious Diseases, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

The key gluconeogenic gene PCK1 is crucial for virulence of Botrytis cinerea via initiating its conidial germination and host penetration - Jian‐Kang Liu; Hao‐Wu Chang; Yue Liu; Yu (Haity) Qin; Yu‐Han Ding; Lan Wang; Yue Zhao; Ming‐Zhe Zhang; Sheng‐Nan Cao; Le‐Tao Li; Wei Liu; Gui‐Hua Li; et al. (Environmental Microbiology, 2018)
Summary The process of initiation of host invasion and survival of some foliar phytopathogenic fungi in the absence of external nutrients on host leaf surfaces remains obscure. Here, we demonstrate that gluconeogenesis plays an important role in the process and nutrient‐starvation adaptation before the pathogen host invasion. Deletion of phosphoenolpyruvate c arboxy k inase gene BcPCK1 in gluconeogenesis in Botrytis cinerea , the causative agent of grey mould, resulted in the failure of the Δ Bcpck1 mutant conidia to germinate on hard and hydrophobic surface and penetrate host cells in the absence of glucose, reduction in conidiation and slow conidium germination in a nutrient‐rich medium. The wild‐type and Δ Bcpck1 conidia germinate similarly in the presence of glucose (higher concentration) as the sole carbon source. Conidial glucose‐content should reach a threshold level to initiate germination and host penetration. Infection structure formation by the mutants displayed a glucose‐dependent fashion, which corresponded to the mutant virulence reduction. Exogenous glucose or complementation of BcPCK1 completely rescued all the developmental and virulence defects of the mutants. Our findings demonstrate that BcPCK1 plays a crucial role in B. cinerea pathogenic growth and virulence, and provide new insights into gluconeogenesis mediating pathogenesis of plant fungal pathogens via initiation of conidial germination and host penetration.

Heterotopic Purkinje Cells: a Comparative Postmortem Study of Essential Tremor and Spinocerebellar Ataxias 1, 2, 3, and 6 - Elan D. Louis; Sheng-Han Kuo; William J. Tate; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Amyloid β-Derived Diffusible Ligands (ADDLs) Induce Abnormal Autophagy Associated with Aβ Aggregation Degree - Jie Wen; Fang Fang; Shu-Han Guo; Ying Zhang; Xiang-Lei Peng; Wei-Min Sun; Xiao-Ran Wei; Jin-Sheng He; Tao Hung (Journal of Molecular Neuroscience, 2018)

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Genetic Variants Within Molecular Targets of Antipsychotic Treatment: Effects on Treatment Response, Schizophrenia Risk, and Psychopathological Features - Marco Calabrò; Stefano Porcelli; Concetta Crisafulli; Sheng-Min Wang; Soo-Jung Lee; Changsu Han; Ashwin A. Patkar; Prakash S. Masand; Diego Albani; Ilaria Raimondi; Gianluigi Forloni; Sofia Bin; et al. (Journal of Molecular Neuroscience, 2018)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

New methods for calculating bare soil land surface temperature over mountainous terrain - Yong Yang; Ren-sheng Chen; Yao-xuan Song; Jun-feng Liu; Chun-tan Han; Zhang-wen Liu (Journal of Mountain Science, 2017)

Gene Expression Profiling Stratifies IDH1-Mutant Glioma with Distinct Prognoses - Wen Cheng; Xiufang Ren; Chuanbao Zhang; Jinquan Cai; Sheng Han; Anhua Wu (Molecular Neurobiology, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Cerebellar Pathology in Familial vs. Sporadic Essential Tremor - Elan D. Louis; Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2017)

Phylogenetic analysis of IDD gene family and characterization of its expression in response to flower induction in Malus - Sheng Fan; Dong Zhang; Libo Xing; Siyan Qi; Lisha Du; Haiqin Wu; Hongxia Shao; Youmei Li; Juanjuan Ma; Mingyu Han (Molecular Genetics and Genomics, 2017)

Antipredation Sleeping Behavior of Skywalker Hoolock Gibbons (Hoolock tianxing) in Mt. Gaoligong, Yunnan, China - Han-Lan Fei; Dao Zhang; Sheng-Dong Yuan; Lu Zhang; Peng-Fei Fan (International Journal of Primatology, 2017)

Local adaptation shapes pattern of mitochondrial population structure in Sebastiscus marmoratus - Sheng-Yong Xu; Dian-Rong Sun; Na Song; Tian-Xiang Gao; Zhi-Qiang Han; Bo-Nian Shui (Environmental Biology of Fishes, 2017)

Cell-culture derived fowl adenovirus serotype 4 inactivated vaccine provides complete protection for virus infection on SPF chickens - Dongying Du; Pantao Zhang; Xiangdong Li; Hui Tian; Yi Cheng; Dongbei Sheng; Xueying Han; Yihong Shan; Xuefeng Li; Yue Yuan; Haiyang Zhang; Jingjing Xue; et al. (VirusDisease, 2017)

The Initial Symptom and Motor Progression in Spinocerebellar Ataxias - Lan Luo; Jie Wang; Raymond Y Lo; Karla P Figueroa; Stefan M Pulst; Pei-Hsin Kuo; Susan Perlman; George Wilmot; Christopher M Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G Shakkottai; et al. (The Cerebellum, 2017)

Cerebellar Pathology in Early Onset and Late Onset Essential Tremor - Sheng-Han Kuo; Jie Wang; William J. Tate; Ming-Kai Pan; Geoffrey C. Kelly; Jesus Gutierrez; Etty P. Cortes; Jean-Paul G. Vonsattel; Elan D. Louis; Phyllis L. Faust (The Cerebellum, 2017)

Genes Related to Oxytocin and Arginine-Vasopressin Pathways: Associations with Autism Spectrum Disorders - Rong Zhang; Hong-Feng Zhang; Ji-Sheng Han; Song-Ping Han (Neuroscience Bulletin, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Effects of rapid ascent on the heart rate variability of individuals with and without acute mountain sickness - Ming Ling Yih; Fang-Chi Lin; Heng-Sheng Chao; Han-Chen Tsai; Shi-Chuan Chang (European Journal of Applied Physiology, 2017)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)

Antidepressant-Like and Anxiolytic-Like Effects of ZBD-2, a Novel Ligand for the Translocator Protein (18 kDa) - Dong-sheng Wang; Jing Han; Shuo Li; Ting Sun; Yan-yan Guo; Wen-bo Kang; Zhen Tian; Jian-ning Zhao; Gang Liu; Shui-bing Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

Sinomenine attenuates chronic inflammatory pain in mice - Shuo Li; Jing Han; Dong-sheng Wang; Qi Yang; Bin Feng; Wen-bo Kang; Le Yang; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

Temporal dynamics of fungal communities in soybean rhizosphere - Li-Li Han; Jun-Tao Wang; Sheng-Hui Yang; Wen-Feng Chen; Li-Mei Zhang; Ji-Zheng He (Journal of Soils and Sediments, 2017)

CRIM1 is necessary for coronary vascular endothelial cell development and homeostasis - Swati Iyer; Yash Chhabra; Tracey J. Harvey; Richard Wang; Han Sheng Chiu; A. G. Smith; Walter G. Thomas; David J. Pennisi; Michael Piper (Journal of Molecular Histology, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Cd inhibition and pH improvement via a nano-submicron mineral-based soil conditioner - Shanke Liu; Huan Li; Cheng Han; Xuebin Sheng; Jianming Liu (Environmental Science and Pollution Research, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

Inoculation with endophytic Bacillus megaterium H3 increases Cd phytostabilization and alleviates Cd toxicity to hybrid pennisetum in Cd-contaminated aquatic environments - Ya Li; Hui Han; Lin Yan He; Qi Wang; Xia Fang Sheng (Environmental Science and Pollution Research, 2017)

Mapping Purkinje Cell Placement Along the Purkinje Cell Layer: an Analysis of Postmortem Tissue from Essential Tremor Patients vs. Controls - Elan D. Louis; Daniel Rabinowitz; Matthew Choe; William J. Tate; Geoffrey C. Kelly; Sheng-Han Kuo; Phyllis L. Faust (The Cerebellum, 2016)

Plasma Oxytocin and Arginine-Vasopressin Levels in Children with Autism Spectrum Disorder in China: Associations with Symptoms - Hong-Feng Zhang; Yu-Chuan Dai; Jing Wu; Mei-Xiang Jia; Ji-Shui Zhang; Xiao-Jing Shou; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2016)

Combining nonthermal plasma with perovskite-like catalyst for NOx storage and reduction - Han Hsuan Peng; Kuan Lun Pan; Sheng Jen Yu; Shaw Yi Yan; Moo Been Chang (Environmental Science and Pollution Research, 2016)

Valuation of debris flow mitigation measures in tourist towns: a case study on Hongchun gully in southwest China - Ming-li Chen; Gui-sheng Hu; Ning-sheng Chen; Cun-yao Zhao; Song-jiang Zhao; Da-wei Han (Journal of Mountain Science, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Reproductive responses of male Brandt’s voles (Lasiopodomys brandtii) to 6-methoxybenzoxazolinone (6-MBOA) under short photoperiod - Xin Dai; Lian Yu Jiang; Mei Han; Man Hong Ye; Ai Qin Wang; Wan Hong Wei; Sheng Mei Yang (The Science of Nature, 2016)

Echinocystic acid reduces reserpine-induced pain/depression dyad in mice - Shuo Li; Jing Han; Dong-sheng Wang; Bin Feng; Ya-ting Deng; Xin-shang Wang; Qi Yang; Ming-gao Zhao (Metabolic Brain Disease, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Ultrasonic method for measuring water holdup of low velocity and high-water-cut oil-water two-phase flow - An Zhao; Yun-Feng Han; Ying-Yu Ren; Lu-Sheng Zhai; Ning-De in (Applied Geophysics, 2016)

Measurement of aerosol effective density by single particle mass spectrometry - GuoHua Zhang; XinHui Bi; BingXue Han; Ning Qiu; ShouHui Dai; XinMing Wang; GuoYing Sheng; JiaMo Fu (Science China Earth Sciences, 2016)

Enhancement of naphthalene tolerance in transgenic Arabidopsis plants overexpressing the ferredoxin-like protein (ADI1) from rice - Xiao-Yan Fu; Bo Zhu; Hong-Juan Han; Wei Zhao; Yong-Sheng Tian; Ri-He Peng; Quan-Hong Yao (Plant Cell Reports, 2016)

High-Performance Multiclass Classification Framework Using Cloud Computing Architecture - Feng-Sheng Lin; Chia-Ping Shen; Chia-Hung Liu; Han Lin; Chi-Ying F. Huang; Cheng-Yan Kao; Feipei Lai; Jeng-Wei Lin (Journal of Medical and Biological Engineering, 2015)

Application of a weak magnetic field to improve microbial fuel cell performance - Zhong-Hua Tong; Han-Qing Yu; Wen-Wei Li; Yun-Kun Wang; Min Sun; Xian-Wei Liu; Guo-Ping Sheng (Ecotoxicology, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Dust aerosol effects on cirrus and altocumulus clouds in Northwest China - Wencai Wang; Lifang Sheng; Hongchun Jin; Yongqing Han (Journal of Meteorological Research, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Improving Rice Ability to Degrade Different Polycyclic Aromatic Hydrocarbons Through Multigene Transformation of a Hybrid Dioxygenase System - Ri-He Peng; Biao Shi; Xiao-Yan Fu; Yong-Sheng Tian; Wei Zhao; Bo Zhu; Jing Xu; Hong-Juan Han; Zhong-Yi Yuan; Kai-Hong Liu; Quan-Hong Yao (Plant Molecular Biology Reporter, 2015)

Comparisons of two types of teleostean pseudobranchs, silver moony (Monodactylus argenteus) and tilapia (Oreochromis mossambicus), with salinity-dependent morphology and ion transporter expression - Sheng-Hui Yang; Chao-Kai Kang; Yau-Chung Hu; Ling-Chia Yen; Shu-Chuan Tsai; Yueh-Ling Hsieh; Tsung-Han Lee (Journal of Comparative Physiology B, 2015)

Distribution and estimation of aboveground biomass of alpine shrubs along an altitudinal gradient in a small watershed of the Qilian Mountains, China - Zhang-wen Liu; Ren-sheng Chen; Yao-xuan Song; Chun-tan Han (Journal of Mountain Science, 2015)

Zoeppritz equation-based prestack inversion and its application in fluid identification - Han-Dong Huang; Yan-Chao Wang; Fei Guo; Sheng Zhang; Yong-Zhen Ji; Cheng-Han Liu (Applied Geophysics, 2015)

Drug susceptibility and molecular epidemiology of Escherichia coli in bloodstream infections in Shanghai, China, 2011–2013 - Sheng-Yuan Zhao; Yan-Chun Wang; Shu-Zhen Xiao; Xiao-Fei Jiang; Xiao-Kui Guo; Yu-Xing Ni; Li-Zhong Han (Infectious Diseases, 2015)

Analysis of serum levels of 15 trace elements in breast cancer patients in Shandong, China - Xiao Ding; Meng Jiang; Haiyan Jing; Wei Sheng; Xingwen Wang; Junqing Han; Luhua Wang (Environmental Science and Pollution Research, 2015)

Transglutaminase-2 is Involved in Cell Apoptosis of Osteosarcoma Cell Line U2OS Under Hypoxia Condition - Wei Wang; Xiao Li; Xiang-zhen Han; Fan-bin Meng; Zhen-xing Wang; Yong-qing Zhai; Dong-sheng Zhou (Cell Biochemistry and Biophysics, 2015)

Partial Volume Correction for Equivocal Retropharyngeal Nodal Metastases of Nasopharyngeal Carcinoma with Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography - Yu-Wen Wang; Chin-Shun Wu; Chih-Han Chang; Kuo-Sheng Cheng; Yu-Kang Chang; I-Wen Huang; Chin-Li Lu; Wei-Jen Yao (Journal of Medical and Biological Engineering, 2015)

Late Triassic Batang Group arc volcanic rocks in the northeastern margin of Qiangtang terrane, northern Tibet: partial melting of juvenile crust and implications for Paleo-Tethys ocean subduction - Shao-Qing Zhao; Jun Tan; Jun-Hao Wei; Ning Tian; Dao-Han Zhang; Sheng-Nan Liang; Jia-Jie Chen (International Journal of Earth Sciences, 2015)

Isolation and characterization of pyrroline-5-carboxylate synthetase gene from perennial ryegrass (Lolium perenne L.) - Li Cao; Lei Han; Hua-li Zhang; Hai-bo Xin; Muhammad Imtiaz; Ming-Fang Yi; Zhen-Yuan Sun; Guan-Sheng Ju; Yong-Qiang Qian; Jun-Xiang Liu (Acta Physiologiae Plantarum, 2015)

Enantiomeric composition of polycyclic musks in sediments from the Pearl River and Suzhou Creek - Han Song; Xiangying Zeng; Zhiqiang Yu; Delin Zhang; Shuxia Cao; Wenlan Shao; Guoying Sheng; Jiamo Fu (Environmental Science and Pollution Research, 2015)

Aboveground biomass and water storage allocation in alpine willow shrubs in the Qilian Mountains in China - Zhang-wen Liu; Ren-sheng Chen; Yao-xuan Song; Chun-tan Han (Journal of Mountain Science, 2015)

Isocitrate lyase is required for urediniospore germination of Puccinia striiformis f. sp. tritici - Jie Liu; Qiu-Ling Wang; Qing Chang; Li-Na Han; Guo-Liang Pei; Yue-Qing Xue; Lu-Meng Jia; Kun Zhang; Yuan-Yuan Duan; Zhen-Sheng Kang (Molecular Biology Reports, 2014)

One-step integration of multiple genes into the oleaginous yeast Yarrowia lipolytica - Shuliang Gao; Linna Han; Li Zhu; Mei Ge; Sheng Yang; Yu Jiang; Daijie Chen (Biotechnology Letters, 2014)

Effect of Iron Supplementation on the Expression of Hypoxia-Inducible Factor and Antioxidant Status in Rats Exposed to High-Altitude Hypoxia Environment - Chunlan Xu; Chen Dong; Cuicui Xu; Tiaotiao Han; Sheng Bao; Xiaobo Gao (Biological Trace Element Research, 2014)

Combined impacts of antecedent earthquakes and droughts on disastrous debris flows - Ning-sheng Chen; Yang Lu; Hai-bo Zhou; Ming-feng Deng; Da-wei Han (Journal of Mountain Science, 2014)

The effect of temperature on the extrinsic incubation period and infection rate of dengue virus serotype 2 infection in Aedes albopictus - Fang-Zhen Xiao; Yi Zhang; Yan-Qin Deng; Si He; Han-Guo Xie; Xiao-Nong Zhou; Yan-Sheng Yan (Archives of Virology, 2014)

Torpedo Formation and Purkinje Cell Loss: Modeling their Relationship in Cerebellar Disease - Elan D. Louis; Sheng-Han Kuo; Jean-Paul G. Vonsattel; Phyllis L. Faust (The Cerebellum, 2014)

Enhancement of nitrogen and phosphorus removal from eutrophic water by economic plant annual ryegrass (Lolium multiflorum) with ion implantation - Miao Li; Guo-ping Sheng; Yue-jin Wu; Zeng-liang Yu; Gary S. Bañuelos; Han-qing Yu (Environmental Science and Pollution Research, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of Spatial Scale of Soil Heterogeneity on the Growth of a Clonal Plant Producing Both Spreading and Clumping Ramets - Yong-Qiang Qian; Dong Luo; Gu Gong; Lei Han; Guan-Sheng Ju; Zhen-Yuan Sun (Journal of Plant Growth Regulation, 2014)

Exploring how extracellular electric field modulates neuron activity through dynamical analysis of a two-compartment neuron model - Guo-Sheng Yi; Jiang Wang; Xi-Le Wei; Kai-Ming Tsang; Wai-Lok Chan; Bin Deng; Chun-Xiao Han (Journal of Computational Neuroscience, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Synergistic effects of berberines with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Yang Li; Gen-Chun Wang; Zuo-Sheng Li; Jun Han (Medicinal Chemistry Research, 2014)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

Putative Pathway of Sex Pheromone Biosynthesis and Degradation by Expression Patterns of Genes Identified from Female Pheromone Gland and Adult Antenna of Sesamia inferens (Walker) - Ya-Nan Zhang; Yi-Han Xia; Jia-Yao Zhu; Sheng-Yun Li; Shuang-Lin Dong (Journal of Chemical Ecology, 2014)

Ranging behavior of eastern hoolock gibbon (Hoolock leuconedys) in a northern montane forest in Gaoligongshan, Yunnan, China - Dao Zhang; Han-Lan Fei; Sheng-Dong Yuan; Wen-Mo Sun; Qing-Yong Ni; Liang-Wei Cui; Peng-Fei Fan (Primates, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Application of Physiologically Based Absorption Modeling to Formulation Development of a Low Solubility, Low Permeability Weak Base: Mechanistic Investigation of Food Effect - Hefei Zhang; Binfeng Xia; Jennifer Sheng; Tycho Heimbach; Tsu-Han Lin; Handan He; Yanfeng Wang; Steven Novick; Ann Comfort (AAPS PharmSciTech, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

Cloning and molecular characterization of a myosin light chain gene from Puccinia striiformis f. sp. tritici - Jie Liu; Li-Na Han; Qiong Zhang; Qiu-Ling Wang; Qing Chang; Hua Zhuang; Jia Liu; Man Li; Dan Yu; Zhen-Sheng Kang (World Journal of Microbiology and Biotechnology, 2014)

Proteomics to reveal metabolic network shifts towards lipid accumulation following nitrogen deprivation in the diatom Phaeodactylum tricornutum - Zhi-Kai Yang; Yu-Han Ma; Jian-Wei Zheng; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Journal of Applied Phycology, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Effects of ecological factors on secondary metabolites and inorganic elements of Scutellaria baicalensis and analysis of geoherblism - LanPing Guo; Sheng Wang; Ji Zhang; Guang Yang; ManXi Zhao; WeiFeng Ma; XiaoBo Zhang; Xuan Li; BangXing Han; NaiFu Chen; LuQi Huang (Science China Life Sciences, 2013)

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon - Huawei Duan; Zhini He; Junxiang Ma; Bo Zhang; Zhiguo Sheng; Ping Bin; Juan Cheng; Yong Niu; Haiyan Dong; Han Lin; Yufei Dai; Benzhan Zhu; et al. (Archives of Toxicology, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Separation method for multi-source blended seismic data - Han-Chuang Wang; Sheng-Chang Chen; Bo Zhang; De-Ping She (Applied Geophysics, 2013)

Utility of Physiologically Based Modeling and Preclinical In Vitro/In Vivo Data to Mitigate Positive Food Effect in a BCS Class 2 Compound - Binfeng Xia; Tycho Heimbach; Tsu-han Lin; Shoufeng Li; Hefei Zhang; Jennifer Sheng; Handan He (AAPS PharmSciTech, 2013)

Investigation of EEG abnormalities in the early stage of Parkinson’s disease - Chun-Xiao Han; Jiang Wang; Guo-Sheng Yi; Yan-Qiu Che (Cognitive Neurodynamics, 2013)

Effects of Norepinephrine on Immune Functions of Cultured Splenic Lymphocytes Exposed to Aluminum Trichloride - Ji-Hong Zhang; Chong-Wei Hu; Yan-Zhu Zhu; Shi-Min Liu; Chong-Sheng Bai; Yan-Fei Han; Shi-Liang Xia; Yan-Fei Li (Biological Trace Element Research, 2013)

Geophysical data sparse reconstruction based on L0-norm minimization - Guo-Xin Chen; Sheng-Chang Chen; Han-Chuang Wang; Bo Zhang (Applied Geophysics, 2013)

Seasonal variation of diet and time budget of Eastern hoolock gibbons (Hoolock leuconedys) living in a northern montane forest - Peng-Fei Fan; Huai-Sen Ai; Han-Lan Fei; Dao Zhang; Sheng-Dong Yuan (Primates, 2013)

Development of a new polyclonal antibody for the determination of polychlorinated biphenyls in indoor air by ic-ELISA - Han-Yu Chen; Hui-Sheng Zhuang; Guang-Xin Yang; Xiu-Ling Ji (Environmental Science and Pollution Research, 2013)

Characterizing the interactions between polycyclic aromatic hydrocarbons and fulvic acids in water - Rui Lu; Guo-Ping Sheng; Yi Liang; Wei-Hua Li; Zhong-Hua Tong; Wei Chen; Han-Qing Yu (Environmental Science and Pollution Research, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Complementary screening, identification and application of a novel class II 5-enopyruvylshikimate-3-phosphate synthase from Bacillus cereus - Yong-Sheng Tian; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Quan-Hong Yao (World Journal of Microbiology and Biotechnology, 2013)

Dual liver transplantation - Hao Chen; Ying Zhang; Yong-mei Han; Emmanue Huguet; Dong-sheng Huang; Jia-hong Dong (Journal of Zhejiang University-SCIENCE B, 2013)

Association of angiotensinogen M235T gene polymorphism with end-stage renal disease risk: a meta-analysis - Tian-Biao Zhou; Sheng-Sheng Yin; Yuan-Han Qin (Molecular Biology Reports, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Geographical differences and influencing factors of rural energy consumption in Southwest mountain areas in China: A case study of Zhaotong City - Wei Sun; Xiaoxu Han; Kerong Sheng; Jie Fan (Journal of Mountain Science, 2012)

Inverting reservoir parameters in a two-phase fractured medium with a niche genetic algorithm - Sheng-Qiang Zhang; Li-Guo Han; Chun-Cheng Liu; Yi-Ming Zhang; Xiang-Bo Gong (Applied Geophysics, 2012)

Diagnosis and Treatment of Xanthogranulomatous Cholecystitis: A Report of 39 Cases - Sheng-Hua Han; Yan-Ling Chen (Cell Biochemistry and Biophysics, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

RNAi knockdown of rice SE5 gene is sensitive to the herbicide methyl viologen by the down-regulation of antioxidant defense - Sheng Xu; Lijuan Wang; Bo Zhang; Bin Han; Yanjie Xie; Jie Yang; Weigong Zhong; Huiping Chen; Ren Wang; Ning Wang; Weiti Cui; Wenbiao Shen (Plant Molecular Biology, 2012)

High angle prestack depth migration with absorption compensation - Hui Zhou; He Lin; Shan-Bo Sheng; Han-Ming Chen; Ying Wang (Applied Geophysics, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

China’s wastewater discharge standards in urbanization - Wen-Wei Li; Guo-Ping Sheng; Raymond J. Zeng; Xian-Wei Liu; Han-Qing Yu (Environmental Science and Pollution Research, 2012)

Cyclic fluid shear stress promotes osteoblastic cells proliferation through ERK5 signaling pathway - Peng Li; Yan-chao Ma; Xiao-yun Sheng; Hai-tao Dong; Hua Han; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2012)

Analysis of gene expression profile of Arabidopsis genes under trichloroethylene stresses with the use of a full-length cDNA microarray - Bo Zhu; Ri-He Peng; Ai-Sheng Xiong; Xiao-Yan Fu; Wei Zhao; Yong-Sheng Tian; Xiao-Fen Jin; Yong Xue; Jing Xu; Hong-Juan Han; Chen Chen; Jian-Jie Gao; et al. (Molecular Biology Reports, 2012)

Sulfolobus tokodaii RadA paralog, stRadC2, is involved in DNA recombination via interaction with RadA and Hjc - Lei Wang; DuoHong Sheng; WenYuan Han; Bin Huang; ShanShan Zhu; JinFeng Ni; Jia Li; YuLong Shen (Science China Life Sciences, 2012)

PCSK9 siRNA inhibits HUVEC apoptosis induced by ox-LDL via Bcl/Bax–caspase9–caspase3 pathway - Chun-Yan Wu; Zhi-Han Tang; Lu Jiang; Xue-Fei Li; Zhi-Sheng Jiang; Lu-Shan Liu (Molecular and Cellular Biochemistry, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Using differential SAR interferometry to map land subsidence: a case study in the Pingtung Plain of SW Taiwan - Chia-Sheng Hsieh; Tian-Yuan Shih; Jyr-Ching Hu; Hsin Tung; Mong-Han Huang; Jacques Angelier (Natural Hazards, 2011)

Self-compatibility of ‘Zaoguan’ (Pyrus bretschneideri Rehd.) is associated with style-part mutations - Yong-Jie Qi; Ying-Tao Wang; Yan-Xiao Han; Sheng Qiang; Jun Wu; Shu-Tian Tao; Shao-Ling Zhang; Hua-Qing Wu (Genetica, 2011)

Genomic in situ hybridization (GISH) analysis of intergeneric hybrids in Colchicaceae - Daisuke Nakazawa; Tomonari Kishimoto; Takeru Sato; Tomoka Saito; Junji Amano; Sachiko Kuwayama; Hajime Okuno; Toshinari Godo; Yusuke Watanabe; Dong-Sheng Han; Masaru Nakano (Euphytica, 2011)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Metaproteomic characterization of dissolved organic matter in the water column of the South China Sea - Da-Zhi Wang; Hong-Po Dong; Zhang-Xian Xie; Min-Han Dai; Hua-Sheng Hong (Limnology and Oceanography, 2011)
We characterized dissolved organic matter (DOM;

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake I: Yingxiu town - Chang-Rong He; Ru Zhang; Qun Chen; Sheng-Li Han (Natural Hazards, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake II: Dujiangyan and Pengzhou City - Chang-Rong He; Qun Chen; Sheng-Li Han; Ru Zhang (Natural Hazards, 2011)

Identification of SNPs within the sheep PROP1 gene and their effects on wool traits - Xian-Cun Zeng; Han-Ying Chen; Bin Jia; Zong-Sheng Zhao; Wen-Qiao Hui; Zun-Bao Wang; Ying-Chun Du (Molecular Biology Reports, 2011)

Plant regeneration via direct and indirect adventitious shoot formation and chromosome-doubled somaclonal variation in Titanotrichum oldhamii (Hemsl.) Solereder - Hiroki Takagi; Shintaro Sugawara; Tomoka Saito; Haruka Tasaki; Lu Yuanxue; Guan Kaiyun; Dong-Sheng Han; Toshinari Godo; Masaru Nakano (Plant Biotechnology Reports, 2011)

RNA interference targeting CITRON can significantly inhibit the proliferation of hepatocellular carcinoma cells - Yinghui Fu; Jian Huang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular Biology Reports, 2011)

Single-stranded DNA binding activity of XPBI, but not XPBII, from Sulfolobus tokodaii causes double-stranded DNA melting - Xiaoqing Ma; Ye Hong; Wenyuan Han; Duohong Sheng; Jinfeng Ni; Guihua Hou; Yulong Shen (Extremophiles, 2011)

Life Cycle Assessment of a Wastewater Treatment Plant Focused on Material and Energy Flows - Jian-Guang Wu; Xiang-Yu Meng; Xiao-Meng Liu; Xian-Wei Liu; Zhi-Xia Zheng; De-Qian Xu; Guo-Ping Sheng; Han-Qing Yu (Environmental Management, 2010)

β-catenin signaling involves HGF-enhanced HepG2 scattering through activating MMP-7 transcription - Fei-Yan Pan; Sheng-Zhou Zhang; Na Xu; Fan-Li Meng; Hong-Xia Zhang; Bin Xue; Xiao Han; Chao-Jun Li (Histochemistry and Cell Biology, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Analysis of Olfactory Ensheathing Glia Transplantation-Induced Repair of Spinal Cord Injury by Electrophysiological, Behavioral, and Histochemical Methods in Rats - Kai-Jun Liu; Jin Xu; Chang-Yu Yang; Han-Bo Chen; Xiang-Sheng Liu; Yong-Deng Li; Zhan-Fei Li (Journal of Molecular Neuroscience, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

A single-nucleotide polymorphism of the TNFAIP3 gene is associated with systemic lupus erythematosus in Chinese Han population - Li-Qiong Cai; Zai-Xing Wang; Wen-Sheng Lu; Jian-Wen Han; Liang-Dan Sun; Wen-Hui Du; Shu-Mei Zhang; Xian-Bo Zuo; Xue-Jun Zhang; Sen Yang (Molecular Biology Reports, 2010)

Digenean parasites of Chinese marine fishes: a list of species, hosts and geographical distribution - Sheng-fa Liu; Wen-feng Peng; Peng Gao; Ming-jun Fu; Han-zhou Wu; Ming-ke Lu; Ji-qing Gao; Jun Xiao (Systematic Parasitology, 2010)

Isolation and characterization of 15 microsatellite loci from Caridina gracilipes (Atyidae, Decapoda) - Chiao-Chuan Han; Cheng-Sheng Chang; Tzen-Yuh Chiang; Ping-Han Chung; Hung-Du Lin (Conservation Genetics, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

An age-dependent proliferation is involved in the postnatal development of interstitial cells of Cajal in the small intestine of mice - Feng Mei; Jiang Zhu; Sheng Guo; De-shan Zhou; Juan Han; Bin Yu; Shi-feng Li; Zhong-yong Jiang; Cheng-jie Xiong (Histochemistry and Cell Biology, 2009)

Use of dual section mRNA in situ hybridisation/immunohistochemistry to clarify gene expression patterns during the early stages of nephron development in the embryo and in the mature nephron of the adult mouse kidney - Kylie Georgas; Bree Rumballe; Lorine Wilkinson; Han Sheng Chiu; Emmanuelle Lesieur; Thierry Gilbert; Melissa H. Little (Histochemistry and Cell Biology, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Sesquilignans and dilignans from Campylotropis hirtella (Franch.) Schindl. - Hui-Ying Han; Hong-Wei Liu; Nai-Li Wang; Xin-Sheng Yao (Natural Product Research, 2008)

A new ent-kauranoid from Isodon lophanthoides var. geradianus - Ying-Hong Liu; Sheng-Xiong Huang; Qin-Shi Zhao; Jin-Kai Ding; Ngoh-Khang Goh; Han-Dong Sun; Tet-Fatt Chia; Swee-Ngin Tan; Lian-Sai Chia (Natural Product Research, 2008)

Adrenal myelolipoma within myxoid cortical adenoma associated with Conn’s syndrome - Lu Hong-sheng; Gan Mei-fu; Chen Han-song; Huang Shan-qiang (Journal of Zhejiang University-SCIENCE B, 2008)

Mesozoic paleogeography and tectonic evolution of South China Sea and adjacent areas in the context of Tethyan and Paleo‐Pacific interconnections - Di Zhou; Zhen Sun; Han‐zong Chen; He‐hua Xu; Wan‐yin Wang; Xiong Pang; Dong‐sheng Cai; Deng‐ke Hu (Island Arc, 2008)
During the Mesozoic era, the South China Sea and its environs were located at the south‐eastern margin of the Eurasian continent. There has been hot debate on the influences of Tethyan and Paleo‐Pacific tectonics to the Mesozoic evolution of the area. This paper compiles lithofacies maps of six time slices and discusses the paleogeographic and tectonic evolution of the area based on this compilation and other data on structural deformation and magmatism. In the Early Triassic, the Paleotethys Ocean extended eastward to the study area through the Song Da passage. Then a significant east–west differential evolution began. In the Late Triassic, the western area uplifted as a result of the collision between the Indosinian and South China blocks during the Indosinian orogeny, and the Song Da passage has closed since then. Meanwhile, a transgression of Paleo‐Pacific waters occurred in the eastern and south‐eastern portions of the area, forming the ‘East Guangdong–North‐west Borneo Sea’. In the Early Jurassic, seawater transgression was even more pronounced, resulting into the connection of this sea with the Mesotethys Ocean to the west. Large quantities of Tethyan water carrying Tethyan organisms entered the area. In the Middle Jurassic, a short‐lived transgression occurred in the eastern Mesotethys and resulted in the formation of the ‘Yunnan–Burma Sea’. The Late Jurassic to Early Cretaceous was the climax of the subduction of both the Mesotethys and Paleo‐Pacific towards the Eurasian continent. This led to the formation of the great ‘Circum South‐east Asia Subduction–Accretion Zone’ in the Middle or Late Cretaceous. This paper also presents various lines of evidence for a newly recognized segment of this Mesozoic subduction–accretion zone buried under Cenozoic sediments in the north‐eastern South China Sea.

Molecular Characterization of Tree Peony Germplasm Using Sequence-Related Amplified Polymorphism Markers - Xiao Yan Han; Liang Sheng Wang; Qing Yan Shu; Zheng An Liu; Su Xia Xu; Takuya Tetsumura (Biochemical Genetics, 2008)

Expression, purification and characterization of pectate lyase A from Aspergillus nidulans in Escherichia coli - Qingxin Zhao; Sheng Yuan; Yuling Zhang; Hong Zhu; Chuanchao Dai; Fang Yang; Fengmin Han (World Journal of Microbiology and Biotechnology, 2007)

Benzyladenine and low temperature promote phase transition from juvenile to vegetative adult in bulblets of Lilium × formolongi ‘White Aga’ cultured in vitro - Takateru Ishimori; Yoshiji Niimi; Dong-Sheng Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Oogenesis in summer females of the rice water weevil, Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae), in southern Zhejiang, China - Sheng-wei Shi; Ming-xing Jiang; Han-wu Shang; Hui-ping Lv; Jia-an Cheng (Journal of Zhejiang University-SCIENCE B, 2007)

QTLs and candidate genes for chlorate resistance in rice (Oryzasativa L.) - Sheng Teng; Chaoguang Tian; Mingsheng Chen; Dali Zeng; Longbiao Guo; Lihuang Zhu; Bin Han; Qian Qian (Euphytica, 2006)

Localization of lily symptomless virus and cucumber mosaic virus in anther- and filament-derived calluses and effect of callus culture duration on virus-free bulblet production in Lilium × ‘Enchantment’ - Dong-Sheng Han; Yoshiji Niimi; Shuntaro Kimura (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

The distribution and economic losses of alien species invasion to China - Haigen Xu; Hui Ding; Mingyan Li; Sheng Qiang; Jianying Guo; Zhengmin Han; Zongguo Huang; Hongying Sun; Shunping He; Hairong Wu; Fanghao Wan (Biological Invasions, 2006)

The status and causes of alien species invasion in China - Haigen Xu; Sheng Qiang; Zhengmin Han; Jianying Guo; Zongguo Huang; Hongying Sun; Shunping He; Hui Ding; Hairong Wu; Fanghao Wan (Biodiversity and Conservation, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Inhibition of mitochondria responsible for the anti-apoptotic effects of melatonin during ischemia-reperfusion - Yi-xiang Han; Sheng-hui Zhang; Xi-ming Wang; Jian-bo Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Different effects on ACC oxidase gene silencing triggered by RNA interference in transgenic tomato - Ai-Sheng Xiong; Quan-Hong Yao; Ri-He Peng; Xian Li; Pei-Lai Han; Hui-Qin Fan (Plant Cell Reports, 2005)

SYNTHESIS BIODISTRIBUTION AND QSAR STUDIES OF FIVE Tc-99M LABELED NOVEL N3S PSEUDO-PEPTIDE COMPLEXES - Hua-bei Zhang; Hai-hong Ye; Ya-ling Zhang; Xuefang Zheng; Jian-sheng Han; Hua Li; Chun-ping Liu (Medicinal Chemistry Research, 2005)

Haploid plant regeneration via embryogenesis from anther cultures of Hepatica nobilis - Toshikazu Nomizu; Yoshiji Niimi; Dong-sheng Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Production of seedlings from ovules excised at the zygote stage in Lilium spp. - Noriko Ikeda; Yoshiji Niimi; Dong-Sheng Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Delayed cardioprotection induced by nitroglycerin is mediated by alpha-calcitonin gene-related peptide - Zhi-Hong Zhou; Jun Peng; Feng Ye; Nian-Sheng Li; Han-Wu Deng; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

High incidence of JC viruria in JC-seropositive older individuals - Han Chang; Meilin Wang; Rong-Tai Tsai; Hui-Sheng Lin; Jin-Shue Huan; Wen-Chuang Wang; Deching Chang (Journal of NeuroVirology, 2002)

Long term maintenance of an anther-derived haploid callus line of the Asiatic hybrid lily ‘Connecticut King’ - Dong-Sheng Han; Yoshiji Niimi; Masaru Nakano (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Regeneration of haploid plants from anther cultures of the Asiatic hybrid lily ‘Connecticut King’ - Dong-Sheng Han; Yoshiji Niimi; Masalu Nakano (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Zinc attenuation of GDP binding to brown adipocytes mitochondria in genetically obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Piin-Sheng Chen; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1997)